Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Reflections on technology, teaching, learning, and professional development: Findings from a teacher survey in Tanzania - Koomar, Saalim; Hennessy, Sara; Zubairi, Asma; Kindoli, Robert; Kreimeia, Adam (African Educational Research Journal, 2022)
This paper presents findings from a survey of 774 government school teachers across Tanzania over the period 2020-2021. The aims were to capture teachers' recent experiences concerning (1) access and use of technology; (2) any student learning losses observed, and teachers' recommendations to address lost learning; and (3) experiences and needs concerning teacher professional development (TPD). Key findings were (1) forty percent of teachers reported that their school lacked access to any form of technological device, with almost half stating they never used digital technologies for teaching and learning purposes. (2) Almost half of the teachers perceived that girls' learning suffered more than boys, and more than 60% of teachers believed learners from the financially poorest households suffered the greatest learning losses. (3) Teachers in Tanzania engaged in very little TPD and wanted increased support. The key differences across teacher groups were further examined by demographic factors, with notable differences apparent between urban and rural teachers, teachers with different levels of experience and different qualification levels. Recommendations are presented to stakeholders across the education ecosystem, including policymakers, school leaders, TPD designers, teachers, and researchers. The findings inform a national technology-mediated TPD programme in Tanzania.
Keywords: Access to Computers; Elementary School Teachers; Faculty Development; Foreign Countries; Gender Differences; Learning Processes; Pedagogical Content Knowledge; Poverty; Public School Teachers; Rural Urban Differences; Secondary School Teachers; Social Differences; Teacher Attitudes; Teacher Characteristics; Teacher Qualifications; Teacher Surveys; Teaching Experience; Teaching Methods; Technological Literacy; Technology Integration; Technology Uses in Education; _r:AddedByZotZen

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

School-based professional development in a developing context: Lessons learnt from a case study in Zambia - Haßler, Björn; Hennessy, S.; Cross, A. (Professional Development in Education, 2014)
This paper reports on the development and outcomes of the second phase of OER4Schools, a school-based professional development programme supporting interactive forms of subject teaching in conjunction with Open Educational Resources (OER) and technology in Zambian primary schools. We worked with partners to identify the needs of school-based continuing professional development adapted to the local context; the programme was based on participatory, collaborative and inquiry-based pedagogies for both classroom learning and teacher development. We worked over a one-year period with four experienced teachers in two basic (primary) schools serving disadvantaged communities. Data were collected from observations, interviews, surveys, lesson planning/review meetings and team workshops. All participants integrated OER and technology into mathematics and science lessons and developed more interactive practices, including collaborative learning. Professional dialogue, quality conversations, reflective practice, cultural sensitivity, peer learning and cooperation were pivotal mechanisms through which teachers shifted their focus from teaching (and teacher exposition) to student learning. Seeing students as capable individuals, teachers raised their expectations and developed insight into interactive practices such as group work, providing meaningful opportunities for student collaboration and active learning by all.
Keywords: Author:Haßler; Open Educational Resources; Zambia; digital technology; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; reflective practice; school-based professional development; sub-Saharan Africa

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
Keywords: _r:AddedByZotZen

Can Facebook groups enhance continuing professional development of teachers? Lessons from Kenya - Bett, Harry; Makewa, Lazarus (Asia-Pacific Journal of Teacher Education, 2020)
Continuing Professional Development (CPD) for teachers in Kenya suffers from challenges such as inadequate resources, poor planning, competing interests, among others. Besides being traditional in approach, most CPD sessions are far between to be meaningfully helpful. With increasing uptake of technology and number of social media users in Kenya, Facebook can be a potential platform to enhance teachers’ professional development. This exploratory cross-sectional survey focussed on discussions teachers had in the month of February 2015 on one Facebook Group named ‘Teachers of English’. A directed content analysis of the 647 posts following Shulman’s category of teacher knowledge base revealed that interactions on the group centred on the teaching of English and Literature, as well as on other education-related matters. This study concludes that that Facebook Groups can be fertile avenues for teachers’ ongoing professional development, especially in developing countries where such opportunities are scarce.
Keywords: Content analysis; Education--Teaching Methods And Curriculum; English teachers; Facebook Groups; Kenya; Professional development; Social networks; Teacher education; Teachers; __:import:02; __:match:final; __:matched; __:study_id:2425933; __finaldtb; professional development

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Developing dialogic classroom practices through supporting professional agency: Teachers’ experiences of using the T-SEDA practitioner-led inquiry approach - Calcagni, Elisa; Ahmed, Farah; Trigo-Clapés, Ana Laura; Kershner, Ruth; Hennessy, Sara (Teaching and Teacher Education, 2023)
Classroom dialogue is considered productive for learning but rarely observed, and practitioner professional development is needed. This study investigated how 67 teachers across educational phases in six countries contextualised the T-SEDA inquiry toolkit to conduct classroom inquiries and develop new practices. Surveys and inquiry reports yielded insights into how practitioner agency was further developed, with implications for sustainability. Change was evident in self-reported enhanced awareness and understanding of dialogue and use of dialogic strategies. Increases in students’ dialogic participation and plans for dissemination to colleagues were reported.
Keywords: Classroom dialogue; Dialogic teaching; Professional development; Professional learning; Reflective inquiry; Teacher agency

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Dual-mode teacher professional development: challenges and re-visioning future TPD in Indonesia - Widodo, Ari; Riandi (Teacher Development, 2013)
This paper presents the results of a two-year research project aimed at developing a teacher professional development (TPD) model in Indonesia. New government policies in this nation, its archipelagic nature, vast numbers of teachers and scarcity of support resources present a unique challenge to TPD. A needs assessment was conducted to identify teachers’ professional needs. Based on the results of this assessment, a dual-mode TPD that combines face-to-face sessions and online sessions was developed. Participation in face-to-face sessions was relatively high but the participation rate in online sessions was very low. Incentives, teachers’ autonomy as professional learners, ICT skills and infrastructure are important considerations when designing TPD in Indonesia. This study and an analysis of TPD policy allow us to suggest future directions for TPD in Indonesia
Keywords: CONTINUING education; EDUCATION & state; EDUCATION -- Forecasting; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Change; Educational Strategies; Elementary Secondary Education; FORECASTING; Faculty Development; Foreign Countries; HIGHER education; Higher Education; INDONESIA; Indonesia; Information Skills; Instructional Design; Interviews; Models; Needs Assessment; Online instruction; PROFESSIONAL education; Pedagogical Content Knowledge; Postsecondary Education; Professional development; Public policy; Questionnaires; Science Teachers; TEACHER certification; TEACHER development; TEACHER education; Teacher Education; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2097039; ___working_potential_duplicate; __finaldtb; dual-mode professional development; online training; teacher certification; teacher education; teacher education futures; teacher professional development in Indonesia

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

Evaluating the impact of teacher professional development: an evidence-based framework - King, Fiona (Professional Development in Education, 2014)
Keywords: C:Ireland

School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
Keywords: Lebanon; professional development; schools; ⛔ No DOI found

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Exploring Teacher Digital Skills and Literacy Competencies: A curated list of frameworks and resources to inform UNICEF Thailand - Flam, Rebekka; Upadhyay, Arjun; Thang, Sarah (EdTech Hub, 2025)
This report was developed in response to a request from UNICEF Thailand for a curated list of digital skills and literacy frameworks designed for teachers. It reviews and compares 16 global, regional, and national frameworks to inform the development or adaptation of teacher-specific training and materials in Thailand. Key insights include the multidimensional nature of digital literacy, the central role of teacher development, and the alignment of learner-centred approaches with competency-based education (CBE). The report concludes with practical recommendations for policymakers, educators, and practitioners in Thailand involved in designing or implementing digital skills and literacy frameworks. Keywords: Digital literacy; digital skills frameworks; teacher competencies; Thailand; Southeast Asia; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

Teachers’ professional development through the English in Action Secondary Teaching and Learning Programme in Bangladesh: experience from the UCEP schools - Shohel, M. Maruf C; Banks, Frank (Procedia-Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training
Keywords: EiA Intervention; Experiential Learning; Secondary Teaching and Learning Programme; Teachers’ Professional Development; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2457264; __finaldtb

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language -- Study & teaching -- Foreign speakers; Education--Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS -- Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: Bangladesh; Education--Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

The lesson study approach to professional development: Promoting teachers' peer mentoring and communities of practice and students' learning in Egypt - Elkomy, Maha M.; Elkhaial, Nevien H. (Teaching and teacher education, 2022)
The purpose of this study was to explore the impact of the lesson study (LS) approach on developing knowledge and perception of peer mentoring (PM) and communities of practice (CoPs) among kindergarten (K.G.) teachers in Egypt. It also aimed to improve students' learning in science concepts and English vocabulary due to teachers' participation in LS. A mixed methods design was employed. Results show that the LS approach provided a rich context for practicing PM experiences and helped teachers to collaborate in a CoP. Further gains were also achieved regarding students’ learning. •Effects of LS on PM and CoP among teachers were investigated.•The impact of the activities developed during LS on students' learning was assessed.•The study was composed of two samples: 21 teachers and 246 learners.•Significant results were obtained concerning teachers' knowledge and perceptions of PM and CoP.•Positive effects on students' learning of science and English were also found.
Keywords: Community of practice; Education & Educational Research; English learning; Lesson study; Mentors; Peer-mentoring; Professional development; Professional learning; Science learning; Sciences education; Social Sciences; Teachers

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Examples of mobile phones being used with teachers to provide continuing professional development (CPD) in emerging economies at scale are largely absent from the research literature. We outline English in Action’s (EIA) model for providing 80,000 teachers with CPD to improve their communicative language teaching in Bangladesh over nine years. EIA’s CPD program is delivered face to face and supported through open distance learning (ODL). This innovative model of teacher CPD is supported through peer learning and self-study using a variety of print, audio and video resources. Drawing on the success of EIA’s pilot studies, where internal and external evaluation reported significant improvement in teachers’ and students’ English-language competence after one year, the current phase is using low-cost mobile phones, or the ‘trainer in your pocket’ to deliver CPD to 12,500 teachers through 2015. We believe EIA’s teacher CDP model is best suited to assist the project in achieving one of its primary goals: to increase the English-language proficiency of 12 million students, allowing them to access greater social and economic opportunities in the future. We argue EIA’s use of mobile phones for the provision of teacher CPD – at scale – is timely and replicable in both developed and developing contexts.
Keywords: English in Action; communicative language teaching; mobile phones; open distance learning; school-based professional development (SBPD); teachers’ continuing professional development (CPD)

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M.; Mahruf, C.; Banks, Frank (Teacher Development, 2012)

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Experimenting With Teacher Professional Development: Motives and Methods - Wayne, Andrew J.; Yoon, Kwang Suk; Zhu, Pei; Cronen, Stephanie; Garet, Michael S. (Educational Researcher, 2008)
A strong base of research is needed to guide investments in teacher professional development (PD). This article considers the status of research on PD and articulates a particular direction for future work. Little is known about whether PD can have a positive impact on achievement when a program is delivered across a range of typical settings and when its delivery depends on multiple trainers. Despite a consensus in the literature on the features of effective PD, there is limited evidence on the specific features that make a difference for achievement. This article explains the benefits offered by experiments in addressing current research needs and?for those conducting and interpreting such studies?discusses the unique methodological issues encountered when experimental methods are applied to the study of PD.
Keywords: C:United States / International

Video as a tool for fostering productive discussions in mathematics professional development - Borko, Hilda; Jacobs, Jennifer; Eiteljorg, Eric; Pittman, Mary Ellen (Teaching and Teacher Education, 2008)
This article explores the use of classroom video as a tool for fostering productive discussions about teaching and learning. The setting for our research is a 2-year mathematics professional development program, based on the Problem-Solving Cycle model. This model relies on video from the teachers’ own classrooms and emphasizes creating a community in which members feel comfortable learning from video. We describe our experiences carrying out the Problem-Solving Cycle model, focusing on our use of video, our efforts to promote a supportive and analytical environment, and the ways in which teachers’ conversations around video developed over a 2-year period.
Keywords: C:United States; Mathematics education; Mathematics teachers; Professional development; Teacher learning; Video

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Professional Development in Tanzania: Challenges and Opportunities - Komba, Sotco Claudius; Mwakabenga, Rehema Japhet (Educational Leadership, 2019)
This chapter is about teacher professional development in Tanzania. The authors have examined the current status of teacher professional development in Tanzania, focusing on predominant perspectives on the concept and provision modalities. In addition, the authors have identified challenges facing teacher professional development in Tanzania, most of which seem to be systemic. The challenges include lack of explicit policy and guidelines for teacher professional development, limited knowledge on teacher professional development among teacher professional development stakeholders, predominance of traditional approach to teacher professional development, and ineffective organization of teacher professional development activities. It is, thus, concluded that a number of opportunities are available for effective teacher professional development in Tanzania. These include strengthening the available institutions responsible for teacher professional development, making use of different teacher professional development providers available in the country to promote professional development activities for teachers through a harmonized scheme and capitalizing on the use of different communication networks and the national optic fiber to promote self-directed teacher professional development.
Keywords: _Tanzania; _final_bib

Support provided for K-12 teachers teaching remotely with technology during emergencies: A systematic review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel (Journal of Research on Technology in Education, 2021)
Emergencies can cause disruption to education. This study is unique in providing the first empirical systematic review on teacher support for Emergency Remote Education (ERE) from 2010 to 2020. A total of 57 studies emerged from the PRISMA search. This mixed-method study used deductive and inductive iterative methods to examine the data. The data reveal teacher support strategies from across 50 different high and low-income countries. Few studies focused on a teacher’s subject and the age range taught. In the examination of professional development provided to prepare K-12 teachers to conduct ERE, eight codes emerged from the grounded coding as; 1) prior preparation, 2) understanding ERE, 3) needs analysis, 4) digital pedagogical strategies, 5) technology tools, 6) frameworks, 7) digital equity, and 8) mental wellness.
Keywords: COVID-19; Teacher education; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:CopiedFromEvLib; _yl:a; disasters; emergencies; emergency remote education; pandemic; remote education

TCPD in Tanzania: Design-Based Implementation Research Cycle 2 Recommendations - Chachage, Kristeen; Koomar, Saalim; Swai, Calvin; Massam, Winston; Hennessy, Sara; Masonda, Jonathan Paskali; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Frederick; Komba, Aneth; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the second cycle of the DBIR carried out between September and November 2023. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; Tanzania; communities of learningAn output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teachers’ self-directed professional development: science and mathematics teachers’ adoption of ICT as a professional development strategy - Mushayikwa, Emmanuel (African Journal of Research in Mathematics, Science and Technology Education, 2013)
This paper is part of a larger study that was carried out to investigate the use of information communication technology (ICT) in the self-directed professional development (SDPD) of mathematics and science teachers in Zimbabwe. The educational context provides an example of how teachers compensated for lack of structured government initiatives to support teachers' professional development. This paper focuses on the ways in which these teachers were using ICT resources to further their professional development. The study is based on 259 questionnaire responses from A-level Science and Mathematics teachers in Zimbabwe. Doyle and Ponder's "Practicality Ethic" and Loucks-Horsley et al.'s "Concerns-Based Adoption Model" provided the theoretical framework for analysing teachers' decision making and led to the development of a model for teacher empowerment with respect to the use of ICT. The study results showed that around 60% of teachers experienced difficulties in accessing ICT for their professional development. About half of the non-users did not access ICT even when it was available at their schools. Some of those who did access ICT used innovative methods to ensure access, including using their own resources, and pooling resources. The findings also show that teachers have three main drivers for using ICT for SDPD, including word processing for generating instructional materials; accessing and downloading web-based learning materials; and emailing for networking with peers and professional organisations. The results of this study demonstrate the great potential that ICT has for teachers' SDPD.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096430; __finaldtb

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.

Improving teacher professional development for online and blended learning: a systematic meta-aggregative review - Philipsen, Brent; Tondeur, Jo; Pareja Roblin, Natalie; Vanslambrouck, Silke; Zhu, Chang (Educational Technology Research and Development, 2019)
In order to fully realise the potential of online and blended learning (OBL), teacher professional development (TPD) strategies on how to teach in an online or blended learning environment are needed. While many studies examine the effects of TPD strategies, fewer studies target the specific important components of these strategies. This study addresses that gap by conducting a systematic review of qualitative data consisting of 15 articles on TPD that targets OBL. Using a meta-aggregative approach, six different synthesised findings were identified and integrated into a visual framework of the key components of TPD for OBL. These synthesised findings are the base for the action recommendations which present specific and contextualised suggestions. Taken together, the findings can inform in-service teachers and trainers, together with further research and development efforts that are concerned with TPD for OBL.

Teacher Professional Development and Student Literacy Growth: a Systematic Review and Meta-analysis - Basma, Badriah; Savage, Robert (Educational Psychology Review, 2018)
This systematic review explores the impact of teacher professional development (PD) on student reading achievement. The first part of the literature evaluates all available existing systematic reviews and meta-analyses of PD intervention studies. No quality reviews of PD and reading specifically (distinct from ‘attainment’) were found. There was a little overlap of studies in existing reviews. The second part of the systematic review focuses on the most recent intervention studies exploring PD and student reading achievement. The results of a meta-analysis of all high-quality studies are presented in the third part of the paper. This analysis showed no strong evidence of publication bias and an effect size for PD on student literacy of g = 0.225. This effect was moderated by the number of hours of PD whereby studies with fewer than 30 h of PD was significant for student reading outcomes (g = 0.367, p < 0.001) but more than 30 PD hours was not significant (g = 0.143, p > .05). Following a Weight of Evidence assessment, analysis showed that nearly all high-quality articles involved shorter PD. Weight of Evidence was a significant moderator, (g = 0.408, p < 0.001 for high-quality studies, g = 0.077, p > 0.5, n.s., for medium quality studies). Our review suggests that only high-quality studies of short teacher PD currently provide evidence of impact on student’s reading achievement.
Keywords: C: International

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pedagogic change by Zambian primary school teachers participating in the OER4Schools professional development programme for one year - Hennessy, Sara; Haßler, Björn; Hofmann, R. (Research Papers in Education, 2016)
Supporting and upskilling teachers are essential to enhancing the quality of learning in developing contexts – the focus of Education For All – yet little evidence exists concerning what kinds of teacher education are actually most effective and what changes in ‘quality’ are desired and feasible. This paper illustrates how a concrete, research-informed school-based, model of professional development in sub-Saharan Africa can address the quality agenda. It reports on a trial of a pioneering, multimedia programme supporting interactive mathematics and science teaching using open educational resources and classroom digital technology, where available. The programme was carefully adapted to the Zambian context and ran weekly for one school year with 12 teachers in a low-resourced primary school. The study examined the impact on teachers' thinking and classroom practices. Data were derived from observations, lesson and workshop recordings, teacher interviews, portfolios and audio diaries. Through a teacher-led workshop approach and trialling new pedagogical strategies, teachers raised their expectations of pupils, adapted to learners’ knowledge levels, used more practical and group work, and integrated technology use. Pupils built deeper understanding of subject matter, were actively engaged, worked collaboratively and used digital technologies for problem-solving.
Keywords: C:sub-Saharan Africa; CAREER development; EDUCATION -- Study & teaching; GRADUATE education; PROFESSIONAL education; TEACHER training; ZAMBIA; Zambia; __:import:01; __:match:final; __:matched; __:study_id:2099887; ___working_potential_duplicate; __finaldtb; digital technology; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Technology use for teacher professional development in low- and middle-Income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: Disability; ICT; Read; Referenced; Teacher education and training; Teacher professional development; What works evidence; _EdTechHub_Output; _MELA_knowledge_product; _MELA_seen; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology; ⛔ No DOI found

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Implementing school-based teacher development in Tanzania - Hardman, Frank; Hardman, Jan; Dachi, Hillary; Elliott, Louise; Ihebuzor, Noel; Ntekim, Maniza; Tibuhinda, Audax (Professional Development in Education, 2015)
This paper reports on the findings of a pilot school-based professional development programme for Tanzanian primary school teachers launched in February 2011 and evaluated in December 2012 by the Ministry of Education and Vocational Training with the support of UNICEF. The study set out to investigate the effectiveness and efficiency of the pilot programme in changing pedagogical practices before it was scaled up nationally. It was found that teachers who had participated in the school-based training showed significant differences in their pedagogical practices and demonstrated a positive attitude towards their training and their pupils, and saw teaching and learning as an interactive, communicative process. Drawing on the findings, the paper explores the challenges and the lessons learned for scaling up school-based teacher development at the national level in Tanzania and other countries in the east and southern African region.
Keywords: Tanzania; __C:filed:1; capacity development; primary education; quality education; school-based teacher development; teacher education reform

Development of a cadre of teacher educators: some lessons from Pakistan - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2004)
This article is based on an educational innovation, the creation of a cadre of teacher educators, in the developing world. Professional development teachers (PDT) were trained in an in-service two-year teacher education programme leading to a Masters of Education (M.Ed.) degree. The PDTs were expected to play three roles in their home schools upon completion of the degree programme: (a) exemplary teachers; (b) teacher educators; and (c) change agents within their home schools to effect improvement. This article reviews education in Pakistan and the innovations that have come to inform the need to focus on teacher education as a primary area of investment and presents findings of a three-year longitudinal study of a selection of PDTs trained at the Aga Khan University’s Institute for Educational Development (AKU-IED). The main findings of the study indicate that teachers benefited significantly as individuals with enhanced career prospects, identified themselves more and preferred the role of teacher educators as opposed to classroom-based teachers, and sought opportunities outside their own schools but their role as change agents was more limited. Those teachers who maintained links with their schools beyond the three-year bonding period (a condition of being admitted to study for the M.Ed.) varied in the extent to which they managed to initiate and sustain school improvement efforts as indicated by changes in the structures and relationships within schools affecting the teaching–learning offered to pupils.
Keywords: Development; Educational policy; International education; Pakistan; School improvement; Teacher education

Exploring Blended Learning for Science Teacher Professional Development in an African Context - Boitshwarelo, Bopelo (The International Review of Research in Open and Distributed Learning, 2009)
This paper explores a case of teacher professional development in Botswana, where a blended learning solution was attempted. The analysis of the implementation environment reveals deficiencies in policy, schools (workplaces), and training providers. The paper concludes with three recommendations: 1) Schools should support on-going teacher learning in the workplace and should manage ICT resources for use by both teachers and students; 2) Government should support participatory and localised learning and institutionalise ICT access and use; and 3) Training providers should use blended methods and should model good ICT practices. The author also notes that change is needed in the culture of teaching and learning so that ongoing, situated, participatory, and collaborative approaches are accepted. Finally, collaboration between the training providers and the schools is necessary as is a change in beliefs about the use of ICTs in education.
Keywords: C:Botswana; ICTs; Pedagogy; Professional Development; Teacher Training; ___working_potential_duplicate

Teacher Professional Development in Africa: A Critical Synthesis of African Research Evidence - Mitchell, Rafael; Ayinselya, Roger A.; Barrett, Angeline M.; Cortez, Artemio; David, Opanga; Imaniriho, Dan; Nwako, Zibah; Reda, Nigusse Weldemariam; Singh, Marcina (Zenodo, 2024)
This study is an original synthesis of African research evidence on teacher professional development (TPD) provision in the sub-Saharan region. It provides a critical appraisal of the evidence base and identifies patterns in the actors and agendas involved in TPD initiatives; the modes and modalities of provision; and teachers’ experiences and outcomes. The study takes the form of a critical interpretive synthesis (CIS) and is informed by theoretical work on decolonising education (Ndlovu-Gatsheni 2013) and promoting Gender Equality and Social Inclusion (GESI). It draws primarily on publications by African-based researchers, where our research team is largely based. The findings point to the prevalence of one-size-fits-all provision can which often undermine, rather than strengthen, the situated professional knowledge and agency of teachers. Additionally, despite the emphasis given to inclusive education and gender-responsive pedagogy as a substantive focus of TPD initiatives, we find that dominant modalities of TPD provision continue to exclude historically marginalised groups, and largely reproduce existing social inequalities along the lines of gender, rurality, dis/ability and other dimensions. Alongside these negative findings, the study also finds fertile ground for more inclusive, generative and empowering TPD in the region.
Keywords: Educational sciences

Professional Development for K–12 Math and Science Teachers: What Do We Really Know? - Scher, Lauren; O'Reilly, Fran (Journal of Research on Educational Effectiveness, 2009)
As investments in K–12 math and science professional development programs expanded over the past decade, researchers and policymakers have questioned whether and how such programs work to improve student learning. This article summarizes the current knowledge-base and offers a theoretical framework researchers can use to design studies that explore mechanisms through which professional development programs inﬂuence teacher knowledge, teacher practices, and ultimately student achievement. We quantitatively pool the most rigorous evaluation research available to determine whether currently held beliefs in the ﬁeld are supported by the evidence. Although this study does ﬁnd some support for the guidance propounded by experts, it cautions policymakers and practitioners that the current evidence base is thin. We urge researchers to build on what we have learned through theory and practice to increase the rigor of evaluations on this important topic by incorporating valid and reliable measures of professional development components as well as valid measures of teacher knowledge and practices.
Keywords: C:United States

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

Teacher knowledge and employer-driven professional development: a critical analysis of the Gauteng Department of Education programmes - de Clercq, Francine; Shalem, Yael (Southern African Review of Education, 2014)
There is growing consensus in international and local literature that, to be effective, professional development activities (PDAs) should focus on ways of teaching that improve learners' learning, but there is no clear consensus on the teaching focus and the form in which teacher learning is organised. Drawing from literature on teacher knowledge, in particular Shulman's distinction between subject matter and pedagogical content knowledge (PCK), this article critically reviews the PDAs provided by the Gauteng Department of Education (GDE), South Africa. It identifies 2009 as a turning point in the GDE provision of PDAs. Until 2009, most PDAs were targeted at the improvement of a few discrete aspects of teacher practice, to comply with a new curriculum framework. Around 2009, the GDE turned towards scripted teaching in a form of standardised lesson plans, to engineer a whole new practice for teachers in order to improve learners' results. The argument of this article is that teacher knowledge of subject matter, consisting of knowledge of the substantive and syntactic aspects of the curriculum content and beyond, has not been imparted to teachers by employer-driven curriculum implementation workshops or short courses, and that only a limited number of teaching routines such as sequencing and pacing of the curriculum content can be imparted by scripted lesson plans. Although the idea of scripting a new practice is understandable in the light of the general agreement that PDAs in South Africa failed to make a difference to teachers' practice and to learners' performance, it is essential to understand its limitations., Y. (2014) Teacher knowledge and employer-driven professional development: A critical analysis of the Gauteng Department of Education programmes. Southern African Review of Education, 20(1): 129-147.
Keywords: ⛔ No DOI found

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.

A Co-design Methodology for Blended Teacher Professional Development in Contexts of Mass Displacement.pdf - Kennedy, E; Moghli, MA; Chase, E; Pherali, T; Laurillard, D
Teachers working in challenging contexts of mass displacement need both expert and peer support. This article shares a co-design methodology being used to develop and test the use of what we are calling Massive Online Open Collaborations (MOOCs) which involve blended learning approaches for teacher professional development
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_supporting educators

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The OER4Schools professional development programme: Outcomes of a sustained trial in sub-Saharan Africa - Haßler, Björn; Hennessy, Sara; Hoffmann, R; Makonga, Abel (Frontiers in Education, 2020)
Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention showed that the programme became self-sustaining; earlier participants reported further development of their interactive teaching strategies and awareness of pupil progress; recent joiners developed similarly. Roles of teachers and pupils changed and a new classroom culture emerged. The study identifies the key mechanisms involved in sustainability, including culturally sensitive and participatory development and implementation, semi-structured multimedia materials, and supportive organisational structures for sustained professional learning. Our findings are hence framed by sociocultural influences as well as the wider policy context.
Keywords: Author:Haßler; C: Zambia; Culturally responsive pedagogy (CRP); Design-based implementation research; Interactive Pedagogy; Learner-centred pedagogy; School leadership; Sustainable Development Goal (SDG) 4; Teacher Profesisonal Development; Zambia; ___working_potential_duplicate; _yl:b; dode_eth-src-dode; dode_eth-trf2-dode; school improvement; sub-Saharan Africa

Teachers of Refugees: A Review of the Literature - Richardson, Emily (Education Development Trust, 2018)
The United Nations High Commissioner for Refugees (UNHCR) estimates that 65.6 million people are forcibly displaced, having either crossed national borders or become internally displaced within their own countries. Of this estimate, over 22.5 million are refugees. Over half of the world's refugees are children. With an average length of displacement of approximately 20 years, the majority of these children will spend their entire childhoods away from home. Refugee children have limited access to basic social services like healthcare and education. Given the length of their displacement, generations of refugee children throughout the world could miss out on education altogether. Numerous studies show that the teacher is the most important in-school factor affecting the quality of education, particularly in refugee contexts, where the teacher is sometimes the only resource available to students. In refugee contexts where infrastructure and resources are limited, the role of the teacher is particularly important to the quality of education. However few studies to date have examined the role of teachers in refugee contexts. With more literature focusing on refugee children and youth, little is known about who the teachers of refugees are and how they are recruited, trained, retained, compensated and managed in their contexts. Importantly, there is little research on national teachers who are teaching refugee children; rather, much of the available literature focuses on refugee teachers -- that is, teachers who are also refugees. In addition, this lack of literature on teachers of refugees hinders our understanding not only of their needs but also of 'how refugees can contribute to education in their host countries and (eventually) to their home countries'. The purpose of this literature review is to survey policies, practices and debates that governments and their partners must navigate to provide education for refugee populations, and the strategies they have used to select and manage teaching forces. The review analyses findings from the main literature on teachers of refugees according to the following themes: (1) recruitment, certification and selection of teachers; (2) teacher preparation and development; (3) teacher remuneration and incentives; and (4) teacher retention. In addition, for each of these themes, this review highlights the salient gaps in the research and suggests an agenda for further research. [Co-written with Leonora MacEwen and Ruth Naylor.]
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_supporting educators

Teachers’ conception towards the use of social networks as a tool for professional development in Tanzania government secondary schools: the case of Dodoma municipality - Manyama, Charles (University of Dodoma, 2017)
The current study sought to assess teachers' conception toward the use of social networks as a tool for professional development in Tanzania government secondary schools the case of Dodoma Municipality. Thus, the specific objectives of this study were to assess the influence of demographic characteristics on the use of social networks or as a tool for professional development. To assess teachers conception on the available social networks opportunity that can support professional development, to investigate teachers use of social networks available for professional development, to explore the perceived benefits of using social networks opportunity as a tool for professional development and to examine limitation that hinder teachers for professional development. The study was guided by social-cognitive theory, community of practice model (CoP) and technology acceptance model (TAM). A cross-section research design was used to collect data that involved 84 teachers‟ from ten secondary schools, six head of schools three quality assurers and one respondent from DEO office. SPSS computer program was used to analyze the data. Qualitative data were analyzes through content analysis and quantitative data were analyzed statistically using descriptive and inferential statistics by using SPSS Version 20, and Microsoft Excel were highly used. Linear regression techniques were used to seek whether there is a relationship between demographic characteristics and the use of social networks. The survey results showed that there is no significant relationship between demographic factors with the use of social networks as a tool for professional development. Either teachers have positive conceptions towards the use of social networks as a tool for professional development. Furthermore, teachers use SNs for communicating with their fellow from different groups but it is not effectively integrated into professional development. The findings indicate that, to a large extent, teachers agreed that SNs make them to be more creative and help them to improve their communication skills. In addition the findings indicated that teachers lack training on how to integrate SNs in TPD. Finally,the researcher recommend that, educational stakeholders should provide financial and material support to teachers in order to overcome challenge that limit the use of technology in teaching and learning.
Keywords: ⛔ No DOI found

Using video for professional development: the role of the discussion facilitator - Coles, Alf (Journal of Mathematics Teacher Education, 2013)
Past research into the use of video for professional development has failed to problematise or theorise sufﬁciently the role of the discussion facilitator. It has been reported consistently that it can be hard or take time to establish norms for discussion of video but little has been said about reasons why, or the role of the discussion facilitator. As a starting point in this area, I suggest ﬁves aspects or decision points in the role of the facilitator. Two aspects are taken from the literature and the others are drawn from empirical data, collected as part of an enactivist study into the use of video in one secondary school. At the school, teachers commented on ﬁnding video watching in a group more useful than lesson observation, with no evidence of this taking time to develop. I offer speculations, based on enactivist category theory, as to why the use of video in this school is effective. Having presented key aspects of the role of the facilitator of video use, a further look at the detail of the data from discussions serves to highlight some of the complexities involved in just one of the categories (and, by implication, the others). I conclude that the role of the facilitator cannot be separated from a consideration of the historical context in which discussion takes place.

What makes professional development effective? Results from a national sample of teachers - Garet, Michael; Porter, Andrew; Desimone, Laura; Birman, Beatrice; Yoon, Kwang Suk (American Educational Research Journal - AMER EDUC RES J, 2001)
This study uses a national probability sample of 1,027 mathematics and science teachers to provide the first large-scale empirical comparison of effects of different characteristics of professional development on teachers’ learning. Results, based on ordinary least squares regression, indicate three core features of professional development activities that have significant, positive effects on teachers’ self-reported increases in knowledge and skills and changes in classroom practice: (a) focus on content knowledge; (b) opportunities for active learning; and (c) coherence with other learning activities. It is primarily through these core features that the following structural features significantly affect teacher learning: (a) the form of the activity (e.g., workshop vs. study group); (b) collective participation of teachers from the same school, grade, or subject; and (c) the duration of the activity.

Teacher professional learning and development: best evidence synthesis iteration (BES) - Timperley, Helen (Ministry of Education, 2007)
Keywords: C:New Zealand

Teachers’ professional development through the English in action secondary teaching and learning programme in Bangladesh: Experience from the UCEP schools - Shohel, M; Banks, F; Banks, F (Procedia - Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training.

Guidance Note 10 Prioritising effective and appropriate teacher training From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Teacher educators and OER in East Africa: Interrogating pedagogic change - Wolfenden, Freda; Auckloo, Pritee; Buckler, Alison; Cullen, Jane (Adoption and Impact of OER in the Global South, 2017)
This study examines the use of Open Educational Resources (OER) in six teacher education institutions in three contrasting East African settings – Mauritius, Tanzania and Uganda – all of which had previous engagement with OER initiatives. Drawing primarily on interviews with teacher educators, the study examines how and when teacher educators engage with OER, the factors that support and constrain sustained OER engagement, and the influence of such engagement on their teaching practice. It seeks to answer the following three research questions: What kinds of OER are teacher educators aware of and how do they access them? How and for what purpose are they using the OER? What intended and enacted pedagogic practices are associated with OER use? The study takes a sociocultural approach, paying attention to the practices of teacher educators and the context and culture of the teacher education institutions within which they work, as well as the national policies relevant to these institutions. Surveys were sent to academic staff at each of the participating institutions who were, or had been, involved in curriculum development work involving OER. Male and female educators from different disciplinary backgrounds and with varying roles and periods of service within the institutions were targeted. From the respondents, selected individuals were asked to participate in semi-structured interviews concerning OER and their pedagogical practices. A total of 58 surveys were completed by teacher educators along with 36 in-depth teacher educator interviews and six institutional stakeholder interviews. The results of the study indicate that teacher educators’ understanding and use of OER is highly fragmented, with little traction at department or institutional level. At all the study sites there was dissonance between the ways in which individual educators are using OER and the dominant institutional values and discourse. There were also numerous structural and cultural factors acting to limit agency with regards to OER use. The demands of curriculum and assessment, professional identity, digital skills, provision of equipment and connectivity, values and weak cultures of collaboration all exerted an influence and enabled or constrained teacher educators’ efforts to achieve agency with OER. For a small number of teacher educators (OER “champions”), OER provides a tool for extending their agency to move towards more participatory practices. In their interviews, several of these educators spoke of the formative role of academic training and many were linked to external OER networks. These elements of historic identity formation influence how they respond to OER, and enhance their confidence to take risks in moving beyond conventional practice. Enabling educators to act in an agentive way with OER is not easy. Moving forward, attention should be given to issues of access so that educators are able to locate and view OER relatively easily and experiment with their use. This study recommends that time be made available for educators to enhance their skills in working digitally and to become familiar with principles of learning design such that these become integral dimensions of their professional identity. It is also argued that extending and deepening engagement with OER requires opportunities for professional dialogue and collaboration to support the development of productive educator identities with OER and transformation of the community’s field of practice.
Keywords: East Africa; Global South; Mauritius; OEP; OER; Open Education; Open Educational Resources; ROER4D; Tanzania; Uganda; _not_EdTechHub; _zenodoOTHER; agency; pedagogy; teacher education

Moving education into the digital age: the contribution of teachers' professional development - Twining, P.; Raffaghelli, J.; Albion, P.; Knezek, D. (Journal of Computer Assisted Learning, 2013)
This article introduces the main outcomes of discussions at EDUsummIT 2011 by the specific Technical Working Group on Teacher Professional Development (TWG3). The focus was to explore how professional development of teachers may ensure that teachers are better prepared to use information and communication technology (ICT) to promote 21st century learning. The article is organized into three main sections: a review of key literature on professional development of teachers (TPD), in general and with specific reference to ICT; a summary of the key points emerging from TWG3's discussions; and recommendations for action. On the basis of discussions held within the TWG3, the authors concluded that effective TPD requires changes at several levels of educational systems (political, institutional and individual), and that ICTs should be seen as an opportunity for introducing new goals, structures and roles that support these changes. It is significant that while many of the issues highlighted by the group are well established, addressing them continues to be problematic globally.
Keywords: ICT; IT; digital age; policy recommendations; practitioner research; teacher professional development; transformation

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Empowerment Through Curriculum Development: Theory Into Practice - Carl, Arend E. (Juta and Company Ltd, 2009)
Treating curriculum studies as an educational field in its own right, this critical resource gives teachers the power to control the focus and direction their classes take by revealing the variety of benefits gained from rigorous curriculum planning. Stressing the importance of a teacher’s own involvement in the creation of curriculum, the guide shows teachers how to deal with the constant changes they face. For educators looking to contribute responsibly and dynamically to the content of their classes, this valuable and updated tool reveals new techniques that will empower educators and the significance behind involved curriculum development.
Keywords: Education / Curricula; Education / Professional Development

The role of video in teacher professional development - Marsh, Brian; Mitchell, Nick (Teacher Development, 2014)

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Teacher Professional Development around the World: The Gap between Evidence and Practice - Popova, Anna; Evans, David K.; Breeding, Mary E.; Arancibia, Violeta (World Bank, 2018)
Keywords: C:Low- and middle-income countries

The Influence of Teachers’ Professional Development Activities on the Factors Promoting ICT Integration in Primary Schools in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Sukhbaatar, Javzan; Takada, Jun-ichi (Education Sciences, 2019)
This paper examines the influences of professional development activities on important teacher-level factors that are important for the use of Information and Communication Technology (ICT) in education for primary school teachers in Mongolia. The study utilizes the survey data collected in 2012 (n = 826) and 2016 (n = 1161) to identify the changes in factors that are important to the use of ICT in education. The study result shows that six teacher level factors that are important for the ICT integration have been improved over time through professional development activities. These are professional competency in educational use of ICT, collaboration for ICT integration, benefits on use of ICT, autonomy to innovate, recognition as a professional, and skills and practices in educational use of ICT. This provides supporting evidence to educational practitioners for the implementation of effective professional development programs to promote ICT integration in education, especially in the developing country’s context.
Keywords: ICT in education; ___working_potential_duplicate; auto_merged; education policy; educational change; factors promoting ICT integration; teacher’s professional development

Professional Development Research: Consensus, Crossroads, and Challenges - Hill, Heather C.; Beisiegel, Mary; Jacob, Robin (Educational Researcher, 2013)
Commentaries regarding appropriate methods for researching professional development have been a frequent topic in recent issues of Educational Researcher as well as other venues. In this article, the authors extend this discussion by observing that randomized trials of specific professional development programs have not enhanced our knowledge of effective program characteristics, leaving practitioners without guidance with regard to best practices. In response, the authors propose that scholars should execute more rigorous comparisons of professional development designs at the initial stages of program development and use information derived from these studies to build a professional knowledge base. The authors illustrate with examples of both a proposed study and reviews of evidence on key questions in the literature.
Keywords: C:International

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Preliminary impacts of the “Learning to Read in a Healing Classroom” intervention on teacher well-being in the Democratic Republic of the Congo - Wolf, Sharon; Torrente, Catalina; Frisoli, Paul; Weisenhorn, Nina; Shivshanker, Anjuli; Annan, Jeannie; Aber, J. Lawrence (Teaching and Teacher Education, 2015)
This article examines the impacts of a partial year of implementation of Learning to Read in a Healing Classroom (LRHC), a curricular and social-emotional teacher professional development intervention in southeastern Democratic Republic of the Congo, on teacher professional well-being. Using a cluster-randomized control trial, this study assesses LRHC impacts on a sample of 346 teachers from 64 primary schools. We find statistically significant increases in job dissatisfaction for female teachers and increases in motivation for the least experienced teachers. Implications are discussed for the role of teacher professional development and well-being in improving education in low resource and conflict-affected contexts.
Keywords: Democratic Republic of the Congo; International education; Motivation; Teacher professional development

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

The Effect of Teacher Coaching on Instruction and Achievement: A Meta-Analysis of the Causal Effect - Kraft, Matthew A.; Blazar, David; Hogan, Dylan (Review of Educational Research, 2018)
Teacher coaching has emerged as a promising alternative to traditional models of professional development. We review the empirical literature on teacher coaching and conduct meta-analyses to estimate the mean effect of coaching programs on teachers’ instructional practice and students’ academic achievement. Combining results across 60 studies that employ causal research designs, we find pooled effect sizes of 0.49 standard deviations (SD) on instruction and 0.18 SD on achievement. Much of this evidence comes from literacy coaching programs for prekindergarten and elementary school teachers. Although these findings affirm the potential of coaching as a development tool, further analyses illustrate the challenges of taking coaching programs to scale while maintaining effectiveness. Average effects from effectiveness trials of larger programs are only a fraction of the effects found in efficacy trials of smaller programs. We conclude by discussing ways to address scale-up implementation challenges and providing guidance for future causal studies.
Keywords: C:High-income countries; C:United States; ___working_potential_duplicate; effect size; experimental design; meta-analysis; professional development; school/teacher effectiveness; teacher education/development

Technology use for teacher professional development in low- and middle-income countries: A systematic review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (Computers and Education Open, 2022)
Pre-service education and in-service teacher professional development (collectively termed teacher professional development or TPD here) can play a pivotal role in raising teaching quality and, therefore, learning outcomes for children and young people in low- and middle-income countries (LMICs). However, TPD opportunities in LMICs are limited, unsustained, and often not informed by recent research evidence, and outcomes are mixed. Educational technologies offer potential to enhance formally provided programmes and informal peer-learning forms of TPD. We present the first systematic review of the literature pertaining to technology-mediated TPD for educators of school-aged learners in LMICs, aiming to characterise appropriate and effective uses of technology along with specific constraints operating in those contexts. An in-depth synthesis of 170 studies was undertaken, considering macro-, meso- and micro-level factors during TPD design and implementation in the 40 LMICs represented. Volume of publications increased dramatically over the review period (2008–2020), indicating that the field is rapidly developing. Results largely showed benefits for teachers, but evidence for sustainability, cost-effectiveness or tangible impacts on classroom practice and student outcomes was thin. Promising, locally-contextualised forms of technology-mediated TPD included virtual coaching, social messaging, blended learning, video-stimulated reflection, and use of subject-specific software/applications. We report on the variable effectiveness of programmes and limited attention to marginalised groups. To maximise effectiveness of technology-enhanced TPD, the role of facilitators or expert peers is paramount – yet often glossed over – and the interpersonal dimension of teacher learning must be maintained. Recommendations are made for researchers, policymakers, teachers and teacher educators.
Keywords: ICT; Teacher professional development; e-learning; low- and middle-income countries (LMICs); pedagogy; peer learning; teacher training; technology

From Emergency Remote Teaching to Effective Online Learning: A Teacher Professional Development Case Study from Higher Education in India - Raina, Ashutosh; Rane, Archana; Ngeze, Lucian; Murthy, Sahana; Iyer, Sridhar (Global Perspectives on Educational Innovations for Emergency Situations, 2022)
This chapter describes the design and implementation of an educational solution to prepare teachers and instructors in India for various pedagogical and technological transitions during the pandemic. The goal was to move from an emergency remote teaching approach towards adopting effective online teaching strategies. This solution had to address the key challenge of remote professional development for the online medium while accounting for the diversity in the Indian educational context, taking into account varying needs of learners, teachers, institutions, geography, availability of technology, prior experience, and goals. The solution had two parts: i) a web-based repository for self-learning, consisting of research-based principles, pedagogical strategies and tools for effective design and development of online courses, and ii) synchronous interactive workshops to support instructors in practical implementation of the principles, strategies and tools to make domain specific instruction design decisions. Overall, emphasis was paid to learner engagement, diverse learner needs, peer learning, providing effective feedback and meaningful interaction. The resource repository and workshops guided instructors through making decisions and evaluating trade-offs in their context. This article also provides a brief analysis of the data collected from workshops on teachers’ preparedness at effective integration of technology, and the impact of the OTeach resource repository, which can found at Google Sites and has 25,000+ visitors so far. The article concludes with reflections and recommendations based on our experience.
Keywords: Effective online learning; Higher education; Research-based strategies; Teacher professional development

Professional Development on Digital Literacy and Transformative Teaching in a Low‐Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading research quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.
Keywords: 1‐Early childhood; 2‐Childhood; 3‐Early adolescence; 4‐Adolescence; 6‐Adult; Case Studies; Collaboration; Collaborative Learning; Computer literacy; Constructivism; Creative ability; Creativity; Critical Pedagogy; Culturally Responsive Pedagogy; Digital Literacies; Digital literacy; Digital/media literacy; Education & Educational Research; Educational technology; Gloablization and Literacy; Group work in education; Information literacy; Instructional strategies; methods and materials; Kenya; Literacies; Literacy; Literacy programs; Policy; Postcolonialism; Professional Development; Psychology; Psychology, Educational; Qualitative Research; Social Constructivism; Social Sciences; Socio‐cultural; Students; Study and teaching; Survey Research; Teacher attitudes; Teacher education; Teacher education; professional development; Teachers; Teaching; Teaching methods; Team learning approach in education; Transformative

Teacher design in teams as a professional development arrangement for developing technology integration knowledge and skills of science teachers in Tanzania - Kafyulilo, Ayoub; Fisser, Petra; Voogt, Joke (Education and Information Technologies, 2016)
This study investigated the impact of teacher design teams as a professional development arrangement for developing technology integration knowledge and skills among in-service science teachers. The study was conducted at a secondary school in Tanzania, where 12 in-service science teachers participated in a workshop about technology integration in science teaching and worked in design teams to prepare technology-enhanced biology, chemistry and physics lessons. Through collaboration in design teams, teachers were able to make science animations using PowerPoint and record videos to use in their teaching. The designed lessons were taught in the classroom and reflected upon thereafter by all teachers. In order to determine the change in teachers’ technology integration knowledge and skills, data were collected before and after the professional development arrangement by using questionnaire, interview and observation data. Focus group discussion and reflection questionnaire data were used to assess teachers’ experience of working in design teams at the end of the professional development arrangement. Findings showed an increase in teachers’ technology integration knowledge and skills between pre- and post-measurements. Collaboration in design teams had the potential for teachers to share knowledge, skills, experience and challenges related to technology-enhanced teaching.
Keywords: CAREER development; CHEMISTRY education; Computer Software; Computers--Information Science And Information Theory; Cooperation; EDUCATIONAL technology; ERIC, Current Index to Journals in Education (CIJE); Educational technology; Focus Groups; Foreign Countries; In-service science teachers; Interviews; Lesson design in teams; Lesson plans; MICROSOFT PowerPoint (Computer software); Observation; PROFESSIONAL education; Professional Development; Professional development; Questionnaires; Reflection; SCIENCE teachers; SECONDARY schools; Science Instruction; Science Teachers; Science teachers; Secondary Education; Secondary Schools; Secondary school teachers; TPACK; Tanzania; Teaching Methods; Teamwork; Technology Integration; Technology Uses in Education; Technology integration knowledge and skills; Visual Aids; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096124; __finaldtb

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Journal of Research on Educational Effectiveness, 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students’ literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children’s literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
Keywords: Africa; Classroom Observation Techniques; Dropout Rate; ERIC, Current Index to Journals in Education (CIJE); Early Childhood Education; Effect Size; Elementary Education; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 1; Grade 2; Handheld Devices; Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs; Intelligence Tests; Intervention; Interviews; Kenya; Literacy Education; Maximum Likelihood Statistics; Pretests Posttests; Primary Education; Program Effectiveness; Promising Interventions Are Great, but Are They Enough?; Questionnaires; RCT; Randomized Controlled Trials; Raven Progressive Matrices; Rural Schools; Statistical Analysis; Teacher Improvement; Teaching Methods; Telecommunications; What We Are Learning About Early Education in Sub-Saharan Africa; __:import:01; __:match:final; __:matched; __:study_id:2096051; ___working_potential_duplicate; __finaldtb; early grade reading; literacy instruction

Using video to support in-service teacher professional development: the state of the field, limitations and possibilities - Major, L; Watson, Steven (Technology Pedagogy and Education, 2017)
Keywords: C: International; ⛔ No DOI found

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC, Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

LGA Implementation Guide for Teacher Continuous Professional Development - Tanzania Institute of Education; Ministry of Education, Science & Technology; President’s Office — Regional and Local Governance (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology; _Source:Intuitive; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2425910; __finaldtb

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology

Scaling Online Teacher Professional Development in Bangladesh: Bangladeshi teachers’ experiences of the online training for the National Curriculum Revision - Afzal, Nimra; Atuly, Afsana Sadiq; Mazari, Haani; Clark-Wilson, Alison (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Leveraging Technology for Scaling Teacher Professional Development: Insights into Usage, Challenges, and Opportunities in Rural Tanzania - Swai, Calvin; Hennessy, Sara; Chachage, Kristeen; Koomar, Saalim; Adam, Taskeen; Mtenzi, Fredrick (EdTech Hub, 2026)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Promoting Student–Teacher Interactions: Exploring a Peer Coaching Model for Teachers in a Preschool Setting - Johnson, Stacy R.; Finlon, Kristy J.; Kobak, Roger; Izard, Carroll E. (Early Childhood Education Journal, 2017)
Peer coaching provides an attractive alternative to traditional professional development for promoting classroom quality in a sustainable, cost-effective manner by creating a collaborative teaching community. This exploratory study describes the development and evaluation of the Colleague Observation And CoacHing (COACH) program, a peer coaching program designed to increase teachers’ effectiveness in enhancing classroom quality in a preschool Head Start setting. The COACH program consists of a training workshop on coaching skills and student-teacher interactions, six peer coaching sessions, and three center meetings. Pre-post observations of emotional support, classroom organization, and instructional support using the Classroom Assessment Scoring System of twelve classrooms assigned to peer coaching were compared to twelve control classrooms at baseline and following the intervention. Findings provide preliminary support that the peer coaching program is perceived as acceptable and feasible by the participating preschool teachers and that it may strengthen student–teacher interactions. Further program refinement and evaluation with larger samples is needed to enhance student–teacher interactions and, ultimately, children’s adaptive development.
Keywords: Classroom quality; Head Start; Peer coaching; Professional development; Professional learning communities; Student–teacher interactions

Teacher professional development and curriculum: Enhancing teacher professionalism in Africa by Education International - Issuu - Sayed, Yusuf; Bulgrin, Eva (Education International Research, 2020)

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

Teacher professional development in sub-Saharan Africa: Equity and scale - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (Embedding Social Justice in Teacher Education and Development in Africa, 2021)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: Author:Haßler; Björn-CV-OECS; _yl:a; dode_eth-src-dode; dode_eth-trf2-dode

Examining sustained impacts of two teacher professional development programs on professional well-being and classroom practices - Wolf, Sharon; Peele, Morgan E. (Teaching and Teacher Education, 2019)
We examine second-year impacts of a 1-year pre-primary teacher training and coaching program, delivered with and without parental-awareness meetings, evaluated with a school-level randomized trial. Outcomes included teachers’ professional well-being and classroom practices. Most gains observed during the program year faded out. However, there were small sustained impacts on the implementation of training activities. Counteracting effects of the parental-awareness meetings were evident, with suggestive evidence that teachers in this treatment group displayed lower scores on one dimension of classroom qualitydSupporting Student Expressiondcompared to controls. Implications for professional development and educational quality are discussed.
Keywords: _proposed-for: Scoping review

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Assessing the scale-up of a technology-supported, government-led teacher professional development programme in Tanzania: Considering issues of equity, agency, and adaptation, Round 2 Policy Brief - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Developing Great Teaching: Lessons from the international reviews into effective professional development - Cordingley, Philippa; Higgins, Steve; Coe, Rob; Greany, Toby; Buckler, N.; Coles-Jordan, D.; Crisp, B.; Saunders, L. (Teacher Development Trust, 2015)
Keywords: C:England / International; ___working_potential_duplicate

Teachers’ professional development for ICT integration: Towards a reciprocal relationship between research and practice - Albion, Peter R.; Tondeur, Jo; Forkosh-Baruch, Alona; Peeraer, Jef (Education and Information Technologies, 2015)

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Pakistani Teacher-Educator Professional Learning through an International Blended Course - Impedovo, Maria Antonietta; Malik, Sufiana Khatoon (Open Praxis, 2019)
International teacher-educator learning supports a more complex vision of teacher professionalism for both developed and developing countries. The aim of this paper is the analysis of Pakistani teacher-educator professional learning after attending an international blended course, considering the impact of online and face-to-face participation and the main competencies involved in their professional learning. The blended learning course attended by the Pakistani Teacher-educators is part of an international project between Europe and Asia. The analysis is carried out using written traces in the online platform; 47 questionnaires at the end of the face-to-face training sessions in Pakistan and 10 deep-interviews with Pakistani educators; the written traces, open questions, and deep-interviews were qualitatively analyzed. Additionally, the educators' technological, pedagogical and instructional design and interpersonal and intercultural skills were also analysed. The paper considers how international learning could affect the professional learning of teacher-educators in Global South and the centrality of the design of innovative learning courses for today's environment of international globalization.
Keywords: Blended Learning; Cultural Awareness; Faculty Development; Foreign Countries; Instructional Design; International Education; Interpersonal Competence; Professionalism; Skill Development; Teacher Educator Education; Teacher Educators; Teaching Skills; Technological Literacy

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

The potential of research for professional development in isolated settings during the COVID-19 crisis and beyond - Trikoilis, Dionysios; Papanastasiou, Elena (Journal of Technology and Teacher Education, 2020)
The global COVID-19 pandemic has created the urgent need for quality online instruction throughout all levels of educa- tion. However, this pandemic has found teachers physically isolated within their homes, and unprepared for the challeng- ing tasks of teaching online. Many of the challenges faced by teachers due to this isolation, are similar to those faced by teachers in remote areas around the world. One such issue, is the lack of access to traditional professional development op- portunities, which is frequently the only type of professional development offered to teachers in many countries. Thus, many teachers lack guidance on how to resolve many online teaching challenges during this period. Therefore, this study examines the potential of utilizing educational research for assisting teachers through this trying period of COVID-19
Keywords: Access to Education; Communicable Diseases; Disease Control; Educational Research; Educational Technology; Faculty Development; Foreign Countries; Online Courses; Professional Isolation; Rural Areas; Technology Uses in Education; ⛔ No DOI found

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Improving impact studies of teachers’ professional development: toward better conceptualizations and measures - Desimone, Laura M. (Educational Researcher, 2009)

Professional Development and Teacher Change - Guskey, Thomas R. (Teachers and Teaching, 2002)
This article describes a model of teacher change originally presented nearly two decades ago (Guskey, 1986) that began my long and warm friendship with Michael Huberman. The model portrays the temporal sequence of events from professional development experiences to enduring change in teachers’ attitudes and perceptions. Research evidence supporting the model is summarized and the conditions under which change might be facilitated are described. The development and presentation of this model initiated a series of professional collaborations between Michael and myself, and led to the development of our co-edited book, Professional Development in Education: new paradigms and practices (Guskey & Huberman, 1995), which was named `Book of the Year’ by the National Staff Development Council in 1996.

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing TPACK in science and mathematics teacher education in Tanzania: A proof of concept study - Kafyulilo, Ayoub; Fisser, Petra (Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning, 2019)
Since 1997, the government of Tanzania has made several attempts at introducing technology into education. However, despite these efforts technology has not become integrated into educational practice. A main reason is that teachers do not embrace the use of technology in their teaching. This study was initiated to design, implement and evaluate a professional development arrangement aimed at promoting teachers’ use of technology in their teaching practice. The study started with a ‘proof of concept’ study. Based on experiences in Ghana and Kuwait, a professional development arrangement was developed that incorporated ‘learning technology by design’ to prepare pre-service science and math teachers for using technology in their teaching. The experiences from this study informed the design of a professional development arrangement for practicing science teachers. The iterative design, implementation and evaluation of the professional development arrangements will be presented and discussed.

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Blog-based professional development of English teachers in Mumbai: the potential of innovative practice under scrutiny - Khan, Atiya (Australasian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
Keywords: Action Research; Case Studies; Communities of Practice; Diaries; ERIC, Current Index to Journals in Education (CIJE); Electronic Publishing; English (Second Language); Faculty Development; Foreign Countries; India; Language Teachers; Participant Observation; Private Schools; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Semi Structured Interviews; Teacher Collaboration; Web Sites; Workshops; __:import:01; __:match:final; __:matched; __:study_id:2096053; __finaldtb

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Effective Teacher Professional Development - Darling-Hammond, Linda; Hyler, Maria E; Gardner, Madelyn (Learning Policy Institute, 2016)
Teacher professional learning is of increasing interest as one way to support the increasingly complex skills students need to succeed in the 21st century. However, many teacher professional development initiatives appear ineffective in supporting changes in teacher practices and student learning. To identify the features of effective professional development, this paper reviews 35 methodologically rigorous studies that have demonstrated a positive link between teacher professional development, teaching practices, and student outcomes. It identifies features of these approaches and offers descriptions of these models to inform those seeking to understand how to foster successful strategies.
Keywords: C:United States / International; ___working_potential_duplicate; important; ⛔ No DOI found

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Design-based online teacher professional development to introduce integration of STEM in Pakistan - Anwar, Tasneem (University of Minnesota, 2017)
In today's global society where innovations spread rapidly, the escalating focus on science, technology, engineering and mathematics (STEM) has quickly intensified in the United States, East Asia and much of Western Europe. Our ever-changing, increasingly global society faces many multidisciplinary problems, and many of the solutions require the integration of multiple science, technology, engineering, and mathematics (STEM) concepts. Thus, there is a critical need to explore the integration of STEM subjects in international education contexts. This dissertation study examined the exploration of integration of STEM in the unique context of Pakistan. This study used three-phase design-based methodological framework derived from McKenney and Reeves (2012) to explore the development of a STEM focused online teacher professional development (oTPD-STEM) and to identify the design features that facilitate teacher learning. The oTPD-STEM program was designed to facilitate eight Pakistani elementary school teachers' exploration of the new idea of STEM integration through both practical and theoretical considerations. This design-based study employed inductive analysis (Strauss and Corbin, 1998) to analyze multiple data sources of interviews, STEM perception responses, reflective learning team conversations, pre-post surveys and artifacts produced in oTPD-STEM. Findings of this study are presented as: (1) design-based decisions for oTPD-STEM, and (2) evolution in understanding of STEM by sharing participant teachers' STEM model for Pakistani context. This study advocates for the potential of school-wide oTPD for interdisciplinary collaboration through support for learner-centered practices. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: 0530:Teacher education; 0714:Science education; Attitude Measures; Community of practice; Design; Design-based research; ERIC, Resources in Education (RIE); Education; Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Interdisciplinary Approach; Interviews; Models; Online Courses; Online teacher professional development; Pakistan; Reflective practices; STEM Education; Science education; Stem integration; Student Centered Learning; Teacher Attitudes; Teacher education; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096054; __finaldtb

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

JiFUNzeni: a blended learning approach for sustainable teachers' professional development - Onguko, Brown Bully (Electronic Journal of e-Learning, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was fieldtested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers’ professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Cooperative learning; Course Content; Design; Disadvantaged Environment; Distance learning; Education--Computer Applications; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Internet; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training; __:import:01; __:match:final; __:matched; __:study_id:2096405; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Perspectives on technology, resources and learning: Productive classroom practices, effective teacher professional development - Haßler, Björn; Major, L.; Warwick, P.; Watson, S.; Hennessy, S.; Nicholl, B. (University of Cambridge, 2016)
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found

The Effect of Teachers' Professional Development in Video Technology on Mathematics and the English Language Learning of Preschoolers in a Rural Primary School in Pakistan. - Ikram, Hamid (2016)
The purpose of this mixed methods study was to examine the effect of teachers' professional development in video technology (PBS & Sesame Street videos) on mathematics and the English language learning among nursery students in the rural area of Pakistan where it was impossible for students to experience watching videos for learning purposes. This study showed teachers' motivation and frustration, before and after professional development, toward the use of video technology in the classroom. Also, this study showed the effect of learning videos assisted with games, coloring activities, and portfolios on student's English and mathematics' learning. The demographics of gender, socioeconomic status of the students, parents' education and occupation, learning resources at home for children, and the use of technology and media at home were contrasted to examine how they affect students learning of mathematics and English. The participants of the study were 80 nursery students and two English and math teachers in a rural primary school of Punjab province in Pakistan. Data were collected through a semi-structured interview protocol, biographical survey, and English and math tests. The demographic characteristics of the participants revealed that there were 55 percent female students and 45 percent male students ranging in age from 4 to 6 years. The demographics also revealed that 81 percent of the students belonged to households that had not more than $100 income per month. The findings supported that a majority of the students belonged to low socioeconomic status (SES), and fathers were the main source of household income. The findings showed that fathers' level of education was higher than that of the mothers' level of education. The effective delivery of the content with videos and students' engagement motivated teachers. The use of videos remarkably enhanced students' learning of math numbers and English alphabet in experimental classrooms. However, the lack of funds and technology training was the biggest frustration for teachers. The findings from this research contributed to the literature about teachers' professional development and use of learning media. The findings also identified the reasons behind teachers' frustration and motivation to bring technology in the classroom. Consequently, these study findings informed administrators, teachers, and parents to improve existing teaching and learning practices at early education level in Pakistan. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Educational Media; Educational Technology; Elementary School Teachers; English Language Learners; Foreign Countries; Mathematics Education; Mathematics Instruction; Mixed Methods Research; Pakistan; Preschool Children; Professional Development; Rural Schools; Second Language Learning; Semi Structured Interviews; Surveys; Technology Uses in Education; Video Technology

A COVID-19 intervention: Using digital escape rooms to provide professional development to alternative certification educators - Gómez, Miguel (Journal of Technology and Teacher Education, 2020)
Teachers, support staff, schools, and school districts have faced a multitude of challenges in adapting their known and familiar practices to the new realities and restrictions that have been put in place due to the outbreak of COVID-19. These challenges are daunting and difficult for many in our education system. Fortunately, a numerous amount of our educators are resilient, creative, and determined to overcome these new challenges. Using their prior experiences and wis- dom, these educators can adapt and change to our new edu- cational environment. However, one group of educators have faced these challenges without the benefit of educational ex- periences. Alternative certification teachers, in just their first year of teaching, with no prior educational experience, have been thrust into this new post COVID-19 landscape. Using a digital escape room as a model, the author provided these inexperienced educators with professional development in problem-based learning designed to help these teachers navi- gate this new educational landscape.
Keywords: Alternative Teacher Certification; Beginning Teachers; Communicable Diseases; Disease Control; Educational Technology; Elementary Secondary Education; Faculty Development; Problem Based Learning; Problem Solving; Puzzles; Technology Uses in Education; ⛔ No DOI found

Teachers’ experiences of ICT training in Nepal: how teachers in rural primary schools learn and make progress in their ability to use ICT in classrooms - Rana, Karna; Greenwood, Janinka; Henderson, Robyn (Technology, Pedagogy and Education, 2022)
This article reports on teachers’ experiences of ICT training in rural areas of Nepal. It discusses aspects of policy documents to help understand the Nepali educational context, before highlighting the challenges of establishing and maintaining infrastructure and professional learning opportunities across a country with challenging terrain and extreme environmental conditions. It then examines teachers’ perceptions in five rural primary schools about their experiences of training to use modern educational technologies in instructional activities. The findings indicate that none of the teachers received training in the use of ICT in their initial teacher education and that the Government has allowed non-governmental organisations to provide ICT infrastructure and training for rural schools and teachers. Although this is a small study, it offers insights into the gap between policy and practice and highlights the contextual challenges of Nepal’s attempts to operate on a global educational level as well as the challenges for teachers.
Keywords: ICT training; Nepal education; TPACK; rural education; teacher professional development

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Keywords: ___working_potential_duplicate

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Keywords: ___working_potential_duplicate

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Keywords: ___working_potential_duplicate

MOOCs as an alternative for teacher professional development: examining learner persistence in one Chinese MOOC - Wang, Qiong; Chen, Bodong; Fan, Yizhou; Zhang, Guogang (Peking University, 2018)
Massive Open Online Courses (MOOCs) have developed into a significant international movement, showing great promise in addressing equity, quality, and efficiency issues in global education. To date, many MOOCs have been developed specifically for teacher professional development (TPD). In this regard, an important empirical question remains to be addressed: How and to what extent can MOOCs support equity, quality, and efficiency in teacher professional development? To help fill this knowledge gap, this study, conducted from 2014 to 2016, focused on persistent teacher-learners in a TPD MOOC that was offered for seven consecutive rounds by the X-Learning Center of Peking University. The study found that more than 15% of the 105,383 teachers who enrolled in this MOOC were persistent teacher-learners, defined as learners who enrolled in multiple rounds. Data analysis showed that these persistent teacher-learners had diverse motivations for re-enrollment, including refreshing conceptual understanding, achieving higher scores, earning course certification, and discussing practical problems. The study also found that the persistent teacher-learners developed self-regulated learning skills in the course of multiple rounds of the MOOC and showed significantly higher learning achievement than one-time enrollees. Qualitative and quantitative analysis of both clicklog data and interview data revealed additional insights into the persistent teacher-learners’ learning within the MOOC and their real-world teaching practice beyond the MOOC. Overall, this study contributes to an improved understanding of the potential of MOOCs as an alternative TPD delivery mode in developing countries and sheds light on the future design of effective TPD through MOOCs.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425977; __finaldtb; tpdsysrev_potential_duplicate; ⛔ No DOI found

Theme 5: Teaching and Learning Materials (Professional Development Guide For Student Teachers) - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)

Localizing OER in Afghanistan: Developing a Multilingual Digital Library for Afghan Teachers - Oates, Lauryn; Hashimi, Jamshid (Open Praxis, 2016)
The Darakht-e Danesh (‘knowledge tree’) Online Library is the first open educational resource (OER) initiative in Afghanistan, established to enhance teacher subject-area knowledge, access and use of learning materials, and to foster more diverse teaching methodologies in order to improve learning outcomes in Afghan classrooms. This paper describes our experience developing this local language digital library, buildings its responsiveness to our audience of users as we progressed, customizing both the interface and the resources for Afghanistan’s education environment. We innovated methods to devise relevant local content, localized usability, developed different access models to reach different populations of users, integrated impact measurement, and opted to openly license material in the library’s collection. By making digital educational content open from the first introduction of digital repositories of learning objects in Afghan languages, we have an opportunity to establish the principle of openness and to promote open practices in teacher professional development in Afghanistan. The paper aims to share lessons on how OER can be customized for multilingual, resource-scarce contexts drawing from our experience to date in Afghanistan, and seeking to contribute to the literature on localization and multilingual OER.
Keywords: Afghanistan; OER; language; localization; open access; teacher education; teacher professional development; teaching and learning materials

Teacher professional development using mobile technologies in a large-scale project: lessons learned from Bangladesh - Shrestha, Prithvi (International Journal of Computer-Assisted Language Learning and Teaching (IJCALLT), 2012)

Factors in Mathematics Teachers’ Access to Digital Technologies and Their Professional Development Through Praxis in Marginalised Communities in Bangladesh - Kukulska-Hulme, Agnes; Power, Tom; Dawadi, Saraswati; Rahman, S M Hafizur; Parvin, Tauhida (Journal of Technology and Teacher Education, 2024)
The paper presents findings from a research study of 318 mathematics teachers’ experiences of access to, and use of, digital technology in their professional development in marginalised communities in ten districts across Bangladesh. The innovative two-cycle qualitative study design involved early career researchers collaborating with peer-researcher teachers who interviewed their peers about local teachers’ experiences. The interview data was analysed through the lens of Van Dijk’s model of digital access and use, addressing motivation, physical access, skills, and usage. The findings reveal that most rural teachers were able to overcome barriers to access and complete the online course using their mobile phones, but the aim of making mathematics learning more active and joyful was only realised among the minority of teachers who had a supportive school environment. Promoting and supporting opportunities for praxis in schools is essential if technology enhanced professional development is to lead to improvements in teaching and learning. The findings have important implications for practice and at policy level to rethink access to professional development through ‘mobile first’ technologies and support for praxis in schools, in marginalised communities in Bangladesh and elsewhere.

Reforming teacher education in Nigeria: Laying a foundation for the future - Barnes, Adrienne E.; Boyle, Helen; Zuilkowski, Stephanie Simmons; Bello, Zaliha Nasiruddeen (Teaching and Teacher Education, 2019)
Teacher educators in Nigeria receive limited professional development, particularly regarding the instruction of early grade reading skills. As part of the USAID-funded Northern Education Initiative Plus project, Florida State University faculty provided intensive teacher educator professional development to staff at four Teacher Education Institutions in northern Nigeria. Positive impacts on teacher educator knowledge, skills, and attitudes were observed related to content and pedagogical knowledge, use of participatory teaching and learning activities in the college classrooms, and improvement in student teacher engagement and learning. Continued success of the implemented model for training will be dependent upon national adoption and scale up.

Teacher peer support in social network sites - Kelly, Nick; Antonio, Amy (Teaching and Teacher Education, 2016)
This paper describes the types of support that teachers are accessing through the Social Network Site (SNS) ‘Facebook’. It describes six ways in which teachers support one another within online groups. It presents evidence from a study of a large, open group of teachers online over a twelve week period, repeated with multiple groups a year later over a one week period. The findings suggest that large open groups in SNSs can be a useful source of pragmatic advice for teachers but that these groups are rarely a place for reflection on or feedback about teaching practice.
Keywords: Beginning teacher; Facebook; Natural language processing; Online professional development; Social network; Teacher; Teacher education

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, Hannah; Hennessy, Sara; Pimmer, Christoph (Research Papers in Education, 2022)

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)

Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Characteristics of effective teacher professional development: what we know, what we don’t, how we can find out - Sims, Sam; Fletcher-Wood, Harry (2018)
Several influential reviews and one meta-review have converged on the position that teacher professional development (PD) is more effective when it is: sustained, collaborative, subject-specific, draws on external expertise, has buy-in from teachers and is practice-based. This consensus view has now been incorporated in government policy and official guidance in several countries. Despite this, several recent PD programmes incorporating these characteristics have failed to have any detectable impact on pupil attainment. This article reviews the evidence underpinning the consensus, arguing that the reviews on which it based are methodologically flawed because they employ inappropriate exclusion criteria and depend on an invalid inference method. The consensus view is therefore likely to be inaccurate. Researchers would make more progress on identifying characteristics of effective professional development by looking for alignment between evidence from basic research on human skill acquisition and features of rigorously-evaluated PD interventions.
Keywords: C:International; CitedIn:OER4Schools-HHH3-A; ⛔ No DOI found

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, Hannah; Hennessy, Sara; Pimmer, Christoph (Research Papers in Education, 2022)

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Pakistani Teachers' Professional Learning Experiences: Comparing Face-to-Face versus Online Learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language--ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language--ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language--ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

A short guide on the use of technology in learning: Perspectives and toolkit for discussion - Haßler, Björn; Major, L; Warwick, P; Watson, S; Hennessy, S; Nichol, B (University of Cambridge, 2016)
Perspectives on Technology, Resources and Learning - Productive Classroom Practices, Effective Teacher Professional Development
Keywords: _not_EdTechHub; dode_eth-src-dode; dode_eth-trf2-dode

A Design Approach to Mathematics Teacher Educator Development in East Africa - Golding, Jennie; Batiibwe, Marjorie Sarah K. (Journal of Research and Advances in Mathematics Education, 2021)
Mathematical functioning in sub-Saharan Africa remains persistently weak in global terms. This limits the flourishing of young people and communities in the region. Moreover, affordable, effective ways to address the issue are not well established. This paper analyses outcomes from a blended learning 'Mathematical Thinking and IT' course, iteratively adapted for East African primary mathematics teacher educators. The course adopted theoretical approaches derived from the mathematics, teacher and technology education literatures. It aimed to address the problem of low mathematical functioning by equipping participants for their own work, and also for supporting local collaborative teacher development workshops. The reported study asked, 'What are the affordances and constraints of the adapted course and the available technology for mathematics teacher educator development in this context?' A variety of qualitative tools were used to track the course's impact on the ten mathematics teacher educator participants over six months, as they attempted to transfer course learning to their home professional context. The analysis adopted an ethnographic lens. Outcomes suggested participants with a broad mathematical and pedagogical capacity for change, including critical levels of reflection, made significant progress in their technological, mathematical and mathematics pedagogical expertise. However, teacher educators without such a threshold capacity appeared not able to re-envision practice. Free subject-specific software was appreciated by all participants, but not yet reliably accessible in these teacher educators' institutional contexts. The reported study evidences the potential for affordable, sustainable, development of many mathematics teacher educators in this context, but further research is needed. Similar courses should take account of local technological and education constraints.
Keywords: Blended Learning; Distance Education; Elementary School Mathematics; Foreign Countries; Mathematics Teachers; Pedagogical Content Knowledge; Professional Development; Program Effectiveness; Teacher Collaboration; Teacher Educators; Technological Literacy; Technology Integration

Learning to argue: A study of four schools and their attempt to develop the use of argumentation as a common instructional practice and its impact on students - Osborne, Jonathan; Simon, Shirley; Christodoulou, Andri; Howell-Richardson, Christina; Richardson, Katherine (Journal of Research in Science Teaching, 2013)
This article reports the outcomes of a project in which teachers' sought to develop their ability to use instructional practices associated with argumentation in the teaching of science—in particular, the use of more dialogic approach based on small group work and the consideration of ideas, evidence, and argument. The project worked with four secondary school science departments over 2 years with the aim of developing a more dialogic approach to the teaching of science as a common instructional practice within the school. To achieve this goal, two lead teachers in each school worked to improve the use of argumentation as an instructional practice by embedding activities in the school science curriculum and to develop their colleague's expertise across the curriculum for 11- to 16-year-old students. This research sought to identify: (a) whether such an approach using minimal support and professional development could lead to measurable difference in student outcomes, and (b) what changes in teachers' practice were achieved (reported elsewhere). To assess the effects on student learning and engagement, data were collected of students' conceptual understanding, reasoning, and attitudes toward science from both the experimental schools and a comparison sample using a set of standard instruments. Results show that few significant changes were found in students compared to the comparison sample. In this article, we report the findings and discuss what we argue are salient implications for teacher professional development and teacher learning. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50:315–347, 2013
Keywords: argumentation; dialogic teaching; epistemic learning; student engagement; teacher professional development

Teachers’ virtual communities of practice: A strong response in times of crisis or just another Fad? - Ghamrawi, Norma (Education and Information Technologies, 2022)
The purpose of this study was to investigate the perceived effectiveness of a virtual community of practice (vCoP) designed to support knowledge and expertise sharing between K-12 teachers during Covid-19 pandemic. Besides, it aimed at exploring the potential of such vCoPs in delivering effective professional development, in general, and during crisis in particular. The vCoP was developed by the researcher herself as part of a consultancy to the UNESCO. The sample included 696 participants who were members of the vCoP. The research methodology adopted was mixed methods. Quantitative data was collected through surveying; and qualitative data was collected through 8 focus group interviews each involving 6 participants. Statistical analysis was used to analyze survey data, while interviews data was analyzed using theme-based analysis. Findings showed that participants viewed vCoPs as effective tools for e-professional development in general and during crisis in particular. Facilitators and blockers confronting vCoP nourishment are presented and discussed. Discussions and conclusions are offered at the end of the study.
Keywords: Covid-19 pandemic; Crisis education; Professional development; Remote education; Social networking; Virtual communities of practice

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
Keywords: _yl:i; dode_eth-src-dode; dode_eth-trf2-dode

Effectiveness of Multimodal Microlearning for In-Service Teacher Training - Allela, Melisa Achoko; Ogange, Betty Obura; Junaid, Muhammad Ibn; Charles, Prince Brainard (Journal of Learning for Development, 2020)
To meet the growing demand for continuing professional development of practising teachers, the integrated in-service teacher training (INSET) programme aims at making permanent improvements on the quality of teaching and learning for Junior Secondary School (JSS) Teachers in Sierra Leone. Within this context, a toolkit for School-Based Teacher Development was created and microlearning identified as an ideal mode to deliver the toolkit content. In this paper, we present the design considerations that informed this decision as well as challenges and lessons learned from the first implementation of the INSET project for junior secondary school teachers in Sierra Leone. A multimodal approach was considered and implemented to mitigate Internet access challenges and to expand learning opportunities. These include a mobile app version of the Toolkit, offline access to microlearning resources on the TeacherFutures platform via the Moodle mobile app, a mobile app version of one INSET module, an e-portfolio to be used by participants in sharing their learnings as demonstrated and practised during a face-to-face roll-out seminar, and finally, WhatsApp groups in which different schools engaged in discussions based on the questions on the Toolkit. Preliminary findings indicate a strong preference among participants for the use of WhatsApp as the main channel of communication within the communities of practice; and very limited use of the main e-learning Moodle platform and e-Portfolio. This necessitates a need to critically evaluate the effectiveness of the design of a multimodal approach for delivering microlearning content. From this, we seek to establish a set of design considerations, capacity building and technical support issues derived from analysis of data emerging from the ongoing project rollout. This will inform future integration of Microlearning resources in the teacher training project.
Keywords: Barriers; Communities of Practice; Electronic Learning; Foreign Countries; Inservice Teacher Education; Integrated Learning Systems; Internet; Multimedia Materials; Portfolios (Background Materials); Professional Continuing Education; Professional Development; Program Effectiveness; Secondary School Teachers; Social Media; Synchronous Communication; Teacher Collaboration; Teacher Competencies; Workshops

A model of practice for improving autism knowledge in teachers of mainstream students on the autism spectrum in Australia - Bruck, Susan; Robinson, Ainslie; Gallagher, Emma (Australasian Journal of Special and Inclusive Education, 2021)
Australian mainstream school teachers report a severe shortage of accessible autism-focused resources, strategies, and professional development (PD). This 2-part mixed methods study investigated the effect of using a web-based model of practice (MoP) for PD. The MoP contains evidence-based, autism-specific educational practices and resources designed for mainstream teachers of students on the autism spectrum. The aim was to examine teacher responses to using the MoP and the impact of the mode of delivery. In Part 1, 3 PD delivery conditions for using the MoP were trialled (8 weeks): face-to-face support, online support, or web-based access to detailed resources only. Support was provided by expert autism educators. Teachers (N = 15) reported that the MoP was an accessible, comprehensive, and practical support for educational decision-making, and that support encouraged implementation of the MoP practices. Part 2 trialled a hybrid PD model in 6 regional schools. Limited face-to-face and online support plus access to the MoP was trialled. Interview data indicated that a hybrid model can be an effective method of providing immediate support for teachers.
Keywords: autism; confidence; educators; knowledge; professional development; teachers

Characteristics of effective teacher education in low- and middle-income countries: an overview (HDR10A) - Haßler, Björn; McBurnie, Chris; Allier-Gagneur, Zoe; Damani, Kalifa (EdTech Hub, 2020)
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher learning and policy intention: selected findings from an evaluation of a large‐scale programme of professional development in the Republic of Ireland - Murchan, Damian; Loxley, Andrew; Johnston, Keith (European Journal of Teacher Education, 2009)

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC, Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
Keywords: ⛔ No DOI found

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics--Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

Reflective teacher supervision through videos of classroom teaching (supervisión colaborativa docente a través de clases grabadas en video) - Kaneko-Marques, Sandra Mari (PROFILE: Issues in Teachers' Professional Development, 2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.
Keywords: Brazil; Cooperation; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); English Teachers; Foreign Countries; Higher Education; Observation; Postsecondary Education; Preservice Teacher Education; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Self Evaluation (Individuals); Student Teachers; Teacher Supervision; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2098468; __finaldtb

Community-Based Teacher Training: Transformation of Sustainable Teacher Empowerment Strategy in Indonesia - Mardapi, Djemari; Herawan, Tutut (Journal of Teacher Education for Sustainability, 2019)
Teacher empowerment is a central issue in relation to the efforts to improve the quality of education. However, teacher empowerment will remain an abstract idea if its implementation is not supported by an appropriate strategy. The demands for a quality education will be unreciprocated if teachers do not have the opportunity to empower themselves. This research aims to investigate the teacher empowerment strategy in Indonesia, which has been conducted by employing a community-based teacher training program. This study has highlighted several research questions: What is meant by community-based training program? Why is the training program needed? Who is the target of the training program? What model has been used to implement the training? What are the results of the training that has been executed? This research was conducted from November 2018 to January 2019. The research data were collected by means of documentation studies and interviews. The data analysis was carried out quantitatively and qualitatively, where the quantitative analysis was processed based on the document study data, meanwhile the qualitative analysis was performed based on the interview data. The research results showed that community-based teacher training was transformation of teacher development strategy as a follow-up on teachers’ competency test in Indonesia. The community-based teacher training succeeded in increasing the professionalism of teachers in Indonesia, particularly in terms of implementing their pedagogical and professional competencies. The training is also successful in motivating the teachers to engage themselves in continuous learning efforts through building strong teachers’ network and working collaboratively with colleagues. Quantitatively, training was proven to increase the average of teacher competency by 23.97 (on a scale of 100). The research results are expected to provide information about the best practice in teacher coaching that is conducted massively in a national scope based on the local community so that a lifelong learning culture for teachers is established to support the development of sustainable education.

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Reexamining technology’s role in learner-centered professional development - Polly, Drew; Hannafin, Michael J. (Educational Technology Research and Development, 2010)
The American Psychological Association’s Learner-Centered Principles provide empirically-based approaches to improving teaching and learning. However, in order to facilitate learner-centered, technology-rich instruction to K-12 students, teachers must be afforded opportunities to develop key understandings and skills, rarely evident in most professional development programs. In this paper, we synthesize empirically-based studies and recommendations for teacher learning and propose a learner-centered professional development (LCPD) framework to guide both professional development and empirical work on teacher learning. We describe LCPD components, discuss ways that technology can support LCPD, and highlight implications for research and practice.

Reexamining technology’s role in learner-centered professional development - Polly, Drew; Hannafin, Michael J. (Educational Technology Research and Development, 2010)
The American Psychological Association’s Learner-Centered Principles provide empirically-based approaches to improving teaching and learning. However, in order to facilitate learner-centered, technology-rich instruction to K-12 students, teachers must be afforded opportunities to develop key understandings and skills, rarely evident in most professional development programs. In this paper, we synthesize empirically-based studies and recommendations for teacher learning and propose a learner-centered professional development (LCPD) framework to guide both professional development and empirical work on teacher learning. We describe LCPD components, discuss ways that technology can support LCPD, and highlight implications for research and practice.

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
Keywords: ⛔ No DOI found

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Blog-based professional development of English teachers in Mumbai: The potential of innovative practice under scrutiny | Australasian Journal of Educational Technology - Khan, Atiya (Australian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Evaluating Teachers' Professional Development For ICT Use: Towards Innovative Classroom Practices - Agyei, D. D (International Journal of Education, 2015)
This paper describes an evaluation study designed to investigate the impact of an ICT-Instructional digital innovation in teaching Mathematics, English and Integrated Science subjects from the teacher capacity building professional development programme to classroom implementation at senior high school levels in Ghana. Interviews and survey data were used for data collection following a week professional development programme on the instructional digital learning training. The study demonstrated that the teachers increased in ICT proficiencies but this was limited to their own professional development and not so much of classroom implementation of ICT which results when transfer of learning takes place from training to practice. The study reported that teachers faced a complex mix of factors that when combined, contributed to challenges in transferring the ideas gained in the training programme to the classroom situation. It was evident from the findings that more systematic efforts are needed at the school levels and at the level of stakeholders who implement in-service teachers’ professional development programmes to move the goal of transforming teaching and learning through ICT-based innovations. Based on the outcomes, the study discussed recommendations to help smoothen the transition from teacher professional development programmes to actual classroom implementations in Ghanaian senior high schools and such similar contexts.
Keywords: ⛔ No DOI found

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

MEWAKA in Tanzania: Emerging findings on tech-supported teacher professional development - Koomar, Saalim; Massam, Winston; Anthony, Gervace; Mrope, Winifrida; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fredrick; Proctor, Jamie; Komba, Aneth; Mwakabungu, Fika; Barretto, Johnpaul; Barretto, Saalim Koomar, Winston Massam, Gervace Anthony, Winifrida Mrope, Taskeen Adam, Sara Hennessy, Fredrick Mtenzi, Jamie Proctor, Aneth Komba, Fika Mwakabungu and Johnpaul (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teachers’ Continuous Professional Development (TCPD)) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The programme is decentralised, with teacher learning based in schools and focused on semi-structured Communities of Learning (CoLs). CoLs are spaces where teachers can gather weekly to discuss and reflect on issues most relevant to their schools as well as learn and improve their pedagogical skills. Peer facilitators help teachers to collaboratively solve problems, learn new approaches to improve their practice, and generally create a culture of reflection and school improvement.

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Teachers' professional development in a challenging educational context -- a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found

Curated Tools for Teacher Continuous Professional Development - Hub, EdTech (EdTech Hub)
EdTech Hub has created curated lists of teacher professional development (TPD) tools along with evidenced-based advice on how to effectively use them. Because, of course, it’s not only which tool you choose, but how you use it that will determine whether it will lead to better teaching and learning.

Usage patterns of Teachers' Continuous Professional Development Learning Management System in Primary schools in Tanzania - Mtebe, Joel S.; Kondoro, Aron; Maro, Salome; Simmons, Hannah; Komba, Aneth (East African Journal of Science, Technology and Innovation, 2025)
This study aims to understand how primary school teachers in Tanzania use the Teachers' Continuous Professional Development (TCPD) Learning Management System (LMS). There is currently limited information about how effectively the LMS supports teachers' ongoing professional development through structured Communities of Learning. Without clear data on usage patterns, it is difficult to identify barriers to access and measure the success of the LMS in improving teacher training. To fill this knowledge gap, the study examined LMS log data over a period of one year (July 2023–June 2024). It specifically looked at how often teachers logged into the system, which modules they enrolled in, what resources they accessed, and from which regions they logged in. The analysis revealed that usage was highest during key academic periods, such as the start of school terms and exam preparations, suggesting that teachers engage more actively with the LMS during these critical times. Teachers predominantly accessed practical modules, including those related to curriculum guidelines and foundational education training. This indicates that teachers prefer resources directly applicable to their teaching tasks. There was also a noticeable increase in LMS access through mobile devices, highlighting the growing importance of mobile technology in teacher professional development. However, significant challenges remain, such as limited internet connectivity and varying digital literacy levels, particularly in rural areas. These issues create obstacles for equitable LMS usage. The study recommends targeted efforts to enhance internet infrastructure, provide digital literacy training, and improve mobile accessibility. Addressing these challenges can increase the effectiveness of the TCPD LMS, ensuring equitable and widespread professional development support for primary school teachers across Tanzania.

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

ICT use in the teaching of mathematics: Implications for professional development of pre-service teachers in Ghana - Agyei, Douglas; Voogt, Joke (Education and Information Technologies, 2011)
Included in the contemporary mathematics curricula in Ghana is the expectation that mathematics teachers will integrate technology in their teaching. However, importance has not been placed on preparing teachers to use ICT in their instruction. This paper reports on a study conducted to explore the feasibility of ICT use in mathematics teaching at senior high school levels in Ghana. Interviews and survey data were used for data collection. Preliminary results showed that mathematics teachers in Ghana do not integrate ICT in their mathematics instruction. Among the major perceived barriers identified were: Lack of knowledge about ways to integrate ICT in lesson and Lack of training opportunities for ICT integration knowledge acquisition. To overcome some of these barriers, opportunities of a professional development arrangement for pre-service mathematics teachers were explored. Findings from the study revealed specific features of a professional development scenario that matters for ICT integration in mathematics teaching in the context of Ghana. KeywordsICT use–Professional development–Computer competencies–Mathematics education–Computer attitude–Ghana

Live virtual sessions with toddlers and preschoolers amid COVID-19: Implications for early childhood teacher education - Szente, Judit (Journal of Technology and Teacher Education, 2020)
This paper shares reflections on over 50 live Zoom instructional lessons with toddlers and preschoolers amid the first three weeks of school closures due to COVID-19 in the State of Florida. Reflections resulted in three themes such as 1) Implementing digital sessions with young children; 2) Establishing and maintaining home-based child engagement through technology; and 3) Ensuring family involvement/engagement through technology. Implications and recommendations are provided for early childhood teacher education programs and in-service professional development opportunities to ensure that teachers are better prepared for teaching and learning in an online environment.
Keywords: Access to Computers; Communicable Diseases; Disease Control; Distance Education; Early Childhood Teachers; Educational Technology; Faculty Development; Family Involvement; Online Courses; Preschool Children; Preservice Teacher Education; Technological Literacy; Toddlers; ⛔ No DOI found

An experimental study of the performance of prospective teachers of flipped classroom and non-flipped classroom - Minaz, Maksal; Tabassum, Rabia; Idris, Muhammad (Pakistan Journal of Education, 2017)
Video-recording of lectures and creating of podcasts for playback on the computer and other portable devices which accommodate the new formats of self-developed learning are identified as flipped classroom. The study was focused on the objective to Investigate performance of prospective teachers of flipped classroom and non-flipped classroom with respect to flipped classroom strategy. Therefore, null hypotheses were formulated; there is no significant difference between the mean scores of flipped classroom and non-flipped classroom of prospective teachers before and after treatment; Pretest posttest equivalent group experimental research design was taken for the study. A paired random sampling technique was employed to select the sample on the basis of pretest scores from the subjects.. Experimental group was named flipped classroom and control group was named non-flipped classroom. Treatment of flipped classroom strategy provided to the flipped classroom and the non-flipped classroom was thought through lecture demonstration method. Posttest was administered to collect data from both groups without delay after treatment of six academic weeks. Results of the study illustrated that there was significant difference between the performance of flipped and non-flipped classrooms prospective teachers. It was recommended that flipped classroom may be an integral part of curriculum of professional development courses in Pakistan.
Keywords: Education; Educational technology; Learning; Pedagogy; Podcasts; Professional development; Teacher attitudes; __:import:01; __:match:final; __:matched; __:study_id:2096864; __finaldtb; ⛔ No DOI found

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Understanding language teachers' practice with educational technology: A case from China - Li, Li (System, 2014)
This article explores how eight secondary school teachers integrated educational technology into English language teaching in Beijing, China and considers their views of the factors influencing technology use. Analysing data from classroom recordings and follow-up interviews, this study revealed that PowerPoint was the most frequently used technological application in the classroom, while the internet and other technological tools were also used by the teachers. They employed educational technology for different pedagogical purposes, including addressing professional needs in improving teaching, designing materials and conducting professional development. Teachers also claimed that they used technology to address learners' needs, such as improving engagement, enhancing language acquisition, facilitating understanding and establishing a context for language use. The study identified four important factors in influencing teachers' use of technology, including sociocultural contexts, teachers' beliefs, access to resources, and technology competence and confidence. This study suggests that a critical reflective approach is useful in assisting teachers to understand their needs and pedagogical beliefs concerning technology use. Ongoing professional development is also valuable in promoting teachers' technology competence and confidence, thereby improving the use of technology in their teaching.
Keywords: Case study; China; Socio-cultural context; Teachers' perceptions; Technology use

Transforming Teacher Education and Learning in Ghana: The Impact of a Continuous Professional Development on Physics Teaching at the Colleges of Education - Coffie, Isaac Sonful (International journal of Research and Scientific Innovation, 2019)
The colleges of education in Ghana have been involved in a continuous professional development for over four years with support of Transforming Teacher Education and Learning (T-TEL). The main purpose of this research was to assess the perceived impact of the continuous professional programme on physics teaching at the colleges of education. Descriptive cross sectional survey was used for the study. An online survey was conducted which was completed by 85 physics tutors. The survey data were analysed using means and standard deviations and ANOVA. It was found that the professional development is perceived by the physics tutors to have great impact on their teaching practice. It was also found out that there was no statistical significant difference in the perceived impact of the professional development based on tutors’ experience. It was concluded that if the student teachers who are being trained by these tutors will learn these ideas from their tutors and practice them, teaching at the basic schools will be more interactive, students-centered and gender responsive.
Keywords: ⛔ No DOI found

Supporting teachers in taking up productive talk moves: The long road to professional learning at scale - O’Connor, Catherine; Michaels, Sarah (International Journal of Educational Research, 2019)
In this paper we describe our early, qualitative work on “teacher talk moves” such as revoicing, situated within the urban classrooms of highly skilled teachers, including their role in the work of managing multiple constraints while maintaining productive inclusivity. We then describe our attempts to discern the impact of these talk tools on student achievement in multiple classrooms, using both post-hoc controls and in vivo studies. We move on to the challenges present in disseminating this work in professional development settings; our approach includes framing talk tools as rational responses to actual classroom challenges. Finally we describe current efforts to disseminate cyber-enabled PD in science education K-12, including a central focus on academically productive talk.

Teacher Coaching: What We Know - Evans, David (World Bank Blogs - Development Impact, 2017)
“Teacher coaching has emerged as a promising alternative to traditional models of professional development.” In Kraft, Blazar, and Hogan’s newly updated review “The Effect of Teacher Coaching on Instruction and Achievement: A Meta-Analysis of the Causal Evidence, ” they highlight that reviews of the literature on teacher professional development (i.e., ...

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

Experimental Impacts of a Teacher Professional Development Program in Chile on Preschool Classroom Quality and Child Outcomes - Yoshikawa, Hirokazu; Snow, Catherine; Barata, Clara; Gomez, Celia; Leyva, Diana; Treviño, Ernesto; Weiland, Christina; Moreno, Lorenzo (Developmental Psychology, 2015)
We assessed impacts on classroom quality and on 5 child language and behavioral outcomes of a 2-year teacher professional-development program for publicly funded prekindergarten and kindergarten in Chile. This cluster-randomized trial included 64 schools (child N 1,876). The program incorporated workshops and in-classroom coaching. We found moderate to large positive impacts on observed emotional and instructional support as well as classroom organization in prekindergarten classrooms after 1 year of the program. After 2 years of the program, moderate positive impacts were observed on emotional support and classroom organization. No significant program impacts on child outcomes were detected at posttest (1 marginal effect, an increase in a composite of self-regulation and low problem behaviors, was observed). Professional development for preschool teachers in Chile can improve classroom quality. More intensive curricular approaches are needed for these improvements to translate into effects on children.

The Effects of Micro-Reflective Teaching Practices on the Professional Skill Development of Pre-Service Physics Teachers - Batman, Demet; Saka, Ahmet Zeki (The Turkish Online Journal of Educational Technology, 2021)
The aim of this study is to find out the effects of micro-reflective teaching practices on the professional skill development of pre-service physics teachers. It was planned as an experimental study with one group pretestposttest and supported by the case study method. The data were collected by using professional skill scale, observation form and reflective diaries. The sample of the study composed of 13 (6 female, 7 male) pre-service teachers were studying in a Physics Teaching Program in an education faculty in north-eastern Turkey. Each preservice teacher implemented 5 micro-reflective teaching practice within the scope of the research. These practices were recorded by the camera. At the end of each practice pre-service teachers watched themselves and wrote their reflective diaries. The data obtained from the scales and the observation form were analyzed by using the Wilcoxon Signed Rank Test, and the data acquired from the reflective diaries were examined based on interpretive analysis. The findings based on the data obtained from the professional skill scale, observation forms and the reflective diaries indicate that micro-reflective teaching practices help improve pre-service physics teachers’ basic professional skills; subject matter mastery, planning, communication, classroom management, and evaluation.
Keywords: ⛔ No DOI found

The Potential of Mobile Phones to Transform Teacher Professional Development to Build Sustainable Educational Futures in Bangladesh - Walsh, Christopher S; Woodward, Clare; Solly, Mike; Shrestha, Prithvi (Asian Association of Open Universities Journal, 2015)
Futures thinking is used by governments to consider long-term strategic approaches and develop policies and practices that are potentially resilient to future uncertainty. English in Action (EIA), arguably the world's largest English language teacher professional development (TPD) project, used futures thinking to author possible, probable and preferable future scenarios to solve the project's greatest technological challenge: how to deliver audio-visual TPD materials and hundreds of classroom audio resources to 75,000 teachers by 2017. Authoring future scenarios and engaging in possibility thinking (PT) provided us with a taxonomy of question-posing and question-responding that assisted the project team in being creative. This process informed the successful pilot testing of a mobile-phone-based technology kit to deliver TPD resources within an open distance learning (ODL) platform. Taking the risk and having the foresight to trial mobile phones in remote rural areas with teachers and students led to unforeseen innovation. As a result, EIA is currently using a mobile-phone-based technology kit with 12,500 teachers to improve the English language proficiency of 700,000 students. As the project scales up in its third and final phase, we are using the new technology kit — known as the 'trainer in your pocket' — to foster a 'quiet revolution' in the provision of professional development for teachers at scale to an additional 67,500 teachers and nearly 10 million students.

The Role of Educational Technology in Upgrading Teacher Education in Pakistan - Abbasi, M. Hashim; Millar, Alex C. (1996)
This paper outlines a joint Asian Bank/Pakistan Ministry of Education project designed to upgrade the state of teacher education and to improve the quality, status, and professional self-esteem of Pakistan's teachers. The main strategies identified by the Project for priority attention include: structural changes through the creation of four new types of teacher education institutions in each of the provinces; development of the main teacher education pre- and in-service courses; increased output and improved standard of teachers at all levels; development and implementation of a Total Educational Technology Plan; and upgrading and strengthening of existing Government Colleges for Elementary Teachers and Government Colleges of Education. Educational technology is a key element designed to assist in achieving the Project's major goals and objectives. Needs analysis produced recommendations geared for: target population; new teacher education courses; allocation of electronic media; teacher/principal attitudes towards the equipment and software; potential sources of software; availability of ancillary funding; specialist educational technology assistance for teachers; developing a profession of educational technology interested people; storage and access for hardware and software; roles of Mobile Training Units; and overseas lessons on the application of educational technology. (AEF)
Keywords: Educational Change; Educational Development; Educational Finance; Educational Strategies; Educational Technology; Elementary Secondary Education; Foreign Countries; Higher Education; Needs Assessment; Professional Development; Program Improvement; Resource Allocation; Schools of Education; Teacher Attitudes; Teacher Education; Technology Planning

The Teachers’ Portal as a tool for teachers’ professional development in Bangladesh: Facilitating nationwide networking and digital multimedia content for 40,000 schools - Hansson, H; Sultana, S; Sarwar, A; Ahmed, F; Uddin, R; Saha, P; Islam, G; Islam, M (International Journal of Education and Development using ICT, 2018)
The Teachers’ Portal (teachers.gov.bd) is an online platform for Bangladeshi teachers designed to store and retrieve digital educational contents of different subjects useful for classroom teaching and students’ learning. The portal also facilitates professional networking among teachers across the country. This study aims to find out the benefits of using this Portal and associated challenges from teachers’ perspective. Following a mixed methods research approach Teachers, head teachers, teacher educators from primary, secondary, madrasa and vocational educational institutions and specialists on teachers’ Portal (N=410) were interviewed and consulted for the study. Telephone interviews, online surveys, Key Informant Interviews (KII), Focused Group Discussions (FGD), Face-to-Face interviews, and large consultative workshops were used to collect data. The results suggest that teachers are motivated to use the Portal as its contents stimulate students’ creativity and encourage students’ active participation in classrooms learning. Besides, it empowers teachers in a number of ways. However, internet connectivity, slow Internet speed, power failure, technical issues, high cost of Internet and unavailability of equipment are found as major challenges. In short, the Teachers’ Portal is a key driver for changing Bangladeshi education and preparing the young generation with quality education.
Keywords: ⛔ No DOI found

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

A Practice-Based Approach to Foreign Language Teacher Preparation: A Cross-Continental Collaboration - Barahona, Malba; Davin, Kristin J. (Profile Issues in Teachers` Professional Development, 2021)

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The effectiveness of technology-supported teacher professional learning communities in emergency settings - El-Serafy, Yomna; Adam, Taskeen; Hassler, Björn (Future-Proofing Teacher Education, 2022)
Professional learning communities are becoming increasingly popular in emergency settings due to their potential to be a sustainable, scalable, and grounded modality for teacher professional development. In settings where formal structures of professional development are absent or disjointed, professional learning communities respond to the urgent need to develop quality teachers. Moreover, where teachers have experienced significant trauma, such communities offer highly valued spaces for socioemotional support. Increasingly, practitioners in emergency settings are moving towards using technology to support professional learning communities, either by facilitating them entirely online or by using technology for specific components. This chapter builds upon existing literature on the use of technology in professional learning communities, both globally and in emergency settings in particular. The chapter correlates such literature to findings from primary research that involved 280 practitioners of professional learning communities in emergency settings. We demonstrate the potential for technology to significantly increase access to and effectiveness of professional learning communities in emergency settings, while laying out significant barriers to implementation.

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn; Open Development & Education (OpenDevEd, 2022)

Can new modes of digital learning help resolve the teacher crisis in sub-Saharan Africa? - Moon, Bob; Villet, Charmaine (Journal of Learning for Development, 2017)
Sub-Saharan Africa, more than any other part of the world, is experiencing a crisis in finding sufficiently qualified teachers to meet the needs of expanding school systems. The professional development support provided to serving teachers is also inadequate in most countries. The most recent data on learner outcomes has revealed a worrying picture of significant under-achievement across the region. This paper argues that the teacher education and training structures of the last century will never be able to meet urgent contemporary needs. Given population growth, especially among the young, large-scale expansion of the teaching force and the associated teacher education systems will be the norm through to the middle years of the century and beyond. In this context the paper argues for a significant policy shift to expand quality teacher education and professional support at scale through a more school-based and digitally supported network model of provision. Examples of current digital programmes within the region are considered as well as the new technologies that are emerging with relevance to teacher education. The paper suggests a three-phase process through which national governments might move in making the necessary changes in policy and practice.
Keywords: Africa; Computer Uses in Education; ERIC, Current Index to Journals in Education (CIJE); Educational Change; Educational Policy; Electronic Learning; Faculty Development; Foreign Countries; Higher Education; Inservice Teacher Education; Online Courses; Postsecondary Education; Preservice Teacher Education; Resource Units; Teacher Shortage; ⛔ No DOI found

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, H.; Hennessy, S.; Pimmer, C. (Research Papers in Education, 2022)
This study reports on the adaptation and outcomes of a teacher professional development (TPD) programme in a rural Zimbabwean secondary school. The programme incorporated Open Educational Resources (OER), specifically OER4school materials, that were provided via tablet computers for teachers and students. A mixed-methods case study was employed to explore teachers’ perceptions, knowledge, experiences of interactive learning and teaching in relation to this TPD, as well as their perceptions and experiences of the role and value of using technology to support student learning. Video data from structured lesson observations were triangulated with teacher post-lesson interviews and thematically coded. The interviews indicated that all teachers demonstrated a change in mindset and a clear understanding of interactive teaching methods. However, the structured observations revealed that only half of the teachers were using these interactive methods. Teachers also emphasised the value of OER and tablet technologies in improving lesson planning and making classroom learning more authentic. The use of technology, as both a TPD medium and as a classroom tool, showed potential to enhance the quality of TPD and teacher quality. Yet more specific teacher development to support the interactive use of technology within the classroom would be beneficial.

The evaluation of "technological pedagogical content knowledge based argumentation practices" training for science teachers - Çoban, Gül Ünal; Akpinar, Ercan; Baran, Bahar; Saglam, Merve Kocagül; Özcan, Erkan; Kahyaoglu, Yasemin (Egitim ve Bilim, 2016)
In science education, creating learning environments supported with technology and students' use of theory-evidence coordination when expressing their ideas is emphasized regarding the development of students' scientific reasoning, critical thinking, decision making skills, and etc. In this process, great responsibilities are fallen to teachers as planner and designer of a learning environment. In this study, it is aimed to assess the training which aims the development of science teachers' technological pedagogical content knowledge (TPACK) through argumentation practices. In this context; this study evaluated the science teachers' argumentation skills, self-efficacy perceptions towards TPACK and the teachers' views about the training. 37 science teachers working at different cities in Turkey participated in the one group pre-test post-test experimental training study, which was lasted 54 hours during a week. The training is composed of both hand and minds on argumentation practices based on TPACK. The participants joined different activities such as collaborative group works, drama, modeling, thematic games, art activities, problem-based learning, field trips, observation and workshops. In the study, Argumentation Test, TPACK Self-Efficacy Belief Scale were used as data collection tools. At the end of the training written views of science teachers towards activities were taken. In the light of the findings, this training was effective on the participants' self-efficacy levels towards technological pedagogical content knowledge. Moreover, this training resulted in a positive change in the participants' views about how a statement could be accepted as an argument. However, the increase in scores of argumentation skills was not significant. Additionally almost all of the participants stated that they found the activities useful and can use in their classes. By considering these results, some suggestions were given.
Keywords: Argumentation; Education; Professional development; Science teachers; Technological pedagogical content knowledge; __:import:01; __:match:final; __:matched; __:study_id:2097466; __finaldtb

ICT use in science and mathematics teacher education in Tanzania: Developing Technological Pedagogical Content Knowledge - Kafyulilo, Ayoub; Fisser, Petra; Pieters, Jules; Voogt, Joke (Australasian Journal of Educational Technology, 2015)
Currently, teacher education colleges in Tanzania are being equipped with computers to prepare teachers who can integrate technology in teaching. Despite these efforts, teachers are not embracing the use of technology in their teaching. This study adopted Technological Pedagogical Content Knowledge (TPACK) as a framework for describing the knowledge and skills that pre-service teachers need to develop in order to effectively integrate technology in science and mathematics teaching. Pre-service teachers (N=22) participated in microteaching, hands-on training, collaborative lesson design in design teams, and reflection with peers. Pre- and post-assessment results of the pre-service teachers’ perceived knowledge and skills of integrating technology in teaching, showed significant changes in technology-related components of TPACK. We conclude that opportunities for pre-service teachers to participate in professional development programs that involve lesson design, teaching, evaluation and re-design, can be effective for the development of the knowledge and skills of integrating technology in science and mathematics teaching.
Keywords: TPACK; lesson design; microteaching; reflection; technology integration; training

Experimental Impacts of the “Quality Preschool for Ghana” Interventions on Teacher Professional Well-being, Classroom Quality, and Children’s School Readiness - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward (Journal of Research on Educational Effectiveness, 2019)
We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children’s readiness during one school year. This cluster-randomized trial included 240 schools (teachers N ¼ 444; children N ¼ 3,345, Mage ¼ 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children’s school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.
Keywords: Ghana; ___working_potential_duplicate; classroom quality; early childhood education; kindergarten; school readiness; teacher training and coaching

Transforming teacher quality in the Global South: using capabilities and causality to re-examine teacher performance - Tao, Sharon (Palgrave Macmillan, 2016)
A common story of teachers from the Global South portrays them as deficient, unreliable and unprofessional. However, this book uses an innovative Capability Approach/Critical Realist lens to reveal the causal links between teachers' constrained capabilities and their 'criticised' behaviours and offer nuanced, creative strategies for improvements.
Keywords: Education / Comparative; Education / Educational Policy & Reform / General; Education / General; Education / Professional Development; Education / Teacher Training & Certification; Social Science / Anthropology / Cultural & Social; Social Science / Developing & Emerging Countries; Social Science / General; Social Science / Sociology / General

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Approaches to teacher professional development in low-to-middle-income countries - Power, Tom (Sustainable English language teacher development at scale: Lessons from Bangladesh, 2019)
This chapter begins by situating discussion of approaches to teacher development (TD) in the context of the grand societal challenge of Education for All (UNESCO 2014), as written into the earlier Millennium Development Goals (MDGs) and now Sustainable Development Goal (SDG) 4:‘to ensure inclusive and equitable quality education for all.’ This goal cannot be met without addressing the stark and urgent need for greater numbers of teachers who are adequately equipped with the knowledge and skills to enable effective student learning. Drawing upon personal experiences of work with teachers in LMICs over nearly two decades, the chapter argues against ‘blaming teachers’ for poor student learning outcomes, and advocates instead the development of better understandings of the often challenging contexts in which teachers practise. The chapter then critically examines common approaches to TD that have often failed adequately to equip teachers for classroom practice, outlining a broadly supported agenda for reform. Recent literature has begun to identify certain characteristics of TD programmes that are increasingly associated with effective student outcomes, in what may be an emerging consensus. These characteristics are briefly outlined, before the chapter closes with lessons learned from English in Action. EIA has both contributed to and benefitted from this emerging evidence base and Chapter 5 illustrates how the implementation of EIA exemplifies such characteristics through a cohesive programme design.
Keywords: Important; Read

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers' experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies-enhanced supported open distance learning programme of professional development in English-language teaching. This paper presents evidence arising from semi-structured interviews carried out with teachers from a pre-pilot study for the English in Action project. The teachers participating in this study reflect upon six months' experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text-book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods). (Contains 1 table and 1 figure.)
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted language instruction; COMPUTERS in education; CONTINUING education; Computer Assisted Instruction; DISTANCE education; Developing Nations; Digital audio players; Distance Education; Distance learning; ENGLISH language -- Study & teaching -- Foreign speakers; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Development; Educational Technology; Educational technology; Elementary Secondary Education; English (Second Language); English in Action support model; English language; Foreign Countries; Handheld Devices; Higher Education; Inservice Teacher Education; Interviews; LANGUAGE teachers; Language instruction; Multimedia Instruction; OPEN learning; Open Universities; Pilot Projects; Postsecondary Education; Professional development; Program Descriptions; Program Development; Program Effectiveness; Protocol Materials; SECONDARY education; Second Language Instruction; Secondary Education; Secondary School Teachers; Studies; TEACHER development; TEACHERS -- Attitudes; TELEMATICS; Teacher Attitudes; Teachers; Technology Integration; United Kingdom; Video Technology; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2098161; ___working_potential_duplicate; __finaldtb; auto_merged; mobile learning; mobile technology; technology intervention

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, Lee Kean, (PhD); Swanto, Suyansah, (PhD); Lajium, Denis Andrew, (PhD) (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Keywords: Collaboration; Distance learning; English as a second language--ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

An exploration of agency in the localisation of open educational resources for teacher development - Wolfenden, Freda; Adinolfi, Lina (Learning, Media and Technology, 2019)
This study examines the practice of adaptation and translation (localisation) of Open Educational Resources (OER). It employs a sociocultural perspective to focus on the experiences of practitioners (localisers) who undertook the localisation of a suite of 125 OER created as part of a teacher professional development programme in India. This localisation process generated eight unique versions of the OER in five languages. Drawing on project reports, practitioner interviews and analysis of the adapted OER, the study explores how localisers created meaning for the task, the situational and linguistic factors that influenced and mediated their decisions to adapt the materials – or not – and the skills and experiences that emerged through the process. Although the findings revealed that changes to the materials were limited, suggesting that enacting localisation is more difficult than perhaps suggested by OER proponents, the analysis indicated forms of localisers’ emerging professional agency through this endeavour.
Keywords: India; Open educational resources (OER); __:import:01; __:match:final; __:matched; __:study_id:2457357; __finaldtb; localisation; professional agency

An EdTech reading list from the Helpdesk team: Autumn 2020 (EdTech Hub, 2020)
In this blog post, we summarise six new publications from the Helpdesk and what we have learned about monitoring and evaluation, curriculum reform, blended learning, and teacher education. As Covid-19 continues to affect learning around the world, our Helpdesk is seeing a shift in the requests we receive. Earlier, the bulk of requests were linked to short-term Covid responses. Now,…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The Teachers’ Digital Literacy: Determining Digital Divide in Public Basic Schools in Ghana - Quaicoe, James Sunney; Pata, Kai (Springer International Publishing, 2015)
This study explored the role of the teacher’s digital literacy (TDL) among other schools’ digital culture (SDC) components in determining Digital Divide (DD) among Ghana’s basic schools. A paper-based survey was conducted with teachers and head-teachers from randomly sampled 17 basic schools in various locations in Ghana. The questionnaire was adopted from the Institute for Capacity Building – UNESCO and EU rubrics for measuring ICT in education; and explored nine Digital Culture components including TDL. Data were analysed using K-means Clustering, Correlation analysis, Discriminant analysis, and Independent-samples T-test. The schools were clustered based on SDC components into two DD groups; the principal influencing factors were Teachers’ digital literacy and ICT related policy documents. The school groups particularly differed based on whether they not only had the digital literacy competences, but also applied these competences in their teaching and professional development in schools. We argue that in spite of training for TDL, many schools still lack other digital culture components, and this may hinder them in applying ICT in their schools.
Keywords: Digital divide; Digital literacy; Information literacy; School digital culture; Teacher digital literacy

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.

Reflective Teacher Supervision Through Videos of Classroom Teaching - Kaneko-Marques, Sandra Mari (PROFILE Issues in Teachers' Professional Development, 2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.

Collaboration and self-regulation in teachers’ professional development - Butler, Deborah L; Lauscher, Helen Novak; Jarvis-Selinger, Sandra; Beckingham, Beverly (Teaching and Teacher Education, 2004)

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Lessons on technology-enabled teacher professional development from Bangladesh’s national curriculum reform - Ahmed, Shakil; Mazari, Haani; Hassan, Mehdi; Azam, Shafiul; Sidotam, Annie; Clarke-Wilson, Alison; Sarwar, Md Afzal Hossain (EdTech Hub, 2023)
This blog presents Part 1 of our lessons on tech-enabled professional development. We shall be bringing you more insights and evidence in Part 2. Stay tuned!

Integrating problem-based learning with ICT for developing trainee teachers' content knowledge and teaching skill - Karami, Mehdi; Karami, Zohreh; Attaran, Mohammad (International Journal of Education and Development using Information and Communication Technology, 2013)
Professional teachers can guarantee the progress and the promotion of society because fostering the development of next generation is up to them and depends on their professional knowledge which has two kinds of sources; content knowledge and teaching skill. The aim of the present research was studying the effect of integrating problem-based learning with Information and Communications Technology (ICT) on developing content knowledge and teaching skill of trainee teachers. The research design was a quasi-experimental one, and the participants were elementary education trainee teachers of Shahid Bahonar teacher training center of Hamadan, Iran. Two groups were given tests of theory and practice on teaching mathematical concepts at elementary school, and then a multivariate analysis of variance (MANOVA) was conducted to compare the pretest-posttest scores. There was a significant difference, in both multivariate and univariate analyses, in scores. The findings suggest that trainee teachers who integrate problembased learning with ICT in solving a problem may develop more professional content knowledge and teaching skill than those who merely employ ICT.
Keywords: _THEME: Curriculum and resources; __:import:01; __:match:final; __:matched; __:study_id:2096422; __finaldtb; ⛔ No DOI found

Action research and the transfer of reflective approaches to in-service education and training (INSET) for unqualified and underqualified primary teachers in Namibia - O’Sullivan, Margo C. (Teaching and Teacher Education, 2002)
The literature on training approaches for both pre-service and in-service teacher training has been dominated since the 1980s by reﬂective approaches. This has undoubtedly inﬂuenced the relatively recent introduction of reﬂective approaches in developing countries. This article explores efforts, within an action research study of a 3-year (1995–1997) In-service Education and Training (INSET) programme, to implement reﬂective approaches in the training of unqualiﬁed and underqualiﬁed primary teachers in Namibia. The study raises ‘transfer’ questions concerning the appropriateness of reﬂective approaches, as conceptualised in western contexts, for these teachers. It led to the adaptation of these approaches and ultimately the development of an approach termed the ‘structured reﬂection’ approach, which was within the professional capability of the teachers to implement at the time of the study. Action research was used to develop this approach. r 2002 Elsevier Science Ltd. All rights reserved.

Understanding the relationship between teachers’ pedagogical beliefs and technology use in education: a systematic review of qualitative evidence - Tondeur, Jo; van Braak, Johan; Ertmer, Peggy A.; Ottenbreit-Leftwich, Anne (Educational Technology Research and Development, 2017)
This review was designed to further our understanding of the link between teachers’ pedagogical beliefs and their educational uses of technology. The synthesis of qualitative ﬁndings integrates the available evidence about this relationship with the ultimate goal being to facilitate the integration of technology in education. A meta-aggregative approach was utilized to analyze the results of the 14 selected studies. The ﬁndings are reported in terms of ﬁve synthesis statements, describing (1) the bi-directional relationship between pedagogical beliefs and technology use, (2) teachers’ beliefs as perceived barriers, (3) the association between speciﬁc beliefs with types of technology use, (4) the role of beliefs in professional development, and (5) the importance of the school context. By interpreting the results of the review, recommendations are provided for practitioners, policy makers, and researchers focusing on pre- and in-service teacher technology training.

Provision of continuing professional development by resource centres in selected high schools of the Copperbelt province - Mwale, Kelly Kezala (2011)
The purpose of the study was to investigate the effectiveness of resource centres in providing Continuing Professional Development to high school teachers in the Copperbelt Province.Major concerns have been expressed by various stakeholders that not enough has been done in enhancing and strengthening the concept of Continuing Professional Development among high school teachers. The Teacher Resource Centres that are supposed to be custodians of In-service Training of Teachers(INSET) now Continuing Professional Development (CPD) are perceived not to have done enough. The establishment of Teacher Resource Centres throughout the country was meant to help upgrade the skills and competencies of teachers at both basic and high school levels. These Continuing Professional Development activities that should be on-going include School Programme of In-service for the Term (SPRINT), Demonstrate, Observe, Discuss and Implement (DODIS) and Subject Meeting at the Resource Centre (SMARC).A purposive sample of 8 teacher resource centres and 12 high schools giving the study a number of 84 respondents was selected.Data were collected by way of questionnaires, interviews and Focus Group Discussions. The major informants were the following: Headteachers, Heads of Department, Teachers and Resource Centre Coordinators.The results of the study revealed that Teacher Resource Centres were not effectively providing Continuing Professional Development (CPD) activities among high school teachers. The findings further revealed that the Continuing Professional Development activities such as School Programme of In-service for the Term (SPRINT), Demonstrate, Observe, Discuss and Implement (DODIS) and Subject Meeting at the Resource Centre (SMARC) were almost non-existent in high schools despite clustering them with basic schools.Generally, the findings indicated lack of commitment both by the coordinators in Resource Centres and school administrators. Further revelations by the study indicate that little or no effort has been given to school - based workshops, seminars, professional meetings and conferences. Additionally,constant monitoring of CPD activities was not given prominence by Resource Centre Coordinators hence the glaring lapses in the actual implementation of Continuing Professional Development programmes.Further analysis of both quantitative and qualitative data revealed that there was lack of significant advocacy and sensitisation on the difference between Continuing Professional Development activities and In-service Teacher Education tenable at colleges of education and universities. In view of the research findings, recommendations were made. Teacher Resource Centres ought to enhance advocacy and sensitisation of Continuing Professional Development activities. Pedagogical competences and skills would be strengthened at high school level if Teacher Resource Centres played their expected role of providing Continuing Professional Development to teachers. The study has also shown that school administrators did not apportion equal weight to Continuing Professional Development as they did with sporting activities. There is need to give both areas equal attention.

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Turkish pre-service teachers' reflective practices in teaching English to young learners - Güngör, Muzeyyen Nazli (Australian Journal of Teacher Education, 2016)
The course "Teaching English to Young Learners" is the first stage where pre-service teachers are introduced to a child's world, developmental characteristics, needs, interests as well as teaching and learning techniques for these learners in English language teaching pre-service teacher education programmes in Turkey. This action research study identifies the gap that pre-service teachers experience between the theoretical considerations and realities of teaching, and the problems they face in this course. It provides the opportunity for monitoring and evaluating themselves in a pre-service teacher education programme in Turkey. Hence, this piece of research aims to promote reflective practice at the preservice level in teaching English to young learners through video recorded microteaching sessions, reflective journals, and lesson plans of pre-service teachers. The study reports on the results by highlighting the contribution of these reflective tools to pre-service teachers' professional development, self- and peer- reflections and the preparedness to teach English to young learners. Finally, insights and recommendations concerning teacher educators and pre-service programmes are offered to promote reflective practice and make methodology courses more beneficial before pre-service teachers embark on their practicum experience.
Keywords: Action Research; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Elementary Education; English (Second Language); Foreign Countries; Higher Education; Journal Writing; Language Teachers; Lesson Plans; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Qualitative Research; Reflection; Reflective Teaching; Second Language Instruction; Teaching Methods; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096127; __finaldtb

The effects of continuing professional development (CPD) through SPRINT on teacher classroom practices and student learning outcomes - Mazala, Chileya Mbasilu (2011)
This study looked at the effects of Continuing Professional Development (CPD) through School Programmes for In -Service for the Term (SPRINT) on teacher classroom practices and student learning outcomes. The purpose of the study was to find out if SPRINT had any effect on teacher classroom practice and student learning outcomes. The target population was all Ndola high schools. The sample consisted of 196 respondents that is, five head teachers, five deputy heads, fifteen heads of department, five School In- Service Providers (SIP), five Zone INSET Providers (ZIP) and twelve teachers from each of the five schools and one Resource Centre Coordinator. The sample also included one hundred grade twelve pupils, twenty randomly picked from each of the five schools Purposive sampling was used to select the schools, head teachers, heads of department, INSET providers and the subject coordinator. Teachers and pupils were selected using simple random sampling. Questionnaires, observations, interviews, Focus Group Discussions and documentary evidence were the research instruments used to gather information. A review of relevant literature and its implication for CPD was undertaken to provide interrogation framework for this study. Guskey's five levels of evaluation were used to structure the framework Data were analyzed by identifying and categorizing significant themes relevant to research objectives. The data were presented in form of tables, percentages,graphs and charts. Qualitative data from interviews were coded and emerging themes grouped into categories The themes and categories of initial data were compared with those of subsequent interviews. Categories were then regrouped to get the most significant categories and themes.The findings from this study indicated that teachers at all career stages expressed the desire to take part in Continuing Professional Development through SPRINT.Research findings also showed that SPRINT activities did impact on teacher classroom practice basing on the twelve observable skills recommended by The Ministry of Education. The findings from this study further revealed that SPRINT had an impact on student learning outcomes as shown by the average scores of students whose teachers took part in CPD and those whose teachers did not.Average scores for the latter were lower than the former category of students.The findings further revealed that although there was evidence of the effect of CPD through SPRINT on teacher classroom practices and student learning outcomes, this programme was hindered by weak organisational support.The results of the study showed that teachers were not enthusiastic about continuing with the CPD programme as it lacked adequate funding and support from both local administrators and the Ministry of Education. Teachers were not involved in identifying training needs and as such did not feel they were the owners of CPD Teachers also felt that this kind of CPD did not help in career progression as the credit system was not effective. At organizational level, this study found that policies and guidelines on how to organize and manage CPD were lacking.CPD leaders also did not have adequate training to prepare them for their roles. Because of this lack of training, CPD leaders could not carry out assessment of the effects of CPD through SPRINT on teacher classroom practices and student learning outcomes.On the basis of these findings, it is recommended that teachers should be in charge of their own CPD and be involved in needs assessment .Secondly, CPD leaders should be properly trained for their role and they should have clear job specifications. In addition, adequate funding for the programme should be made available by both the Government and the School Administration. The Ministry of Education also needs to formulate national policies and guidelines on management and evaluation of SPRINT .A standardized accreditation system which would enable teachers to experience career progression through SPRINT should also be put in place. Lastly, CPD through SPRINT should be made research based with teachers having access to INTERNET and good library facilities.

Enhancing the teaching skills of the multi-grade teachers through lesson study - Thephavongsa, Souphanh (International Journal of Learning, Teaching and Educational Research, 2018)
Teaching in the multi-grade class is more difficult than mono-grade for teachers, however, multi-grade teaching was defined as the best strategy to achieving access to Education For All (EFA) of children especially those from rural areas. Teachers have been working diligently but unmethodical in their classroom. This study aimed to improve and enhance the teachers' professional skills which they have been facing in the classroom through the Lesson study and discuss why most of the teachers did not like to prepare and/or develop lesson plans. There were 100 participants who teach in the multi-grade schools in the Salavan district. The results represented that pre-test scores and post-test scores from two of training groups were significantly different and found that most of teachers do not usually prepare lesson plans. The research findings also determined that a Lesson study can be beneficial to enhance the development the teachers' professional skills.https://doi.org/10.26803/ijlter.17.4.5
Keywords: Development a lesson plan; Lesson study approach; Multi-grade class; Multi-grade teaching; Training Multi-grade teachers; ⛔ No INSPIRE recid found

Exploring formative assessment - Brookhart, Susan M. (ASCD, 2009)
About the PLC series: Welcome to an adventure! If you are a teacher who is interested in developing a professional learning community to develop your classroom repertoire and increase your students achievement and motivation, you are in for a treat. A professional learning community (PLC) is a small group of teachers or administrators that meets regularly and works between meetings to accomplish shared goals. PLCs are vehicles for connecting teacher practice and student outcomes, improving both. About this book: Exploring Formative Assessment is your guide to creating a PLC to help further your understanding of how to use formative assessment in your school or classroom. You ll find everything you need to organize and run your PLC, including agendas, handouts, worksheets, and the background reading for each of seven sessions. You ll get the chance to try out new techniques and to collaborate with your colleagues as you deepen your understanding of formative assessment.
Keywords: Education / Professional Development; Education / Testing & Measurement

Investigating effects of using digital video in teacher training in Cambodia - Lok, Leandra; Schellings, Gonny; Brouwer, Niels; Den Brok, Perry (Journal of Technology and Teacher Education, 2018)
While research has shown that video can be an effective tool in the professional learning of teachers in industrialized countries, it is unknown whether this is also true for other countries with distinctive cultural, political, and historical contexts, such as Cambodia. This paper presents results from a study which examined the effectiveness of using video to introduce student-centered teaching to teachers in Cambodia. The training consisted of collaboratively watching and discussing videos of teaching practices. A 2x2 design was used, varying group conditions (team versus pair) and relevance of the material (model video versus action video). The findings indicated that although it was not possible to determine if there had been changes in teacher behavior, using video had led to an increase in teachers' perceived knowledge of student-centered teaching, especially for the team and the model video conditions.
Keywords: Active Learning; Behavior Change; Cambodia; Cultural Context; ERIC, Current Index to Journals in Education (CIJE); Education--Computer Applications; Faculty Development; Foreign Countries; Instructional Effectiveness; Knowledge Base for Teaching; Learning; Mixed Methods Research; Questionnaires; Student Centered Learning; Studies; Teacher Attitudes; Teacher Behavior; Teacher education; Teachers; Teaching; Teaching Methods; Training; Video; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2095890; __finaldtb; ⛔ No DOI found

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction--CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics--Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

New modes of teacher pre-service training and professional support - Anamuah-Mensah, Jophus; Banks, Frank; Moon, Bob; Wolfenden, Freda (Teacher education and the challenge of development: a global analysis, 2012)
Keywords: Economic development -- Effect of education on -- Developing countries.; Teachers -- Training of -- Developing countries.; Teaching -- Developing countries.

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Form and Substance in Mathematics and Science Professional Development - Kennedy, Mary M (National Institute for Science Education, University of Wisconsin-Madison, 1999)
This document reviews studies of professional development for teachers to examine benefits to students in science and mathematics education. A major finding from this review was that programs that focused on teaching classroom management strategies or attaining knowledge of how students learn specific school subject matter provided later benefits to students. The more successful professional development programs were not simply courses in mathematics or science, but instead were about what to teach and how students learn that subject matter.

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Keywords: ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Keywords: _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Education management; _THEME: Open systems; _THEME: School management; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2426091; ___working_potential_duplicate; __finaldtb

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Keywords: ___working_potential_duplicate

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Can Virtual Replace In-person Coaching? Experimental Evidence on Teacher Professional Development and Student Learning in South Africa - Cilliers, J; Fleischz, B; Kotzex, J; Mohohlwanex, N; Taylor, S; Thulare, T (2020)
We experimentally compare on-site with virtual coaching of South African teachers. After three years, on-site coaching improved students’ English oral language and reading proﬁciency by 0.31 and 0.13 SD, respectively. Virtual coaching improved English oral language proﬁciency (0.12 SD), had no impact on English reading proﬁciency, and an unintended negative eﬀect on home language literacy. Classroom observations show that on-site coaching improved teaching practice and that virtual coaching led to larger crowding-out of home language teaching time. Implementation and survey data suggest that the use of technology did not preclude eﬀectiveness, but rather that in-person contact enabled more accountability and support.
Keywords: Important; Read; ⛔ No DOI found

Online teacher professional development in ICT integration in Tanzania: An experience report - Ngeze, Lucian Vumilia; Iyer, Sridhar (2019)
Integration of Information and Communication Technology (ICT) in teaching and learning in schools has been hindered by many barriers, including lack of in-service teacher training, teacher beliefs and lack of infrastructure. In the effort to solve the challenge of teacher training in Tanzania, few in-service teachers, based on different parameters, are selected to participate in the face to face ICT training at the specified training centre. Scaling of such teacher training initiatives has been challenging over time. To reach more school teachers, we developed a ten-day online course, run over Moodle. A total of 134 teachers from all the regions of Tanzania registered and participated. Topics were developed based on the preference of the in-service teachers. Online surveys were used to collect qualitative and quantitative data before and after the course. Teachers were active during the duration of the course and many of them applied the skills in their schools by improving their teaching strategies, use of technology tools and sharing experiences with other teachers in their schools.
Keywords: ⛔ No DOI found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Demonstrating a situated learning approach for in-service teacher education in rural India: The Quality Education Programme in Rajasthan - Saigal, Anju (Teaching and Teacher Education, 2012)
Recent educational policy in India has repositioned elementary school teachers as active, reflective practitioners, not just ‘deliverers’ of syllabus material. This article examines innovations in teacher support in Rajasthan's government schools through the ‘Quality Education Program.’ Drawing on qualitative research of collaborative learning processes, the paper discusses two support strategies used by the program: professional dialogic interactions and modeling of pedagogic strategies, which paralleled introductory or developmental phases within a ‘collaborative apprenticeship model’ of teacher professional development. In doing so, the paper outlines the potential of situated, collaborative approaches for Indian in-service teacher education and education development reform, more broadly.

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Bridging between research and practice: Supporting professional development through collaborative studies of classroom teaching with technology - Hennessy, Sara (Sense Publishers, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory – through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators’ complementary professional knowledge bases. Teachers’ voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially. The book reflects upon the power of lesson video review and details how the co-inquirers negotiated “intermediate theory” – bridging educational theory and specific settings – framed in mutually accessible language and embodied in interactive multimedia resources for teacher development. These include video clips, analytic commentary from multiple perspectives, lesson materials, plus optional prompts for reflection and critique – not models of “best practice”. The resources make pedagogy explicit and vividly illustrate the book’s ideas, offering theory-informed yet practical tools designed with and for practitioners. Hennessy and colleagues have tested a model of ongoing, teacher-led development and innovation, professional dialogue and classroom trialing stimulated by discussing selected multimedia resources. The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes – springboarding teachers’ further critique and professional learning. “I cannot recommend this book too highly … it weaves a complex developmental story with a range of facets. It emphasises clearly the rigour of the research that was conducted, while demonstrating the complexity of the inter-relationships, practices and issues for both teachers and researchers in developing practical and theoretical knowledge. Its graphic insights through text and associated media provide exemplars for teachers and those who work with teachers as a rich resource. It shows us all what can be achieved and the means of achieving it.” Prof. Barbara Jaworski, University of Loughborough

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How does professional development improve teaching? - Kennedy, Mary M. (Review of Educational Research, 2016)
Professional development programs are based on different theories of how students learn and different theories of how teachers learn. Reviewers often sort programs according to design features such as program duration, intensity, or the use of specific techniques such as coaches or online lessons, but these categories do not illuminate the programs’ underlying purpose or premises about teaching and teacher learning. This review sorts programs according to their underlying theories of action, which include (a) a main idea that teachers should learn and (b) a strategy for helping teachers enact that idea within their own ongoing systems of practice. Using rigorous research design standards, the review identifies 28 studies. Because studies differ in multiple ways, the review presents program effects graphically rather than statistically. Visual patterns suggest that many popular design features are not associated with program effectiveness. Furthermore, different main ideas are not differentially effective. However, the pedagogies used to facilitate enactment differ in their effectiveness. Finally, the review addresses the question of research design for studies of professional development and suggests that some widely favored research designs might adversely affect study outcomes.

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Evidence to Strengthen Tech-Supported Teacher Development in Madagascar - Coflan, Caitlin Moss; Koomar, Saalim; Rasolohery, Hasiniavo (EdTech Hub, 2021)
Our latest blog looks at using evidence to strengthen tech-supported teacher professional development in Madagascar. For more details, visit our website.

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Scrutinizing practicum for a more powerful teacher education: a longitudinal study with pre-service teachers - Tülüce, Serdar Hande; Çeçen, Sevdeger (Educational Sciences: Theory and Practice, 2016)
This study aims to explore the role of school-based practicum in promoting pre-service English language teachers' professional development through the use of a longitudinal design in combination with qualitative methods. To achieve this aim, pre-service teachers were asked to successively reflect on video-recordings of their micro-lessons in their university-based methodology courses directly after delivering the micro-lessons and retrospectively after their practicum experience. The participants of this study were 13 pre-service English language teachers studying at a foundation university in Istanbul, Turkey. The same data collection methodology was adapted before and after the practicum to gain a deeper understanding of the learning stemming from school-based practicum. The data for the study came from pre- and post-self-evaluation reports as well as pre- and post-focus-group interviews that had been collected based on the pre-service teachers' video-recorded microteaching simulations. The findings indicate that pre-service teachers commented on the same pedagogical, psychological, and physical factors they had noticed regarding their micro-lesson before and after the practicum. However, some qualitative changes were detected in their views over time as they had become more learner-oriented and had developed a more reflective view of teaching following the practicum. These findings have implications for the impact of practicum for future teacher education programs.
Keywords: Attitude Change; Case Studies; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); Focus Groups; Foreign Countries; Higher Education; Language Teachers; Learning Processes; Longitudinal Studies; Microteaching; Physical Characteristics; Postsecondary Education; Practicums; Preservice Teacher Education; Preservice Teachers; Pretests Posttests; Professional Development; Psychological Patterns; Qualitative Research; Reflective Teaching; Second Language Instruction; Self Concept; Self Evaluation (Individuals); Simulation; Student Teacher Attitudes; Teaching Methods; Transformative Learning; Turkey (Istanbul); Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096126; __finaldtb

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.

Understanding the professional learning and support needs of educators during the initial weeks of pandemic school closures through search terms and content use - Cavanaugh, Catherine; DeWeese, Abraham (Journal of Technology and Teacher Education, 2020)
Beginning in February and March of 2020, school closures impacted at least 90% of the world’s population of students, according to UNESCO estimates. As educators swiftly shifted to teaching online, they sought information to guide their initial planning and teaching in new environments with new tools. Analysis of educators’ search terms and their use of support content during this period indicates the needs felt by educators globally and informs content and professional development support for preservice educators. The authors compared the volume of searches, frequency of search terms, and patterns of content use during this period to the previous year by educators using an education support website. Re- sults show that site use multiplied six times in volume, use of video increased by 30 times, and among the search terms and content topics used during and prior to this period, focus nar- rowed to digital and distance learning. Implications of these findings are that professional development providers can meet educators’ needs with video and a focus on the specific teaching practices that educators are learning as they transi- tion to distance teaching at an entry level. Keyword
Keywords: Communicable Diseases; Disease Control; Distance Education; Educational Needs; Educational Technology; Faculty Development; Online Courses; Online Searching; Teaching Methods; Technology Uses in Education; Video Technology; Web Sites; ⛔ No DOI found

Professionalizing in- service teachers’ focus on technological pedagogical and content knowledge - Getenet, Seyum Tekeher; Beswick, Kim; Callingham, Rosemary (Education and Information Technologies, 2016)
In Ethiopia, primary school teachers of science and mathematics are encouraged to integrate Information and Communication Technology (ICT) into their teaching as a means to improve the quality of education. However, there has not been the same emphasis placed on providing professional learning opportunities for teachers on how to use ICT in their teaching. The present study investigated how a group of practising primary school science and mathematics teachers developed the skills needed to integrate ICT into their teaching. The study employed a combination of qualitative and quantitative research methods within an action research approach. The teachers took part in activities from a Technological Pedagogical and Content Knowledge (TPACK) based professional learning workshop, including designing lessons, classroom instruction, and reflection activities in teams. A lesson evaluation sheet, questionnaire, observation checklist, and logbook were used to gather data. The results showed that the teachers acquired an improved competency to integrate available ICT into their teaching through the intervention activities.

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Relocating Research on Teacher Learning: Toward Pedagogically Productive Talk - Lefstein, Adam; Vedder-Weiss, Dana; Segal, Aliza (Educational Researcher, 2020)
Most research and practice in teacher in-service learning focuses on formal professional development activities. This article calls for paying greater attention to the informal conversations that are embedded in teachers’ day-to-day work and through which they learn from one another what it means to be a teacher and how to perform their duties. The authors build on theory and research in teacher on-the-job discourse and learning in order to (a) argue that, as a field, we need to pay more focused and systematic attention to teacher on-the-job discourse; (b) offer a coherent conceptual framework for “pedagogically productive” teacher talk; and (c) highlight key research directions and challenges in investigating this and related phenomena.

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Global Report on Teachers: Addressing teacher shortages and transforming the profession. - UNESCO & International Task Force on Teachers for Education 2030 (Paris: UNESCO., 2024)
Teachers are central to unlocking every learner's potential and achieving Sustainable Development Goal 4 of inclusive, equitable and quality education for all. Regrettably, worldwide teacher shortages have been endangering the future of education. New data collected for the Global Report on Teachers indicates that 44 million additional teachers are needed to achieve universal primary and secondary education by 2030. Shortages are widespread, with sub-Saharan Africa needing 15 million more teachers, while higher-income countries face retention challenges, resulting in teachers massively leaving the profession. Echoing calls from the International Commission on the Futures of Education and the 2022 Transforming Education Summit, this report advocates for dignifying, diversifying, and valorizing the teaching profession. It emphasizes the importance of improved working conditions, enhanced professional development, and increased teacher involvement in decision-making to bridge the gap. This report is a tool to mobilize international and country efforts to empower, recruit, train, and support teachers within resilient education systems for a collaborative, innovative, and cohesive teaching profession. It is a roadmap, aiming to elevate the status of the teaching profession and ensure quality education for all learners, urging immediate action

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Prospective teachers' teaching experience: teacher learning through the use of video - Osmanoglu, Aslihan (Educational Research, 2015)
Background: Future teachers need to observe, interpret and analyse teaching during the initial teacher education period. The use of videoed teaching and learning in teacher education promotes reflection, and analysing videos of teaching is helpful in learning effective classroom practices that prospective teachers mostly do not have the chance to observe during fieldwork experiences. The analysis of videos of teaching can be seen as a way to enhance the development of prospective teachers' professional vision, which, in turn, improves instruction. Purpose: The purpose of this study was to examine prospective teachers' reflections on video examples depicting their own teaching experiences. It aimed to create a professional development environment to facilitate the prospective teachers' reflection on their own videos and those of their peers to improve their professional vision. Sample: This study was conducted with over 200 (in 31 groups) third-year prospective mathematics teachers in a university in Western Turkey. The student teachers, receiving training to teach first- to fourth-grade elementary school pupils, were taking a teaching methods course. Design and methods: In the first week of the semester, the student teachers, working in groups, were assigned mathematics topics to teach the elementary school pupils. During the semester, each group prepared by trying out their activities in front of other student teachers in other groups. At the end of the semester, one student teacher from each group presented a short lesson related to their mathematical topic to the elementary school pupils. This lesson was videotaped, then later it was watched and discussed by the student teachers. Of the student teachers who undertook the teaching in the videos, 22 volunteers agreed to be interviewed. All groups of student teachers provided written reflections on their experience. Selected videos of the class discussions about the videos of teaching were also used for triangulation. The data were analysed to identify the issues the prospective teachers reflected upon. A content analysis technique was employed. Results: The data indicated that the prospective teachers were able to reflect on several issues related to effective teaching, connect their theoretical knowledge to their practice and consider issues related to pupil learning and difficulties. Conclusion: The findings suggested that the use of video, together with discussions between the student teachers, had the potential to create promising learning opportunities for prospective teachers.
Keywords: Case Method (Teaching Technique); Case Studies; Case-based pedagogy; Content Analysis; Data Analysis; Discussion (Teaching Technique); EDUCATION of student teachers; EFFECTIVE teaching; ELEMENTARY school teachers; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Electronic Learning; Elementary Education; Elementary School Teachers; Foreign Countries; Higher Education; Knowledge Base for Teaching; Learning Activities; Mathematics Teachers; Methods Courses; Microteaching; Outcomes of Education; PROFESSIONAL education; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Reflective Teaching; Student Teacher Attitudes; Student Teachers; TEACHER education; TEACHING methods; TRAINING of student teachers; Teacher Effectiveness; Teaching Experience; Theory Practice Relationship; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096187; __finaldtb; class discussions; prospective teacher education; reflection; video case study

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using design-based research to bring partnership between researchers and practitioners - Getenet, Seyum (Educational Research, 2019)
Background: A key aim of educational research is for findings to inform practice, thereby bringing about improvements in teaching and learning. However, the relationship between research and practice is complex, and there is often no clear link between changes in practice and research findings. One of the challenges for research and practice is breaking down barriers and finding effective and sustainable ways to translate research findings into practical solutions in the classroom.Purpose: This discursive paper focuses on describing the nature of the partnership working involved when a design-based research (DBR) approach was employed to bring researchers and practitioners together. The researchers and practitioners worked in collaboration to design a professional development (PD) programme, in order to solve classroom problems and enhance practitioners’ research engagement.Sources of evidence: This paper describes the author’s experience of using DBR to co-design a PD programme that was responsive to a particular context and practitioners’ needs. It illustrates and exemplifies the ways in which the researcher–practitioner collaboration itself sits at the heart of the design process and enabled solutions to be found. The paper also considers the epistemological positions of the practitioners and researchers in the different stages of DBR. The context for the description is a mixed-methods intervention study conducted in two colleges of teacher education, which documented the design and refinement of a PD programme to facilitate teachers’ effective use of technology to teach mathematics.Discussion and conclusions: The examples presented and discussed here suggest how a DBR process is able to facilitate fruitful collaborations between researchers and practitioners and increase engagement in research. By working with practitioners to design interventions such as PD programmes, DBR can provide a practical approach for improving practice and deepening the relationship between educational research and classroom practice.
Keywords: Design-based research; evidence-informed practice; practice; practitioners; professional development; teacher education

‘Tich Mi Ar Tich Dem’: Designing a low-cost and scalable teacher professional development in Sierra Leone - Walker, Hannah; Tegha, Ghislaine; Lurvink, Anne-Fleur; McBurnie, Chris (Open Development & Education, 2022)
Reading Time: 4 minutes Over the past two decades, Sierra Leone has faced a series of shocks: a civil war, landslides, Ebola, and the COVID-19 pandemic. These shocks have aggravated the learning crisis that the country’s education system faces—and dramatically increased the pressure on teachers to deliver high-quality support to children. In this context, the Ministry of Basic and […]

Training teachers to use new technologies impacts multiple ecologies: Evidence from a national initiative - Davis, Niki; Preston, Christina; Sahin, Ismail (British Journal of Educational Technology, 2009)
A pair of papers re-examined the evidence from a national initiative to train all teachers in England to bring them up to the level of newly qualified teachers, who are required to know when to use and when not to use information and communication technologies (ICT) in their professional practice. The first paper confirmed that multilevel evaluation of professional development was robust for ICT teacher training. This second paper contrasts the highest and lowest rated designs for ICT teacher training: an ‘organic’ approach that provided training in schools was highly rated, whereas a centralised computer-assisted learning approach with online access to trainers was the lowest rated design. The study supports an ecological view of the diffusion of ICT innovations in education and recommends that ICT teacher training be designed to support evolution of each teacher's classroom, school and region, as well as the training of the ICT teacher trainers.

The Use of Information and Communications Technology (ICT) To Improve Access to In-Service Teacher Education Programmes For Educational Development in Pakistan - D‘CRUZE, Melaine (The Turkish Online Journal of Distance Education, 2009)
The use of ICT and distance education in the delivery of professional developmentprogrammers for in-service teachers to improve access to educational opportunitiesis explored in this article. Further, the link between teacher development and thedevelopment of human capital to aid educational and national development isdiscussed. The role of ICT and distance education is highlighted in enabling thisventure which eventually leads to overall educational and national development.
Keywords: ⛔ No DOI found

Timor-Leste education: Supporting sustainable system-wide reform and school leader capacity-building through collaborative foreign aid - Owen, Susanne; Wong, Debbie (Journal of Educational Change, 2021)
Effective school leadership and ongoing teacher capacity-building are essential aspects of school reform and improving educational outcomes for students in developing countries. This paper examines a Timor-Leste curriculum reform and associated school leader capacity-building and the implementation processes for building sustainability, within the context of research literature regarding effective professional development and successful foreign aid principles. The Timor-Leste leadership program was developed using an interpretivist paradigm and action research, with the authors being program designers and managers embedded in the context. School leader interviews and surveys, meeting notes and monitoring and evaluation reports, also teacher skills and student achievement data, were continuously examined to analyse issues and plan actions and solutions. Findings outline early impacts in relation to changing school leader behaviours, improved teacher skills and increased student literacy and numeracy, while also presenting implementation processes and actions taken to overcome challenges in relation to research-informed foreign aid principles.Given the importance of foreign aid for supporting significant educational improvement in developing countries, this Timor-Leste leadership capacity-building case study provides an example relevant to an under-researched area. While the focus is on one particular country and reform involving curriculum and professional development, the paper has value for other education contexts and system change initiatives which involve collaborations with foreign aid donors.
Keywords: Foreign aid; International development; School leadership capacity-building; School reform; School-based professional development; ⛔ No INSPIRE recid found

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.

Summary: EdTech in Cambodia - A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Cambodia. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

A framework for an ICT-based development program for science teachers in state universities and colleges in region VI - Magallanes, Amel Lavezores; Lavezores, Amel (Universal Journal of Educational Research, 2014)
Curriculum reform is central to the aspirations of many developing countries as they strive to deliver a quality education to their citizens. In State Universities and Colleges in Region VI, with its remarkable achievement of a high literacy rate in a few decades, the next step is bringing its resources to bear on providing a quality education so that Filipino science professors and students may take their places in the global labor force. This study concerns the integration of information and communications technologies (ICT) into the science curriculum of Higher Education Institutions in State Universities and Colleges in the Philippines particularly in Region VI, and the training and development requirements of science professors in this regard. A mixed methodology was employed to obtain qualitative data from 11 policy makers as represented by the Vice President of Academic Affairs of the SUC's in region VI, and quantitative data from a questionnaire for which 139 replies were received from SUC's science professors in Region VI.The findings of this study confirmed those citations in the literature that inefficient management planning and inadequate resources influence the integration of ICT in the science curriculum. Furthermore, the qualitative and quantitative findings confirmed that teachers' access to training is affected by time constraints, ineffective ICT course material, unavailability of ICT infrastructures and facilities, and high cost of ICT trainings. The policy makers interviewed in this study perceived the teachers as having a positive attitude toward ICT integration in the science curriculum, quantitative data from the teachers pointed to a high interest in ICT integration, and their willingness to pursue further professional development in the effective use of ICT in the science curriculum. Furthermore, age factor exhibited a significant difference in ICT skills, utilization and individual barriers of science teachers in SUC's Region VI. The length of service also showed a very significant difference as to the ICT skills, utilization attitudes, and individual barriers of the teacher respondents. However, as to their gender and highest educational attainment, home location and school location, there was no such factor implicating a non-significant difference in the attitudes, skills, utilization and perceived barriers.
Keywords: Barriers; College Faculty; College Science; Computer Literacy; Computer Uses in Education; ERIC, Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Information Technology; Mixed Methods Research; Philippines; Postsecondary Education; Science Teachers; State Colleges; State Universities; Teacher Attitudes; Technology Integration; Training

A Cascade Teacher Training Model in Disaster Education: A Case of Turkey - Gökmenoğlu, Tuba; Sönmez, Elif Daşçı; Yavuz, İbrahim (2021)
Individuals' reluctance to take precautions before the disasters happen is one of the most critical concerns of the disaster management area. The disaster education given through schools is a critical process in addressing this problem. The purpose of this paper is to introduce the teacher training program model and the implementation practices of Turkey's School-Based Disaster Education Project. In Turkey, there are few studies regarding the planning, development, implementation, and evaluation stages of Disaster Risk Reduction education for teachers. The project has been carried out within the framework of the Ministry of National Education and Japan International Cooperation Agency. An at-scale cascade teacher professional development model was implemented. The model reached 135,375 teachers in 67 provinces by the 567 trainer teachers in a relatively short time with the cascade training system. This project has brought a significant nationwide disaster risk reduction training experience for Turkey with its economic and sustainable structure.

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 5: Final report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021, the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE), and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fifth and final report on the development of a proof of concept for the Regional Learning Hub. We recommend beginning with this document and then moving to any of the remaining four reports, depending on your interest: Inception report; User research; Skills taxonomy; Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mobile literacy among Syrian refugee women teachers - Bradley, Linda; Bahous, Rima; Albasa, Ali (Research-publishing.net, 2019)
This research project investigates mobile literacy of Syrian refugee women teachers settled in Lebanon and Sweden. Our research provides input into Syrian refugee women teachers' professional aspirations and their connection to informal mobile learning. In both countries, training programs are used for these newly arrived teachers, enabling them to move forward in their careers, where digital and mobile learning play an important part. The purpose is to investigate how Syrian refugee women teachers are blending their teaching profession and vocational training with mobile literacy and digital technology. A qualitative method approach was applied, interviewing 20 refugee women in Lebanon and Sweden, all teachers from Syria. The outcomes show that the teachers are developing their vocational abilities in getting more career-oriented training in their areas of education by means of enhancing their language skills through mobile technology. [For the complete proceedings, see ED600837.]
Keywords: Career Development; Cross Cultural Studies; ERIC, Resources in Education (RIE); Faculty Development; Females; Foreign Countries; Handheld Devices; Informal Education; Information Technology; Land Settlement; Lebanon; Literacy; Occupational Aspiration; Refugees; Second Language Instruction; Second Language Learning; Sweden; Syria; Teacher Attitudes; Telecommunications; Videoconferencing; __:import:01; __:match:final; __:matched; __:study_id:2095768; ___working_potential_duplicate; __finaldtb

Digital storytelling and reflection in higher education: a case of pre-service student teachers and their lecturers at a university of technology - Ivala, Eunice; Gachago, Daniela; Condy, Janet; Chigona, Agnes (Journal of Education and Training Studies, 2014)
Employers in South Africa are calling for students graduating from higher education institutions (HEIs) to exhibit the capacity for reflection. However, many tertiary institutions fall short in allowing opportunities for reflection. As a result, HEIs are grappling to find ways of fostering reflection amongst their students. This paper argues that digital storytelling if implemented properly is one of the ways which can be used to help HEIs in this accomplishment. It documents results of production of digital stories by 29 final-year pre-service student teachers at the Cape Peninsula University of Technology (CPUT), South Africa, as part of their assessment in their professional development course. The study was informed by structuration theory and levels of reflection and cognitive processing to help the researchers understand the potential of digital storytelling in enhancing reflection. Qualitative methods of collecting data were utilized. Focus group interviews were conducted with the students and their facilitators to elicit whether production of digital stories led to reflection. Findings showed that the production of digital stories promoted the three levels of reflection and thus deep learning and higher-order thinking skills.
Keywords: Case Studies; Cognitive Processes; College Faculty; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Focus Groups; Foreign Countries; Higher Education; Personal Narratives; Postsecondary Education; Preservice Teachers; Professional Development; Qualitative Research; Reflection; Skill Development; South Africa; Story Telling; Teaching Methods; Technology Uses in Education; Video Technology; __:import:02; __:match:final; __:matched; __:study_id:2096367; __finaldtb

Digital training for increasing English teachers’ professionalism at junior high school - Syafryadin, Syafryadin; Wardhana, Dian Eka Chandra; Febriani, R.Bunga (Journal of Education and Learning (EduLearn), 2021)
This research aimed to know the problems and the implementation of the training as the solution and evaluation of digital training that can increase the English teachers’ professionalism at SMP Negeri 13 Bengkulu, Indonesia. This study used a descriptive qualitative method with the number of trainees were 10 English teachers. The procedures of collecting data were observation, documentation and interview. Then, the data analysis were done by comparing the result of the interview from the English teachers at SMP Negeri 13 Bengkulu, Indonesia before they joined and after joining digital training provided by the researchers and finally concluded. The first research finding is the English teachers had problems in terms of knowledge, difficult to apply the application or technology, and never joining training. The second finding is the implementation of digital training had many benefits namely increased the English teachers’ professionalism, experienced and innovated their knowledge and skills toward the use of digital learning, it brought a good quality for learning outcomes and it helped to be better in an advanced educational institution, particularly at SMP Negeri 13 Bengkulu, Indonesia. The last finding is that after implementation, the English teachers still got problems in using the application and need more training. The implication of this study is digital training can be an advanced way in educational development which needs good participation from the trainers, trainees and educational institution.

Strengthening Teacher Professional Development: Local and global communities of practice in Kakuma Refugee Camp - Mendenhall, Mary (Columbia University, 2017)
Keywords: C:Kenya / Rwanda

Technology for professional development: access, interest and opportunity for teachers of English in South Asia - British Council (British Council, 2015)

An overview of e-learning in China: History, challenges and opportunities - Wang, Yan; Liu, Xuan; Zhang, Zhenhong (Research in Comparative and International Education, 2018)
The Chinese government has attached great importance to the development of e-learning since its emergence in the 1990s. As a consequence of the implementation of a series of policies, China has made significant achievements in the e-learning arena with respect to infrastructure construction, production of resources, academic education, non-academic training, and education for disadvantaged groups. However, due to the constraints of China’s traditional culture, information literacy, and educational mechanisms, challenges have emerged in the implementation of e-learning that need urgently to be addressed. As e-learning in China continues to grow, major research areas such as students’ and teachers’ perspectives on developments in e-learning, teachers’ pedagogical capacity and ongoing professional development in e-learning settings, and the production of more convenient and useful e-learning resources, are likely to be topics of continuing research interest.
Keywords: Challenges; China; ICT in education; e-learning; professional development; successes

Teachers and Teaching in Sierra Leone - The World Bank (2021)

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Emerging fundamental issues of teacher education in Tanzania: a reflection of practices - Mgaiwa, Samson J (Educational Process: International Journal, 2018)
Quality of teachers is recognized as one of the critical dimensions for promoting student learning in schools. However, in Tanzania there are several emerging issues that affect teacher education and teachers, and as a result affect students’ learning. The existing corpus of literature indicates a death of studies on the systematic understanding of issues that affect teacher education in Tanzania, especially at a time when education across the world is encountering a number of challenges. Employing documentary review and interviews as data collection methods, this paper attempts to analyze the emerging issues affecting teacher education in Tanzania. Employing the Teacher Education Model for the 21st Century, the paper identified five major issues affecting teacher education namely; lack of specific policies for teacher education, lack of continuing professional development, lack of an autonomous teacher regulatory body, inadequate ICT and teacher education, and poor quality of candidates joining teacher education. Generally, the findings indicate that teacher education is not effectively planned in terms of policy imperatives to meet the contemporary professional demands for 21st century education in Tanzania, and beyond. Finally, conclusions and certain recommendations which take a futuristic perspective in preparing 21st century teachers are offered.
Keywords: 21st century; Education; Learning; Tanzania; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095912; __finaldtb; students’ learning; teacher education; teachers

Designing an Educational Innovation to Achieve Scale: Five Critical Concepts - Dede, Chris (The EvoLLLution, 2016)
Research has documented that in education, unlike other sectors of society, the scaling of successful instructional programs from a few settings to widespread use across a range of contexts is very difficult (Dede, Honan, & Peters, 2005). In fact, research typically shows a huge influence of setting (e.g., the teacher’s content preparation, students’ self-efficacy, prior […]

Embracing EdTech: four critical questions answered through a rapid prototype programme on teachers’ professional development (TPD) - Sabbab, Salman; Shakil, Abdullah All; Alam, Faria (EdTech Hub, 2021)
Seventy-one teachers participating in the ‘Onneshon’ prototype were flooding the WhatsApp group with messages about the challenges and hiccups they were experiencing, either with watching the video content or with taking a quiz in the first two weeks. Problems were pouring in and so were solutions being innovated and offered through diverse channels. In the space of two weeks, the…
Keywords: _EdTechHub_Output

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Effectiveness of Teachers’ Guides in the Global South: Scripting, Learning Outcomes, and Classroom Utilization - Piper, Benjamin; Sitabkhan, Yasmin; Mejia, Jessica; Betts, Kellie (RTI Press, 2018)
This report presents the results of RTI International Education’s study on teachers' guides across 13 countries and 19 projects. Using quantitative and qualitative methods, we examine how teachers’ guides across the projects differ and find substantial variation in the design and structure of the documents. We develop a scripting index so that the scripting levels of the guides can be compared across projects. The impact results of the programs that use teachers’ guides show significant impacts on learning outcomes, associated with approximately an additional half year of learning, showing that structured teachers’ guides contribute to improved learning outcomes. During observations, we find that teachers make a variety of changes in their classroom instruction from how the guides are written, showing that the utilization of structured teachers’ guides do not create robotic teachers unable to use their own professional skills to teach children. Unfortunately, many changes that teachers make reduce the amount of group work and interactivity that was described in the guides, suggesting that programs should encourage teachers to more heavily utilize the instructional routines designed in the guide. The report includes a set of research-based guidelines that material developers can use to develop teachers’ guides that will support effective instructional practices and help improve learning outcomes. The key takeaway from the report is that structured teachers' guides improve learning outcomes, but that overly scripted teachers' guides are somewhat less effective than simplified teachers' guides that give specific guidance to the teacher but are not written word for word for each lesson in the guide.

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Guidance Note 1 In the local context — using digital technologies to develop local content From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Cultivating a personal learning network that leads to professional change - Stewart, Benjamin L. (Northcentral University, 2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about teaching and learning and the practicalities teachers face in the classroom. The purpose of this qualitative multiple case study was to describe how ideas, materials, and social interactions form a PLN through online, informal pedagogical dialogues among English language educators as it relates to professional learning. The five participants of this study were selected from a total of 10 based on their willingness to complete an informed consent form, complete an initial online survey, interact with other professionals publically online, and participate in a final interview. The online survey contained demographic information about each case and included both open and closed items; a content analysis was done on public interactions that tool place online; and a final in-depth interview used open questions to inquire about how respective PLNs changed over time. All data was coded, categorized, and placed into themes based on the ideational, material, and social aspects of each PLN. The findings show that professional knowledge, skills sets, and overall dispositions emerge in unique ways based on how ideas, technologies, and personal contacts interrelate with each other over time, and that an individual’s PLN provides unanticipated benefits when sharing publicly online.
Keywords: 0444:Foreign language education; 0449:Educational leadership; 0710:Educational technology; Actor-network theory; Complexity; Content analysis; Education; Educational leadership; Educational technology; English; Foreign Language; Learning; Personal learning network; Polls & surveys; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2096277; __finaldtb

Artificial Intelligence in Education Across Bangladesh: Findings from a rapid scan and key informant interviews - Honda, Delanie; Ahmed, Shakil; Ramesh Vasudevan, Sharanya (EdTech Hub, 2025)
This Helpdesk Report was developed in response to a request from the UK's Foreign Commonwealth and Development Office (FCDO) Bangladesh for a rapid scan on the use of Artificial Intelligence (AI) in Bangladesh’s education system. The report aims to provide education decision-makers with accessible, evidence-based summaries of best practices in specific areas of EdTech, in this case, the AI landscape in Bangladesh. Using a combination of desk research and key informant interviews, the scan provides insights for the FCDO by highlighting key actors, early use cases, opportunities, and challenges, and to support future thinking about AI’s role in education, particularly as Bangladesh is preparing for its next development education plan — the Primary Education Sub-Sector Programme. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Developing great teaching: lessons from the international reviews into effective professional development - Cordingley, P; Higgins, S; Greany, T; Buckler, N; Coles-Jordan, D; Crisp, B; Saunders, L; Coe, R (Teacher Development Trust, 2015)

Recommendation 7: Use ICT to provide access to content, professional development and professional learning communities - Lawrie, J.; Hennessy, Sara; Haßler, Björn; Phalachandra; Lawrie, J. (Where it's needed most: Quality professional development for all teachers, 2015)
Keywords: C:Fragile contexts; dode_eth-src-dode; dode_eth-trf2-dode

Developing Quality Teacher Professionals: a Reflective Inquiry on the Practices and Challenges in Tanzania - Anangisye, William A.L. (Papers in Education and Development, 2011)
Keywords: ⛔ No DOI found

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobilephones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
Keywords: C:Bangladesh

Usawa na maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Chachage, Kristeen; Swai, Calvin; Rwambali, Innocent; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Chuo Kikuu cha Dodoma, Chuo Kikuu cha Aga Khan, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza upanuzi na mabadiliko ya kuendana na mahitaji ya walimu na mazingira ya shule katika utekelezaji wa Mafunzo Endelevu ya Walimu Kazini (MEWAKA) unaojumuisha matumizi ya teknolojia. Katika kuandaa zana hizi, tumetumia zana zilizochapishwa katika awamu ya kwanza ya utafiti huu na mifano kutoka sehemu mbalimbali, kwa kuzingatia mifano mizuri ya utafiti kuhusu elimu. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Cultivating a Personal Learning Network that Leads to Professional Change - Stewart, Benjamin L (2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about
Keywords: ⛔ No DOI found

Cultivating a Personal Learning Network that Leads to Professional Change - Stewart, Benjamin L (2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about
Keywords: ⛔ No DOI found

EdTech Horizon Scan: Rapid scan on emerging EdTech research during the Covid-19 pandemic. - Ampofo, Rudolph; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking and provide insight into a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This edition of the Hub’s Horizon Scan provides a high-level summary of research, blogs, and think-pieces published between October and December 2021, that provide insights and learnings on the adoption and utilisation of EdTech during the Covid-19 pandemic. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Contract Type and Teacher Absenteeism in Benin: The Role of Teacher’s Supplemental Income - Senou, Barthelemy Mahugnon (2021)
Absenteeism is a phenomenon that has been noted in professional circles with consequences on the income of the wage earner as well as the profits of the firm, consequences that led, according to statistics from 2005, to losses in public finance amounting to close to 70 billion francs for the Government of Benin. Despite such losses, very few studies in economics have focused on the subject in order to try and give an understanding of the real causes of absenteeism and its consequences. The objective of this study is to explore the relationship between the status of the teacher, supplemental income of the teacher, and the absenteeism of the teacher. Using data from PASEC-CONFEMEN 2005, that will be applied to a theoretical model that we are developing, and through the use of a Tobit empirical method, after having taken the endogeneity bias on the practice of supplemental income generating activities by the teacher into account, this study demonstrates that the practice of income generating activities by teachers positively influences their absenteeism, with contract teachers being more frequently absent than those who are on permanent and pensionable employment contracts. Through linking the level of prices in a locality with absenteeism behaviours, we make it clear that the reasons for absenteeism are mostly related to low purchasing power in the context of earning relatively meagre salaries. These results elicit a set of recommendations that essentially suggest that there should be an improvement in the salaries and working conditions of teachers.
Keywords: C:Benin; ⛔ No DOI found

USAID/Madagascar impact evaluation of the Mahay Mamaky Teny (MMT) project - Moussa, Wael; Cao, Yvonne; Louge, Nathalie (United States Agency for International development, 2018)

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Preservice and Inservice Professional Development During the COVID-19 Pandemic - Hartshorne, Richard; Baumgartner, Emily; Kaplan-rakowski, Regina; Mouza, Chrystalla; Ferdig, Richard (Journal of Technology and Teacher Education, 2020)
The global COVID-19 pandemic has changed our lives in countless ways. This has included the move to emergency remote learning for PreK-12 and post-secondary education around the world. While school districts and post-secondary education institutions originally anticipated relatively brief closures, the impact of COVID-19 resulted in extensive periods of emergency remote teaching and learning. Many K-12 school districts and institutions of higher education had to teach online for almost all of the spring semester (2020); they have also added contingency plans for future remote instruction in the summer and for the 2020-2021 academic year. As we move beyond the survival phase of remote teaching and learning, it is critical now to transition to a thriving phase of remote teaching, learning, and teacher education.
Keywords: ⛔ No DOI found

Challenges encountered by teachers in supporting children with autism in primary schools in Tanzania - Ndunguru, N.E.; Kisanga, S.E. (Papers in Education and Development, 2023)
This paper reports the challenges experienced by teachers in supporting children with autism (CA) in primary schools in Tanzania. It is a qualitative study that employed purposive sampling technique to select seven primary school teachers of CA from two schools. Data were collected using a semi-structured interview and were analysed thematically. The findings of the study revealed that teachers experience challenges when supporting CA due to inadequate knowledge in managing the behaviours of CA. Also, teachers received little collaboration from parents of CA due to a lack of commitment to the education of their CA. The paper recommends for continuous professional development training to teachers of CA to enhance the acquisition of updated knowledge and skills for supporting CA. Also, there is a need for effective collaboration between teachers and parents for the successful support of CA.

Using technology to support teacher continuous professional development in Sierra Leone - Beoku-Betts, Iman; Plaut, Daniel; Tanweer, Rabia; Tanweer, Iman Beoku-Betts, Daniel Plaut and Rabia (EdTech Hub, 2022)
In Sierra Leone, EdTech Hub has been working closely with the TSC and the World Bank over the last 18 months to design a TCPD model that will provide primary school teachers with tools to improve their literacy and numeracy instruction.

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

How Is AI Being Used by Education Ministries to Improve Service Delivery in Low- and Middle-Income Countries? - D'Rozario, Jonny (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Save our future - Haßler, Björn; Sagun, Rose (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodoODE

Research on the response to COVID19 - Haßler, Björn; Fitzpatrick, Rachael (BE2, 2020)
Presentation given at BE2, 2020-10-06.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _yl:u; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The global stakes of digitalization in education - Haßler, Björn (The global stakes of digitalization in education (Uganda), 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Demand-Driven Evidence Delivery and Uptake: Reflections on the Edtech Hub Helpdesk - Jordan, Katy; Thakrar, Jayshree; Patel, Prachi; Ramesh Vasudevan, Sharanya; Coflan, Caitlin; Thang, Sarah; Myers, Christina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason; Thornton, Rebecca L. (SSRN Electronic Journal, 2018)
Keywords: _C:Australia AUS; _C:Chad TCD; _C:Ecuador ECU; _C:India IND; _C:Kenya KEN; _C:Mexico MEX; _C:Spain ESP; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:scheme:1

Preparing K-12 Schools for a Pandemic before It Occurs - Christensen, Rhonda; Alexander, Curby (Journal of Technology and Teacher Education, 2020)
While almost all K-12 schools closed for the COVID-19 pandemic with little or no preparation, one school began to prepare 12 years ago for a time such as this. In 2006, the school leadership team began to consider what would happen to teaching and learning in the event of a large-scale pandemic causing the buildings to be closed. The school implemented a Distance Learning Day (DLD) in fall 2007 and continued it for one day each of five years. This paper describes the rationale, implementation, and outcomes of the endeavor, as well as its impact on students, teachers and parents. Implications for professional development are also included for those seeking to replicate this approach.
Keywords: COVID-19; Communicable Diseases; Distance Education; Educational Benefits; Electronic Learning; Elementary Secondary Education; Emergency Programs; Instructional Design; Pandemics; Parent Attitudes; Planning; Program Effectiveness; Program Implementation; School Closing; Student Attitudes; Teacher Attitudes; Teacher Education; ___working_potential_duplicate; ⛔ No DOI found

Technology for Teacher Training - IDEAS (IDEAS | Institute of Development and Economic Alternatives, 2017)
The project will be introducing a new model of delivering in-service teacher training to government sector primary school teachers (PSTs), which builds upon the existing structure of cluster-based Continuous Professional Development (CPD) in Punjab.The Directorate of Staff Development (DSD) employs a cluster-based approach to in-service teacher training which constitutes a cascading model. Although the model […]

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

OER4Schools: Participants Book - Hennessy, Sara; Haßler, Björn; Blair, Janet; Duggal, Nitu; Shin Leong, Wei; Makonga, Abel; Tembo, Agness (The Centre for Commonwealth Education, 2014)
Keywords: dode_eth-src-dode; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Worst practice in ICT use in education - Trucano, Michael (World Bank Blogs, 2010)
In business and in international development circles, much is made about the potential for 'learning from best practice'. Considerations of the use of educational technologies offer no exception to this impulse. That said, 'best practice' in the education sector is often a rather elusive concept (at best! some informed observers would say it ...
Keywords: auto_merged

An Evaluation of ELLN Digital: Technology-Supported Teacher Professional Development on Early Language, Literacy, and Numeracy for K-3 Teachers - Oakley, Grace; King, Ronnel; Scarparolo, Gemma (Digital Learning for Development, 2018)
Keywords: ⛔ No DOI found

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem--the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity--and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints--most of them beyond the scope of action of teachers and students and not approached by previous research--hindering the integration of mathematical modelling in current secondary schools.
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

ICT integration in teaching and learning activities in higher education: a case study of Nepal's teacher education - Rana, Kesh; Rana, Karna (Malaysian Online Journal of Educational Technology, 2020)
This article reports an examination of information and communication technology (ICT) integration in teaching and learning activities in higher education in Nepal. ICT education policy by the government of Nepal emphasises the need to develop teachers' ICT competencies and suggests the use of ICT will transform traditional models of teaching to ones that are student-centred. The case study reported the lack of clear strategy to implement the ICT education policy and to fund for the ICT infrastructure and professional development of university staff to integrate ICT in teacher education. In this case, the Faculty of Education in the university, where there is no funding from the government and university for the ICT in education project, received funding from an international organisation to install ICT infrastructure and provide ICT training for teachers and other staff. It is argued that, to realise the policy in practice, more sustainable mechanisms need to be developed to provide ICT facilities for teachers and to train them how to use ICT in teaching activities.
Keywords: ERIC, Current Index to Journals in Education (CIJE); Educational Policy; Foreign Countries; Higher Education; Information Technology; Nepal; Postsecondary Education; Preservice Teacher Education; Program Implementation; Sustainability; Technology Integration; __:import:01; __:match:final; __:matched; __:study_id:2095751; __finaldtb

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The Use of Technology in the CPD Implementation Plan in Tanzania - Adam, Taskeen; El-Sefary, Yomna; Haßler, Björn; Khalayleh, Abdullah; Kremeia, Adam; Proctor, Jamie; Mtebe, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

Promising Practices in Teacher Professional Development - Inter-Agency Network for Education in Emergencies (Teachers in Crisis Context, 2022)

Continuous Teacher Training Goes Nationwide in Tanzania - World Bank (World Bank, 2023)
A World Bank-funded program is piloting continuous professional development for primary school teachers in Tanzania.

A different approach to scaling up educational technology initiatives - Trucano, Michael (World Bank Blogs, 2013)
the way most projects 'scale up' just might yield inequitable results Much is made of the necessity to 'scale up' in international development circles. Here at the World Bank, a quick search on our web site reveals publications and conferences with titles like Scaling Up Knowledge Sharing for Development, Global ...

Teachers need training and support, not just an internet connection, to deliver quality distance education - Conover, Anna C (Teacher Task Force, 2022)
This blog is based on the findings of Distance learning and teacher training strategies. Lessons from the Caribbean, a recently published report by the Teacher Task Force. It was written by Anna C. Conover, Consultant Distance teaching and learning have expanded rapidly around the world since COVID-19 school closures first began in 2020. The transition exposed a wide digital divide in many countries, where lack of access to devices, online content and internet connectivity hindered universal access. Equally crucial, the shift shone a light on the need for more and better teacher training in digital and relevant pedagogical skills. However, in spite of this urgent need, ministries of education in many countries are only now integrating ICT competencies and standards into teacher policy frameworks. Moreover, traditional teacher training programmes do not necessarily adequately cover digital and related pedagogical skills in initial teacher training and continuing professional education. Teacher training can help improve learners’ and teachers’ experience of distance learning In response to the demand for training in distance learning and technology integration in small island developing states (SIDS) in the Caribbean, the Distance Learning and Teacher Training Strategies in the Caribbean SIDS teacher training programme was created to enhance the capacity of national education systems. The Teacher Task Force, UNESCO’s Global Education Coalition, Blackboard, the Caribbean Centre for Educational Planning (CCEP), UNICEF Jamaica, and the German Federal Ministry for Economic Cooperation and Development collaborated to develop, implement and monitor the programme. Building on the 2020 pilot project, Professional Development for Teachers for Blended Learning and Online Strategies, the programme was designed to strengthen teachers’ digital and related pedagogical skills. It took a holistic and context-sensitive approach to strengthening teachers’ capacity to guarantee that the most vulnerable students were not left behind during the crisis. The project aimed to confront challenges such as: how to maintain engagement and interaction for learning; how to convert content into appropriate online learning formats; how to handle school management issues, such as the need to respect normal school hours; and how to work with students with diverse needs. Providing support in these areas also helped to address teachers’ psychosocial well-being, since the abrupt transition to online teaching led to significant disruption of teachers’ professional and personal lives, causing uncertainty and other emotional challenges. Careful course design, adaptable materials and supportive communities of practice are essential for successful distance learning A key lesson from the programme was the importance of high standards for course design, content, and capacity for collaboration and delivery. Online platforms or learning management systems must be intuitive and user-friendly; courses must include different forms of interaction and student-teacher feedback loops; and time and space must be allotted for collaboration, reflection and experimentation. Since parental involvement is important for successful distance learning, course design should also include guidance for parents and reliable channels for them to communicate with teachers. Preparing and adapting materials for online learning is one of the most challenging and time-consuming tasks for teachers in transitioning to distance learning. So, teacher training should include guidance on tools to facilitate this work, such as “live worksheets”, which are interactive and support assessment at a distance. And programmes should use open-source materials where possible, or explicitly state copyright conditions when needed, to increase scalability and enable teachers to re-use materials. Teachers who participated in the teacher training programme particularly appreciated being part of a community of practice, enabling them to make new connections with distance education experts and other teachers in similar situations across their country and region. This feeling of belonging to a supportive network, as well as their newly acquired skills, boosted their personal and professional confidence in applying digital technologies and the required skills in their classrooms. Teacher training for distance education should prepare teachers to create inclusive online learning environments Ensuring inclusive education should be a priority in distance learning. Even though this form of schooling can limit teachers’ interactions with students (e.g., by reducing opportunities for spontaneous communication and gestural cues), it can also provide opportunities to promote inclusion. Designing courses with accessibility in mind is essential to create inclusive learning environments. For instance, to accommodate the needs of learners with disabilities, participants should be given a range of ways to access materials and participate in courses. This may include offering asynchronous* and synchronous** options for discussion, multimodal (visual, aural, textual, etc.) delivery of content, and downloadable as well as livestreamed content. In multilingual contexts, adapting to teachers’ language needs is also essential. In the SIDS programme, course content was often only available in French or English. However, to allow participants to conduct discussions in the language with which they were most comfortable, course facilitators allowed participants to form online breakout groups using other languages. Flexibility is a key feature in planning for teacher training Training teachers for distance education must be flexible, since teachers have competing and sometimes unforeseen demands on their time. Course content, pacing and assignments should be adjusted throughout the course according to participants’ changing needs. This is particularly important during emergency situations. For accreditation transparency and to maintain teacher motivation, courses can adapt to teachers’ time constraints by offering different levels of certification and micro-credentials for specific ICT skills. Careful planning that considers school calendars and teachers’ accessibility needs, as well as good communication campaigns, are essential to ensure successful enrolment and sustained attendance in teacher training. Registration should be easy and obstacle-free, and directly available online. In general, teacher training should not be scheduled at the beginning or at the end of the school year when teachers are busiest, or during long summer vacations when many teachers are not available. Partnerships are important for developing teacher training programmes for distance education Partnerships are particularly important in delivering distance education, since it requires considerable expertise and resources, including costly devices, uninterrupted connectivity, education software, open educational resources, and pedagogical and organizational expertise. Given that connectivity and device availability are often a barrier in online education, governments and stakeholders should develop partnerships with technology companies and internet providers to identify solutions, while ensuring that data security and participant privacy are respected. Educational technologies have proven to be useful to ensure continuity of education in emergency situations. Increasingly true to all societies, they are also among the basic tools needed to fully participate in our contemporary world. However, investing in these technologies will not achieve the desired results unless we also invest in teachers’ digital and related pedagogical skills. Initial and in-service teacher education must therefore be re-imagined including these skills and technologies. With their first-hand experience of the challenges and opportunities of remote teaching, teachers must be involved in the design, implementation and monitoring of distance learning and technology integration. In such a way, they must effectively be placed at the heart of wider education transformation. Glossary  *Asynchronous online learning:  Education and learning that occur online at a different time compared to when the teacher is instructing. **Synchronous online learning: Education and learning that occur online at the same time, but not in the same place with teachers and/or other learners. Photo credit: Abir Roy Barman/Shutterstock.com

Policy Report on UNHCR’s Community Technology Access Program: Best Practices and Lessons Learned - Anderson, Jessica (Refuge: Canada's Journal on Refugees, 2013)
This report gives an overview of UNHCR’s Community Technology Access (CTA) program, which aims to improve education and livelihood opportunities for displaced populations via technology. Th e paper analyzes the key findings of a comprehensive external evaluation of the program conducted in 2012. According to the evaluation, the areas of greatest positive impact for people of concern were in the enjoyment of basic rights to freedom of expression and information, in building relationships with the host community, and social networking. However, access to technology alone is not sufficient to achieve the goals of quality education and self-reliance. Therefore, the evaluation recommends developing strategic, contextualized education and livelihood content and tools in order to achieve the desired goals of learning, skills, and access to employment, as well as a reassessment of CTAs’ potential for operational and fiscal autonomy in different countries.
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_pedagogies and modalities

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teachers’ Perceptions of Adopting Information and Communication Technologies in Teaching and Learning at Rural Secondary Schools in Eastern Cape, South Africa - Chisango, Grasia; Newlin Marongwe; Mtsi, Nomxolisi; Matyedi, Thembisile E (Africa Education Review, 2020)
There is an increasing global call to adopt information and communication technologies (ICTs) in teaching and learning. ICTs have become so essential that the South African government has introduced the e-education policy. ICTs are powerful enabling tools that play a significant role in the teaching and learning process. This article reports on a study that sought to explore teachers’ perceptions of adopting ICTs in teaching and learning at some secondary schools in Eastern Cape, South Africa. The purposive sampling technique was used to identify three secondary schools and five study participants from each school. Data was collected through face-to-face interviews and focus group discussions. A thematic approach was adopted to analyse and present the collected data. The study found that the teachers had a positive attitude towards the adoption of technologies and were ready to integrate ICTs in teaching and learning but they lacked the requisite ICT skills. The article concludes that ICT is an important vehicle in education, and further recommends the training of both teachers and learners in ICT usage.
Keywords: Communication technology; Communications technology; Curriculum development; Education policy; Education--Higher Education; Information technology; Learning; Pedagogy; Perceptions; Positive thought; Rural communities; Secondary schools; South Africa; Teachers; Teaching; curriculum interpretation; intervention strategies; pedagogy; professional development; support

Factors affecting teachers’ continuation of technology use in teaching - Kafyulilo, Ayoub; Fisser, Petra; Voogt, Joke (Education and Information Technologies, 2016)
This study was conducted to investigate the continuation of technology use in science and mathematics teaching of the teachers who attended a professional development program between 2010 and 2012. Continuation of technology use was hypothesized to be affected by the professional development program and by personal, institutional, and technological factors. Twelve teachers and three school leaders participated in the study. Data was collected through interviews. Findings showed that the continuation of technology use differed for the teachers involved in the professional development program. While all teachers reported to have gained knowledge and skills through the professional development program and were positive about technology use in education, only some teachers continued the use of technology. The data revealed that despite the challenges that all teachers in the sample encountered when using technology in their teaching (such as large classrooms, problems with electricity supply, lack of time and lack of technology tools), the encouragement of school management was a critical factor in teachers’ continuation of technology use. Implications of the findings are discussed.

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Improving procedural and conceptual mathematics outcomes: evidence from a randomised controlled trial in Kenya - Piper, Benjamin; Ralaingita, Wendi; Akach, Linda; King, Simon (Journal of Development Effectiveness, 2016)
To improve learning outcomes, an intervention in Kenya called the Primary Math and Reading (PRIMR) Initiative provided pupil learning materials, teachers’ guides and modest teacher professional development in mathematics. This paper presents the causal impact of PRIMR’s mathematics intervention on pupil achievement indices for procedural and conceptual numeracy, using a diﬀerences-in-diﬀerences analytic strategy. The mathematics intervention produced modest, statistically signiﬁcant results: generally similar results for males and females, a larger impact in grade 2 than grade 1, a larger impact in nongovernment schools than public schools, and smaller outcomes in mathematics than for English or Kiswahili. These ﬁndings have relevant policy implications in Kenya given an impending national mathematics programme.
Keywords: Kenya; Numeracy; elementary school; instruction; international education; mathematics

Examining factors affecting beginning teachers’ transfer of learning of ICT-enhanced learning activities in their teaching practice - Agyei, Douglas D.; Voogt, Joke (Australasian Journal of Educational Technology, 2014)
This study examined 100 beginning teachers’ transfer of learning when utilising Information Communication Technology-enhanced activity-based learning activities. The beginning teachers had participated in a professional development program that was characterised by ‘learning technology by collaborative design’ in their final year of their pre-service preparation program.  Transfer of learning was proposed as characteristic of (i) the professional development program,(ii) beginning teachers and (iii) school environment. Beginning teachers held positive views about active learning and ICT use developed during the professional development program, which seemed the strongest predictor in transfer of their learning. The study also showed that a significant amount of explained differences in the level of transfer of ICT-enhanced activity-based learning innovation could be attributed to range of factors across individual beginning teachers and school environment characteristics. Implications of these findings are discussed.
Keywords: __:import:02; __:match:final; __:matched; __:study_id:2425905; __finaldtb

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Ukraine: UNESCO’s platform to bring together teachers and - UNESCO (2024)
In a time of unprecedented challenges imposed by war, educators in Ukraine have found a designated space for professional development and support in the online Community of Modern Teachers and

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

An investigation of appropriate new technologies to support interactive teaching in Zambian schools (ANTSIT). A joint report from Aptivate and the Centre for Commonwealth Education (University of Cambridge). Final Report to DfID. - Haßler, Björn; Hennessy, S.; Lord, T.; Cross, A.; Jackson, A.; Simpson, M. (Aptivate and University of Cambridge, 2011)
Keywords: Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Sandboxes: Testing the strategy in Malawi - Carter, Alice (EdTech Hub, 2020)
Written by Alice Carter This is the second in this series about our sandboxes. If you haven’t already, read about our approach to experimentation.  Across the Hub, we’re proponents of using our tools and approaches on our own thinking. For innovation, that meant testing the assumptions we were making about how and if the sandboxes …
Keywords: C:Malawi; F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

From Preparation to Practice: Designing a Continuum to Strengthen and Sustain Teaching - Feiman-Nemser, Sharon (Teachers College Record: The Voice of Scholarship in Education, 2001)
This paper was written to stimulate discussions and debate about what a professional learning continuum from initial preparation through the early years of teaching could be like. Drawing on a broad base of literature, the author proposes a framework for thinking about a curriculum for teacher learning over time. The paper also considers the fit (or misfit) between conventional approaches to teacher preparation, induction and professional development and the challenges of learning to teach in reform-minded ways and offers examples of promising programs and practices at each of these stages. The paper is organized around three questions: (a) What are the central tasks of teacher preparation, new teacher induction, and early professional development? (b) How well do conventional arrangements address these central tasks? (c) What are some promising programs and practices at each stage in the learning to teach continuum that promote standards-based teaching and enable teachers to become active participants in school reform?

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

How to Improve Teaching Practice? Experimental Comparison of Centralized Training and In-classroom Coaching - Cilliers, Jacobus; Fleisch, Brahm; Prinsloo, Cas; Taylor, Stephen (Research on Improving Systems of Education (RISE), 2018)
We experimentally compare two modes of in-service professional development for South African public primary school teachers. In both programs teachers received the same learning material and daily lesson plans, aligned to the ofﬁcial literacy curriculum. Pupils exposed to two years of the program improved their reading proﬁciency by 0.12 standard deviations if their teachers received centralized Training, compared to 0.24 if their teachers received in-class Coaching. Classroom observations reveal that teachers were more likely to split pupils into smaller reading groups, which enabled individualized attention and more opportunities to practice reading. Results vary by class size and baseline pupil reading proﬁciency.
Keywords: C: South Africa

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

MOOC adaptation and translation to improve equity in participation - Wolfenden, Freda; Cross, Simon; Henry, Fiona (Journal of Learning for Development, 2017)
There is an urgent need to improve elementary and secondary school classroom practices across India and the scale of this challenge is argued to demand new approaches to teacher professional learning. Massive Open Online Courses (MOOCs) represent one such approach and one that, in the context of this study, is considered to provide a means by which to transcend traditional training processes and disrupt conventional pedagogic practices. This paper offers a critical review of a large-scale MOOC deployed in English, and then in Hindi, to support targeted sustainable capacity building within an education development initiative (TESS-India) across seven states in India. The study draws on multiple sources of participant data to identify and examine features, which stimulated a buzz around the MOOCs, leading to over 40,000 registrations and a completion rate of approximately 50% for each of the two MOOCs.
Keywords: Access to Computers; Access to Education; Attitude Measures; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Equal Education; Foreign Countries; Higher Education; India; International Programs; Large Group Instruction; Online Courses; Partnerships in Education; Postsecondary Education; Pretests Posttests; Program Implementation; Questionnaires; Surveys; Teacher Education Programs; Teacher Educators; Technology Uses in Education; United Kingdom; __:import:01; __:match:final; __:matched; __:study_id:2096064; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Integrating ICT into schools in Sub-Saharan Africa: from teachers’ capacity building to classroom implementation - Agyei, D. D (Education and Information Technologies, 2021)
This study followed up on a selected cohort of 4945 Science, Technology, English and Mathematics (STEM) teacher participants from six Sub-Saharan African countries namely: Kenya, Tanzania, Uganda, Ethiopia, Ghana and Nigeria. The teachers were involved in an instructional digital professional development programme targeted at building their capacity to embed ICT into school organizational and curriculum practices. This study sought to evaluate the impact of the ICT- instructional professional development programme in relation to the quality and the extent of the teachers’ transfer of the programme’s ideas from capacity building to classroom instructional practices. Data for the study were collected using semi-structured survey instrument and diaries kept to maintain records of activities and events during the period of implementation. Findings revealed that the teachers expressed general satisfaction with content and processes of the training programme; however, essential conditions to support transfer of the training’s ideas to school level seemed not adequate during the period of implementation. Implications for effective professional development in integrating ICT into school organization and curriculum practices that have sustainable impact on teaching and learning particularly in Sub-Saharan regions and similar contexts are discussed.

A COVID-19 intervention: Using digital escape rooms to provide professional development to alternative certification educators - Gómez, Miguel (Journal of Technology and Teacher Education)

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Effective teacher professional development - Darling-Hammond, Linda; Hyler, Maria E.; Gardner, Madelyn (Learning Policy Institute, 2017)

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Factors influencing teachers’ level of participation in online communities - Khalid, Fariza; Joyes, Gordon; Ellison, Linda; Daud, Md Yusoff (International Education Studies, 2014)
The use of an online learning community is one possible approach to teachers’ professional development that can enhance the opportunity for collaboration. Discussions in online learning communities not only allow community members to share resources, ideas and expertise, but also contribute to the fulfilment of teachers’ needs in terms of continuous learning and professional development. This paper reports the findings of a study that aimed to explore the factors that influence the way teachers behave in online communities. The research participants were 16 teachers from five secondary schools in Malaysia who were teaching English, science and mathematics. These teachers were involved in online learning communities via blogs in which they exchanged stories and experiences related to their teaching and learning activities. Data were generated through one-to-one interviews. Based on thematic analysis, the overall findings indicate that teachers’ levels of participation in their online learning communities were largely influenced by cultural issues. Other factors that impacted upon their engagement were time, enforcement by school administrators and their need for an online community.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096356; __finaldtb

STEM Skills Initiatives for Adolescent Girls in the LAC Region - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin Moss (EdTech Hub, 2022)
This report was produced in response to a request from the UNICEF country office of Argentina and presents a curated list of science, technology, engineering, and mathematics (STEM) skills initiatives for adolescent girls in the Latin American and Caribbean (LAC) region. It also provides an introduction to gender equality and background on the participation of women in STEM fields in the LAC region — as well as cross-cutting recommendations based on an analysis of a series of initiatives. Key words: STEM; Gender; Girls; LAC; Argentina; technology; Science An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sandboxes: My experience participating in the sandbox alpha - Kumasewera, Pilirani (EdTech Hub, 2020)
This is the third in this series about our sandboxes. If you haven’t already, read about our approach to experimentation and how we tested our sandbox strategy out in Malawi.
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Teacher Professional Development Programme Document - Universal Basic Education Commission

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Preservice Classroom Teachers' Views of Distance Education Science Laboratory Activities - Arslan, Ayten (International Online Journal of Education and Teaching, 2021)
This study investigated preservice classroom teachers' views of distance education science laboratory (lab) activities (DESLA). The study adopted a phenomenology design, which is a qualitative research method. The sample consisted of 34 students (25 women and nine men) from the department of classroom teaching of the education faculty of a public university. Participants were recruited using convenience sampling. Data were collected online (Google Forms) via Google Drive using an open-ended question form developed by the researcher based on a literature review and expert feedback. The data were analyzed using content analysis, a qualitative data analysis method. The results showed that participants had positive and negative opinions about DESLA. They had numerous academic, social, and professional experiences but also faced some challenges. They pointed out the pros and cons of DESLA. Most participants stated that they preferred face-to-face science lab activities to DESLA. The results also showed that DESLA improved participants' attitudes towards science lab activities in general.
Keywords: Barriers; COVID-19; Distance Education; Educational Technology; Foreign Countries; Pandemics; Preservice Teachers; Program Effectiveness; School Closing; Science Instruction; Science Laboratories; Student Attitudes; Technology Uses in Education; ⛔ No DOI found

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Case Studies; Computer Software; Cultural Context; ERIC, Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

EDUsummIT 2011 report from TWG3: teacher professional development - Twining, Peter; Albion, Peter; Knezek, Don (UNESCO, 2011)

National Plan for Teachers’ Continuous Professional Development (4a) - Tanzania Institute of Education (Tanzania Institute of Education, 2021)

Malawi Teacher Professional Development Support Program: Baseline Report - USAID (2011)

Introducing ICT into Teacher-Training Programs: Problems in Bangladesh - Khan, Shahadat Hossain; Hasan, Mahbub (Journal of Education and Practice, 2013)
Information and Communication Technology can offer more adaptable and efficient ways of teacher training for improvement of quality of professional development programs. But the use of ICT into teacher training usually faces certain obstacles. In this paper, we identified different barriers of introducing ICT into teacher training model (this model had been discussed by the authors in a separate paper, titled as “A model for integrating ICT into teacher training programs in Bangladesh based on TPCK) in Bangladesh, a developing country. We then described the strategies to overcome these problems for improving the current status of ICT integration into teacher training. Finally, we concluded with emerging research issues and offered pertinent recommendation with respect to ICT integration into teacher training program for improving quality of teaching in Bangladesh.
Keywords: ⛔ No DOI found

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

What professional development makes the most difference to teachers? - Walter, Catherine; Briggs, Jessica (University of Oxford Department of Education, 2012)

National Framework for Continuous Professional Development for Practicing Teachers - Ministry of Education, Science and Technology (United Republic of Tanzania, 2017)
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Using Digital Video in Rural Indian Schools: A Study of Teacher Development and Student Achievement - Sahni, Urvashi; Gupta, Rahul; Hull, Glynda; Javid, Paul; Setia, Tanuja; Toyama, Kentaro; Wang, Randy (Annual Meeting of the American Educational Research Association, 2008)
This research explores the deployment of model lessons through digital video as part of an in-service effort to engage teachers in government and private rural Indian schools and non-formal educational settings. Our mixed method design combined tests of skills in English and math with participant observation and videotaping of English and math instruction for 100 children in 3 rural schools and 1 non-formal setting over eight months. In this paper we present analyses of test score data and interactional patterns, followed by a qualitative examination of how one teacher appropriated pedagogical and subject matter knowledge from the model video lessons. Specifically, the data show gains in test scores of subject matter knowledge; children in classes that were part of the intervention scored almost 400% higher in English and almost 300% higher in math than did children in a comparison school. There were changes as well in classroom interactional patterns, suggesting that teachers became more student-centered in their approaches. The qualitative data illustrate how one teacher used and learned from the model lessons over time—for example, acquiring pedagogical strategies for interacting with the children and learning to connect classroom topics to the children’s local social worlds. Most generally, the data demonstrate how a network of teachers, schools, computer professionals, and teacher educators can reconfigure flows of information, tools, people, and texts, creating a band of geospatial opportunity within which the educational and social spaces of inhabitants of remote villages can be improved, allowing them hopeful entry to some of the advantages of a digital information age.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Using Digital Video in Rural Indian Schools: A Study of Teacher Development and Student Achievement - Sahni, Urvashi; Gupta, Rahul; Hull, Glynda; Javid, Paul; Setia, Tanuja; Toyama, Kentaro; Wang, Randy (2008)
This research explores the deployment of model lessons through digital video as part of an in-service effort to engage teachers in government and private rural Indian schools and non-formal educational settings. Our mixed method design combined tests of skills in English and math with participant observation and videotaping of English and math instruction for 100 children in 3 rural schools and 1 non-formal setting over eight months. In this paper we present analyses of test score data and interactional patterns, followed by a qualitative examination of how one teacher appropriated pedagogical and subject matter knowledge from the model video lessons. Specifically, the data show gains in test scores of subject matter knowledge; children in classes that were part of the intervention scored almost 400% higher in English and almost 300% higher in math than did children in a comparison school. There were changes as well in classroom interactional patterns, suggesting that teachers became more student-centered in their approaches. The qualitative data illustrate how one teacher used and learned from the model lessons over time—for example, acquiring pedagogical strategies for interacting with the children and learning to connect classroom topics to the children’s local social worlds. Most generally, the data demonstrate how a network of teachers, schools, computer professionals, and teacher educators can reconfigure flows of information, tools, people, and texts, creating a band of geospatial opportunity within which the educational and social spaces of inhabitants of remote villages can be improved, allowing them hopeful entry to some of the advantages of a digital information age.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Using Digital Video in Rural Indian Schools: A Study of Teacher Development and Student Achievement - Sahni, Urvashi; Gupta, Rahul; Hull, Glynda; Javid, Paul; Setia, Tanuja; Toyama, Kentaro; Wang, Randy (2008)
This research explores the deployment of model lessons through digital video as part of an in-service effort to engage teachers in government and private rural Indian schools and non-formal educational settings. Our mixed method design combined tests of skills in English and math with participant observation and videotaping of English and math instruction for 100 children in 3 rural schools and 1 non-formal setting over eight months. In this paper we present analyses of test score data and interactional patterns, followed by a qualitative examination of how one teacher appropriated pedagogical and subject matter knowledge from the model video lessons. Specifically, the data show gains in test scores of subject matter knowledge; children in classes that were part of the intervention scored almost 400% higher in English and almost 300% higher in math than did children in a comparison school. There were changes as well in classroom interactional patterns, suggesting that teachers became more student-centered in their approaches. The qualitative data illustrate how one teacher used and learned from the model lessons over time—for example, acquiring pedagogical strategies for interacting with the children and learning to connect classroom topics to the children’s local social worlds. Most generally, the data demonstrate how a network of teachers, schools, computer professionals, and teacher educators can reconfigure flows of information, tools, people, and texts, creating a band of geospatial opportunity within which the educational and social spaces of inhabitants of remote villages can be improved, allowing them hopeful entry to some of the advantages of a digital information age.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Exploring EFL teachers’ professional identity development in a CALL teacher preparation program - Meihami, Hussein; Esfandiari, Rajab (The JALT CALL Journal, 2021)

The Teachers’ Portal as a Tool for Teachers’ Professional Development in Bangladesh - Prime Minister's Office: Bangladesh (Access to Information Programme: Government of the People's Republic of Bangladesh; UNDP; USAID)

Using Technology to Train Teachers: Appropriate Uses of ICT for Teacher Professional Development in Developing Countries - Gaible, Edmond; Burns, Mary (World Bank, 2007)

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Teacher factors influencing classroom use of ICT in sub-Saharan Africa - Hennessy, Sara; Harrison, David; Wamakote, Leonard (Itupale Online Journal of African Studies, 2010)
This paper synthesises the research literature on teachers‟ use of Information and Communication Technology (ICT) in primary and secondary schools in sub-Saharan Africa, with a particular emphasis on improving the quality of subject teaching and learning. We focus on the internal factors of influence on teachers‟ use, or lack of use, of technology in the classroom. Our discussion attends to perceptions and beliefs about ICT and their motivating effects, technological literacy and confidence levels, pedagogical expertise related to technology use, and the role of teacher education. These factors are discussed in light of significant infrastructure and other external issues. We conclude by drawing out a number of pedagogical implications for initial teacher education and professional development to bring schooling within developing contexts into the 21 st century.
Keywords: Schools, Secondary; Scientific literature; ⛔ No DOI found

Reviewing the evidence on how teacher professional development affects student achievement - Yoon, Kwang Suk; Duncan, Teresa; Wen-yu Lee, Sylvia; Scarloss, Beth; Shapley, Kathy (Issues & Answers, 2007)
Keywords: C:United States

Identifying the characteristics of effective teacher professional development: a critical review - Sims, Sam; Fletcher-Wood, Harry (School Effectiveness and School Improvement, 2020)
Keywords: De-prioritise; ___working_potential_duplicate; ⚠️ Invalid DOI

Where it's needed the most: Quality professional development for all teachers - Burns, M.; Lawrie, J. (Inter-Agency Network for Education in Emergencies, 2015)

Reimagining Teacher Continuous Professional Development: Evidence from a Blended Approach in Senegal - Proudfoot, Diane; Pflepsen, Alison; Swift-Morgan, Jennifer; Niang, Ablaye (Chemonics International, 2022)

Professional Development for Teachers for Blended Learning and Online Strategies - Pilot Project - UNESCO (2020)

Reimagining Teacher Professional Development for Scalable, Sustainable and Equitable Outcomes - Using EdTech Research Evidence - Hennessy, Sara; Koomar, Saalim (Asian Development Bank 9th International Skills Forum: Reimagining Education and Skills Development for a New Normal, 2021)

Learning circles: creating conditions for professional development - Collay, Michelle (Corwin Press, 1998)
Keywords: Cooperativeness; Group work in education; In-service training; Teachers; Teaching; United States

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Keywords: Important; Read

The Patterns and Purposes of School-based and Cluster Teacher Professional Development Programs - Leu, ELizabeth (USAID/EQUIP1, 2004)

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Keywords: Important; Read

Feasibility of a mobile phone training on autism spectrum disorders for teachers in Tanzania - Martino, Daniele C.; Naqvi, Nilofer C. (Technology, Pedagogy and Education, 2023)
Despite the rising global prevalence of autism spectrum disorders (ASD), significant disparities in ASD knowledge persist worldwide. Professional development trainings are effective in increasing teacher knowledge of ASD; however, in-person trainings pose accessibility concerns for teachers in low- and middle-income countries. In sub-Saharan Africa, few teacher development opportunities exist and logistical barriers limit attendance, highlighting the need for a more accessible training modality. The present study used a pre-post-test methodology among general and special education teachers in urban Tanzania to evaluate the feasibility of a mobile phone-delivered training on ASD. Results indicated a robust 84% participation rate and high quiz scores across training modules. The benefits of using mobile phone technology in a low-resource setting are presented. As the first asynchronous ASD training developed and implemented among teachers in Tanzania, this study can guide future research that explores how best to increase ASD knowledge among community members using technology.

A Professional Development Program for the Mother Tongue-Based Teacher: Addressing Teacher Perceptions and Attitudes Towards MTBMLE - Stone, Rebecca J Paulson (University of Massachusetts Amherst, 2012)

Effects of an Early Literacy Professional Development Intervention on Head Start Teachers and Children - Powell, Douglas; Diamond, Karen; Burchinal, Margaret (Journal of Educational Psychology, 2010)

Teachers’ professional development through integrating ICT in English language education: A case from Pakistan - Bashiruddin, Ayesha
Keywords: ⛔ No DOI found

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Teachers Co-creating for Teachers: Design and Implementation of an Online Teacher Professional Development Course in Sub-Saharan Africa - Negeze, Lucian Vumilia; Iyer, Sridhar (Global Perspectives on Educational Innovations for Emergency Situations, 2022)

WhatsApp: Creating a virtual teacher community for supporting and monitoring after a professional development programme - Moodley, Maglin (South African Journal of Education, 2019)

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/

Teachers in Tatweer Primary Schools in Saudi Arabia and Interactive White Boards: Towards a Professional Development Model - Alghamdi, Azzah Hamed (Durham University, 2018)

Technology use in teacher preparation and professional development in low-and middle-income countries - UNESCO Digital Library - Hennessy, Sara; D'Angelo, Sophia; Koomar, Saalim; Kreimeia, Adam; Adam, Taskeen; Cao, Lydia; Haßler, Björn (Global Education Monitoring Report 2023: Background paper, 2023)

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

An Exploration of China-Africa Cooperation in Higher Education: Opportunities and Challenges in Open Distance Learning - Zhu, Xia; Chikwa, Gladson (Open Praxis, 2021)
Cognisant of the wide range of cooperation between China and Africa and the existing strong Sino-African relationship, this article explores the international cooperation between Africa and China in the higher education domain, especially in the field of Open Distance Learning (ODL). The study employed data triangulation relying on both secondary and primary sources to address the main research questions. It sheds light on the development of ODL in Chinese Higher Education Institutions (HEIs) with a focus on professional development of university teachers. The article argues that ODL is crucial for emerging economies' sustainable development. Key factors such as political, technological and socio-cultural features play a crucial role in the development and effective implementation of ODL. By exploring the potential opportunities and identifying related challenges, this article contributes to an understanding of how mutually beneficial partnerships between African universities and Chinese HEIs can be developed within the wider framework of Sino-African relationship.
Keywords: Distance Education; Educational Development; Educational Technology; Faculty Development; Foreign Countries; Higher Education; International Cooperation; Lifelong Learning; Open Education; Partnerships in Education; Sustainable Development

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

What do specialists do in CPD programmes for which there is evidence of positive outcomes for pupils and teachers? - Cordingley, Philippa; Bell, Miranda; Isham, Colin; Evans, Donald; Firth, Antonia (Research Evidence in Education Library, 2007)
What do we want to know? This review aims to explore and describe the role of the specialist in CPD programmes that provide evidence of positive outcomes for pupils as well as teachers within a broad range of indicators, including (for pupils) achievement, attainment, motivation and attitudes; and (for teachers) behaviours, knowledge, understanding and a range of affective outcomes, such as beliefs, attitudes and motivation. Who wants to know and why? The issue of how best to support teachers in their CPD is of interest to teachers, professional associations and agencies responsible for the quality and provision of teacher training. What did we find? • We only found studies where the ‘results’ indicated a positive impact of CPD. Most of the ‘evaluations’ were designed and conducted by the specialists themselves using research approaches with limited capacity to control for the potential biases arising from such a situation. • Pupil impact data was reported in the areas of learning and achievement, and affective development, including attitudes to learning and self-esteem. • Changes in teacher practice resulted from teachers learning more about teaching strategies, learning theories, the use of technology, educational policy and subject knowledge. • Specialists supported teachers through modelling, workshops, observation, feedback, coaching, and planned and informal meetings for discussion. Nearly all specialist support took place on school premises. More than half the CPD involved the specialists in observing teachers and providing feedback and debriefing. They discussed pupil needs, examined test results, reviewed the results of interviews conducted with and by pupils, and observed pupil interaction in the classroom. The quantity of formal ‘input’ was extensive and sustained. • Peer support was a consistent feature. • Specialists encouraged teachers to take on a degree of leadership in their CPD. What are the implications? The limitations of the evidence reviewed mean that we are cautious about putting forward any definitive interpretation of the implications of this review for the practices of specialist CPD. It is clear that we need more rigorous independent evaluation of CPD initiatives. The review evidence highlighted an intensive pattern of support in terms of the variety of skills specialists brought with them, and the amount of time they spent on input and support. This suggests we need to develop a more sophisticated approach to identifying, developing and drawing on the knowledge and skills both of professionals within school, and across networks, so that capacity can be built based on existing resources. More specifically, the review suggests the need for professional development for lead practitioners and CPD leaders to develop specific, specialist knowledge, understanding and skills related to adult professional learning. How did we get these results? The Review Group screened over 3,000 titles and abstracts, from which 239 studies reporting the impact and processes of CPD which involved specialists were identified. Scrutiny of the full reports led to a final sample of 22 studies for in-depth review. All these studies contained teacher and pupil data. Nineteen studies with overall medium or high weight of evidence were used to create a synthesis of findings.

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

The effects of continuing professional development (CPD) though SPRINT on teacher classroom practices and student learning outcomes. In Collaboration toward Greater Autonomy in Educational Development - Mubanga, R (2012)

The Use of Video in Teacher Professional Development Design, Implementation and Impact Evaluation of an Innovative In-service Course for Mathematics Teachers in Indonesia - Ragatz, Andrew B.; Sugiarti, Susie; Iskandar, Susiana (World Bank, 2015)

A Professional Development Study of Technology Education in Secondary Science Teaching in Benin: Issues of Teacher Change and Self-Efficacy Beliefs - Kelani, Razacki Raphael (2009)

(PDF) Pedagogic change by Zambian primary school teachers participating in the OERS4Schools professional development programme for one year | Sara Hennessy - Academia.edu

Access, use and perceptions of teachers and students towards mobile phones as a tool for teaching and learning in Tanzania - Kafyulilo, Ayoub (Education and Information Technologies, 2014)
This study explored the access, use and perceptions of teachers and students towards mobile phones as a tool for facilitating teaching and learning beyond the classroom walls. A total of 29 pre-service teachers and four college instructors from Dar es salaam University College of Education (DUCE) as well as 12 in-service teachers and 40 students from Kibasila secondary school in Tanzania, participated in the study. Data were collected by using pre-service teachers’ questionnaire, students’ questionnaire, and the instructors’, and in-service teachers’ interviews. Findings showed that all in-service teachers, college instructors and pre-service teachers had mobile phones. Also 60 % of school students owned mobile phones, or had access to mobile phones. Students, pre-service teachers and college instructors were in favour of the use of mobile phones for learning, but the majority of in-service teachers were against it. Since mobile phones are the most available technological tools in schools, this study, recommend a professional development programme for in-service teachers to help them develop a positive attitude towards mobile phones use in teaching and learning.

The Impact of Teachers Professional Development in Video Technology on Mathematics and English Learning of Preschoolers in a Rural Primary School in Pakistan - Ikram, Hamid (International Journal for Digital Society, 2015)
Learning media technologies are common and affordable tools in preschools for teaching and learning purposes. Unfortunately, many young children from low socio-economic communities do not have challenging and stimulating learning environment as compared to their advantaged peers.

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Moving towards more participatory practice with Open Educational Resources (OER): TESS-India Academic Review - Wolfenden, Freda; Adinolfi, Lina; Cross, Simon; Lee, Clare; Paranjpe, Sandhya; Safford, Kimberly (The Open University, 2017)
The purpose of this academic review of TESS-India activity in three states (Bihar, Madhya Pradesh and Odisha) was to seek evidence for change brought about by TESS-India in teacher education in each of these states. The findings offer informed guidance on future trajectories for TESS-India activity and support discussions with key stakeholders in each of these states. The overarching goal of TESS-India is to support delivery of quality pedagogic change in teacher education and school classrooms. TESS-India activity is designed to meet identified professional development needs of teachers and teacher educators in each state. Thus it takes a slightly different form in each state, appropriate to local priorities and conditions. The Review focus was similarly differentiated in each state to align to TESS-India activity in that state. The review field work was carried out by academics from the Open University UK and the Head Academic, TESS-India Country Office, between 30 January and 4 February 2017. It adopted an essentially qualitative approach to understand educators’ (trainee teachers, teachers, local teacher educators and DIET faculty) experiences with the TESS-India resources and the influence of this engagement on their pedagogic practice. Data was generated from multiple sources including analysis of key documentation, semi-structured interviews with teachers, teacher educators and policy makers, and classroom observation. Teachers, teacher educators and SRG members were sampled at different locations within each state. The focus of TESS-India activity to date has been to strengthen the existing government (state) educational system at the elementary stage - SCERT, SSA, DIETS, DEO, DPC (SSA), BEO, BRP, BRC, CRCC, HT, Teacher, Child – in alignment with national policies, frameworks and the RTE Act. The project aims at supplementing and complementing GoI and State specific efforts and activities. Although TESS-India has produced original Open Educational Resources (OER) to support educators working in the secondary stage, as yet there is very little evidence of sustained TESS-India activity with this phase of schooling or with the TESS-India School Leader OER. The review findings are therefore focussed on activity at the elementary stage and are reported at different levels of the system in line with the TESS-India theory of change. The report found that use of TESS-India OER is contributing to quality change in classrooms with students and trainee teachers. • SRG members met by the review team were using the TESS-India OER and described how this use was prompting them to experiment with more interactive and participatory practices. • Teachers observed and / or interviewed by the review team were drawing on TESS-India OER to inform their lesson planning and subsequent teaching. Evidence seen by the review team (learning journals and learning plans) indicates that the practices being developed by these teachers are shared by other teachers in the cohort of teachers participating in TESS-India focus district activity. However the innovation in practice and transformation in pedagogy promised by TESS-India OER is still in the early stages and the evidence is highly emergent. But, critically, through engagement with the MOOC and other TESS-India learning resources, policy makers and lead teacher educators (for example SCERT Directors) are changing their thinking about teacher professional development, moving away from cascade models to a focus on continuous professional development and learning of teachers in their classrooms with support from teacher educators/ experts, either virtually or face-to face.
Keywords: C: India; __:import:01; __:match:final; __:matched; __:study_id:2457359; __finaldtb

Using video to support in-service teacher professional development: the state of the field, limitations and possibilities: Technology, Pedagogy and Education: Vol 27, No 1

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Resilient by Design: Ukraine’s EdTech Emergency Response. A qualitative study - Bhatt, Margi; Radford, Kate (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

A Comparative Study of Online and Directly Selected Secondary School Teachers Regarding Teaching Proficiency and Classroom Management in Kohat Division, Pakistan - Suleman, Qaiser; Hussain, Ishtiaq (International Journal of Learning and Development, 2013)
Secondary school teachers occupy the most critical and crucial position in the entire education system (Suleman, et al, 2011a). The purpose of the study was to compare the performance of online and directly selected secondary school teachers regarding teaching proficiency and classroom Management. All the students at secondary school level in Kohat Division, Khyber Pakhtunkhwa (Pakistan) constituted the population of the study. Only 600 students studying at secondary school level in Kohat Division were selected as sample randomly. The study was delimited to only male students at secondary school level. The study was descriptive type and questionnaire was used as research instrument. Data was collected through personal visits. After the collection of data, it was organized, tabulated, analyzed and interpreted. The statistical tools i.e. means, standard deviation and differences of means were computed for each variable. Significance of difference between the mean values of the responses of students about online and directlly selected secondary school teachers were tested at 0.05 levels by applying t-test. After statisitcal analysis of the data, the researchers conclduded that the overall performance of the directly selected secondary school teachers was better and satisfactory. They were found to have the knowledge of teaching methods and the ability to control classroom disruptive behaviour. Conversely, the overall performance of the online selected secondary school teachers was poor and unsatisfactory. They have no knowledge of teaching methodologies and subject mastery. They were found unable to manage classroom disruptive behaviour and other related activities. Based on findings, it was strongly recommended that a special professional training programme should be arranged to the existing online selected SSTs in teaching methodologies and classroom management to equip them with the modern teaching methods and techniques of managing classroom behaviour so that they become able to perform their duties effectively.

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Understanding factors affecting primary school teachers’ use of ICT for student-centered education in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Takada, Jun-ichi (2018)
The past two decades witnessed continuous uptake of ICT in education, and the importance of teachers’ beliefs for adopting ICT in education was revealed in the context of educational change. In recent years, the Mongolian educational system has placed more emphasis on student-centered education and the use of ICT in teaching and learning. Teacher training has become a local responsibility under the Education Master Plan (Government of Mongolia, 2006), New Education Standard and Core Curriculum which focus on the introduction of ICT into education and the implementation of student-centered education (Asian Development Bank, 2008; Ministry of Culture Education and Science, 2014). Despite the growing interest in using ICT for student-centered education, a limited number of studies exist in Mongolia to understand primary school teachers’ perception on use of ICT for student-centered education. This study aims to understand the factors affecting teachers’ perceptions on use of ICT for student-centered education. Based on Fullan’s educational change theory, the analysis through multiple linear regression and focus group discussion was conducted on 838 primary school teachers in Mongolia which found that teacher’s professional competency and perceived benefits on use of ICT are significant factors affecting teachers’ perceptions on use of ICT tool for student-centered education. Furthermore, teacher’s professional competency, perceived benefits on use of ICT and teacher cooperation are affecting teachers’ perceptions on use of digital contents for student-centered education.
Keywords: ⛔ No DOI found

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Emergency remote teaching during COVID19: The role of teachers’ online community of practice (CoP) in times of crisis - Ulla, Mark B.; Perales, William F. (Journal of Interactive Media in Education, 2021)
While previous studies in the literature may have used the concept of a community of practice (CoP) to investigate its role for teachers’ professional development, this study identifies the role of a teachers’ CoP in navigating the challenges in online/remote teaching faced by six teachers of English as a foreign language (EFL) in a university in Thailand during the COVID19 pandemic. This study employed a purposive-convenience sampling method with an individual online interview to gather qualitative data. Findings revealed that although teacher-participants pointed out the lack of students’ interaction, lack of time to do assessment and feedback, and the lack of students’ concentration in online teaching, they greatly acknowledged the role of the teachers’ CoP in navigating the demands and challenges of online teaching during the pandemic. Some of the ascribed roles of the teachers’ CoP in online teaching include; a support group, a source of solutions to online teaching issues, and a learning community. Implications are discussed and suggestions for future studies are offered.

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Use ICT to provide access to content, professional development and professional learning communities (Recommendation 7) - Lawrie, J.; Hennessy, S.; Haßler, Björn; Phalachandra (Where it's needed most: quality professional development for all teachers, 2015)
Keywords: C:Fragile contexts; docs.opendeved.net

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Supporting Change in Literacy Instruction in Malawi - Sailors, Misty; Hoffman, James V.; Pearson, P. David; McClung, Nicola; Shin, Jaran; Phiri, Liveness Mwale; Saka, Tionge (Reading Research Quarterly, 2014)
In this study, we examined the effectiveness of an innovative approach to literacy instruction in Malawi on teachers' perceptions, attitudes, and instructional practices. Two groups participated in the study: Treatment teachers received complementary teaching and learning materials, workshops, and directive coaching, and control teachers received no intervention. After this five-month intervention, treatment teachers were significantly more comfortable with their languages of instruction and were more positive about their teaching ability, beliefs about the learning materials in their classroom, and beliefs about the culture of reading in their communities than control teachers were. There were no significant differences between groups when we analyzed their teaching practices or the engagement of their students. The coaching model proved to be associated with changes in teachers' beliefs and perceptions on many of our variables. These findings suggest that the program under examination was successful in promoting the conditions for success (teacher beliefs and perceptions). Further, the findings suggest that the implementation of coaching was an important source of support in implementing changes.
Keywords: Adult; C:Malawi; Childhood; Coaching; Decoding; Discussion; Early childhood; English as a second language; English for speakers of other languages; English language learners; English learners; Experimental; Fairy tales; Family literacy; Home language; Home-school connections; In-service; Instructional models; Language learners; Literature; Literature-based instruction; Oral language; Parental involvement; Phonics; Program evaluation; Reading strategies; Research methodology; School based; Sight words; Sociocultural; Socioeconomic factors; Strategies; Supplementary resources; Teacher education; Textbooks; and materials; folk tales; methods; phonemic awareness; phonological awareness; professional development; quasi-experimental; word recognition

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Remote Learning: Rapid Evidence Assessment - Education Endowment Foundation (Education Endowment Foundation, 2020)
This rapid evidence assessment aimed to investigate methods that schools could use to support remote learning during school closures caused by the 2020 coronavirus pandemic (Covid-19). The review sought to find the best evidence behind the wide array of approaches that schools might choose to use during the crisis. The review systematically searched for/through existing meta-analyses and systematic reviews to find the best evidence for a wide range of approaches. In addition to the direct teaching of pupils online by teachers, the review also found evidence for approaches that pupils can use independently, including with technology that adapts the content of tasks in order to provide additional challenge or support, educational games, and for approaches that support peer interaction. The review also examined blended learning approaches, which combine remote and classroom teaching. While these approaches may not be directly applicable during school closures, they were included in case there were useful lessons to be learned that were relevant to the current context of home learning. This report summarises the findings from 60 systematic reviews and meta-analyses answers under five key topic areas: - General remote teaching and learning - Blended learning - Computer-supported collaborative learning - Computer assisted instruction - Educational games Another crucial aspect of supporting pupil’s learning is parental engagement. Parental engagement approaches are beyond the scope of this review, but an existing EEF guidance report, Working with Parents to Support Children’s Learning (2019), and accompanying evidence review summarise the best available evidence for engaging parents in their children’s education. In each section, we have detailed the included reviews and listed Findings and implications drawn from the evidence. We have also highlighted case studies from projects funded by the Education Endowment Foundation in which similar approaches have been rigorously evaluated in English schools.
Keywords: Methods; _DOILIVE; _EdTechHub_Output; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Online and distance teaching and learning A32ARSFK; _cover:other:ok; _zenodo:submitted; _zenodoETH

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

Jordan’s EdTech response to COVID-19 - Al-Hindawi, Hind; Hashem, Lina (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Conseils pour l’introduction de la technologie en classe Liste de sources annotée - Allier-Gagneur, Zoé; Lwamba, Etienne (EdTech Hub, 2020)
Cette liste de sources annotée a pour but d’informer la prise de décisions des acteurs du domaine de l’éducation concernant l’introduction de technologies en classe dans les pays à revenu faible et intermédiaire. Cette liste est une introduction qui expose de façon informelle certains des conseils généraux que prodiguent souvent les experts de l’EdTech Hub.
Keywords: F: Helpdesk response; LP: French; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Mahruf, C.; Shohel, M.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted instruction; COMPUTERS in education; CONTINUING education; DEVELOPING countries; EDUCATIONAL technology; INFORMATION technology; PROFESSIONAL education; SECONDARY school teachers; TEACHER development; TEACHERS -- In-service training; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096535; __finaldtb; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Survey of the Use of Assistive Technology in Schools in Nigeria - Ajuwon, Paul M.; Chitiyo, George (Journal of the International Association of Special Education, 2015)
In this study, the researchers explored the state of the use of assistive technology (AT) in Nigeria through a survey of 165 special educators. The underlying structure of the respondents' perceptions, and their challenges and barriers to the use of AT, were examined. Among other findings, the largest proportion of students using AT are those with deafness or hearing impairment (53.3%), followed by those with a learning disability (40%). Training in the use of AT lags behind, with most professionals having received little or no training in the use of AT. The lack of appropriate AT devices and services in classrooms, and irregular electricity to operate available devices, were frequently cited as the biggest challenges regarding AT. Correlations between students' conditions and factors of teachers' perceptions suggested the need to make AT available for students with certain conditions, as well as the need for effective training for teachers.
Keywords: Access to Computers; Assistive Technology; Barriers; Computer Uses in Education; Deafness; Disabilities; Educational Technology; Energy; Faculty Development; Foreign Countries; Hearing Impairments; Learning Disabilities; Likert Scales; Special Education Teachers; Statistical Analysis; Teacher Competencies; Teacher Surveys; Technological Literacy; Training; ⛔ No DOI found

Using instructional video to improve awareness of scientific approach in science classroom - Susantini, Endang; Faizah, Ulfi; Yonata, Bertha; Kurniasari, Ika; Suryanti (Asia-Pacific Forum on Science Learning and Teaching, 2018)
Instructional videos have been developed to engage pre-service teachers to learn how to teach scientific approach in science classroom. This study aimed to improve preservice teachers' awareness of scientific approach in science classroom through instructional video along with their responses. Thirty two pre-service science teachers from Universitas Negeri Surabaya, Surabaya, Indonesia, participated in this study and observed two different instructional videos using video-analysis worksheet supplemented by the supervisor. In response to the instructional video, results showed that pre-service teachers noticed well about application of scientific approach in inquiry-based teaching and cooperative learning models. Pre-service teachers also showed positive views about the instructional videos and became a reflection for their own future teaching actions and practices. Supplementation of the video-analysis worksheet during the implementation and peer-discussion among preservice teachers can be used to improve pre-service teachers' awareness as well as to provide clear exemplary about how to integrate scientific approach at each phase of inquiry-based teaching and cooperative learning models. This study implies that the present instructional videos and followed-up video-analysis task are adequate to facilitate pre-service teachers to understand what to do in actual classroom in terms of applying scientific approach as envisioned by Indonesia curriculum reform.
Keywords: Active Learning; Biology; Chemistry; Classrooms; Cooperative Learning; Cooperative learning; Curricula; ERIC, Current Index to Journals in Education (CIJE); Educational technology; Foreign Countries; Higher Education; Hypotheses; Indonesia; Inquiry; Inquiry method; Instructional Material Evaluation; Mathematics; Models; Pedagogy; Preservice Teacher Education; Preservice Teachers; Professional development; Science Instruction; Science Teachers; Science education; Sciences: Comprehensive Works; Scientific Methodology; Student Attitudes; Students; Teacher education; Teaching Methods; Teaching methods; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2097317; __finaldtb; ⚠️ Invalid DOI; ⛔ No DOI found

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Sandboxes: our approach to systemic experimentation - Simpson, Lea (EdTech Hub, 2020)
What’s a sandbox you ask? First in the series, this blog explains what you need to know about the Hub’s approach to experimentation and innovation.
Keywords: F:Sandbox; LP: English; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Rachel Chuang, Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.

National EdTech strategies: what, why, and who - Chuang, Rachel; Coflan, Caitlin; Giraldo (UNICEF), Juan-Pablo; Attfield (FCDO), Ian; Tungatarova (UNICEF), Auken; Tungatarova (UNICEF), Rachel Chuang, Caitlin Coflan, Juan-Pablo Giraldo (UNICEF), Ian Attfield (FCDO) and Auken (EdTech Hub, 2022)
Using evidence from Covid responses, the report advises policymakers responding to learning loss caused by the pandemic to use existing EdTech, and focus on good pedagogy that is supported, rather than replaced by, technology.

Guidance on Facilitation of E-Learning - Dzinotyiweyi, Monica; Chuang, Rachel; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
Keywords: F: Helpdesk response; _r:AddedByZotZen

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
Keywords: _r:AddedByMyEducationEvidence

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Mentorship Community of Practice - FHI360 (2020)
The Rwanda Mentorship Community of Practice (MCOP) initiative, funded by the U.S. Agency for International Development, aims to strengthen the quality of basic education and to support teacher professional development across Rwanda. The overall objective of MCOP is to improve pedagogical and subject knowledge, particularly for early-grade reading, through the effective use of technologies in in-service professional development.

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Are LLMs useful in the poorest schools? TheTeacher.AI in Sierra Leone - Choi, Jun Ho; Garrod, Oliver; Atherton, Paul; Joyce-Gibbons, Andrew; Mason-Sesay, Miriam; Björkegren, Daniel (arXiv, 2024)
Education systems in developing countries have few resources to serve large, poor populations. How might generative AI integrate into classrooms? This paper introduces an AI chatbot designed to assist teachers in Sierra Leone with professional development to improve their instruction. We describe initial findings from early implementation across 122 schools and 193 teachers, and analyze its use with qualitative observations and by analyzing queries. Teachers use the system for lesson planning, classroom management, and subject matter. Usage is sustained over the school year, and a subset of teachers use the system more regularly. We draw conclusions from these findings about how generative AI systems can be integrated into school systems in low income countries.
Keywords: Computer Science - Computers and Society

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found

Mobile solution for better reading instruction in rural Africa - Ojanen, Emma; Jere-Folotiya, Jacqueline; Yalukanda, Christopher; Sampa, Francis; Nshimbi, Chomba; Katongo, Maggie; Choopa, Mapenzi; Lyytinen, Heikki (2015 IST-Africa Conference, 2015)
GraphoGame Teacher Training Service is a mobile-based solution for providing teachers with scientifically validated pedagogical training in literacy instruction. In many African countries teachers currently have insufficient knowledge to teach literacy in local languages and learning materials are scarce, especially for children with learning difficulties. As part of the GraphoWorld network, CAPOLSA/University of Zambia is developing new mobile-based method for providing in-service training for teachers in literacy instruction and assisting children with learning difficulties. GraphoGame Teacher Training Service was piloted in October 2014 in rural Zambia. An orientative workshop was given to 24 teachers who learned about literacy instruction methodology and then organized a GraphoGame intervention to randomly selected 2nd grade children either at home or in a school environment. Parents of the children in the home intervention group were also encouraged to play GraphoGame. GraphoGame learning analytics shows that both the children and their parents improved their word reading skills. Children who played GraphoGame performed better than their non-playing classmates in the EGRA letter-sound knowledge test at the end of the intervention. Teachers, parents and children were all motivated to use ICT-based literacy learning tools and their literacy skills levels show high demand for support services for literacy instruction.
Keywords: Africa; African country teachers; CAPOLSA/University of Zambia; Conferences; EGRA letter-sound knowledge test; Electronic learning; Games; GraphoGame; GraphoGame learning analytics; GraphoGame teacher training service; GraphoWorld network; ICT-based literacy learning tools; Mobile handsets; Training; Zambia; computer games; educational institutions; home environment; home intervention group; in-service teacher training; information science education; learning materials; literacy; literacy instruction; literacy skills levels; local languages; mobile learning; mobile-based method; orientative workshop; professional aspects; reading instruction; rural Africa; rural Zambia; rural areas; school environment; scientifically validated pedagogical training; teacher training; word reading skills

USAID Partnership for Education - USAID (Global Reading Network, 2020)
The USAID Ghana Partnership for Education: Learning activity developed a phonics-based reading program that will provide evidence-based tools and strategies for improving reading performance in 100 districts in Ghana, reaching approximately 1.1 million primary students. This brochure provides an overview of Learning’s approach, which includes teacher professional development models, methods for scaling up, a model for primary mathematics, a rigorous monitoring and support system and a learning-by-doing approach to capacity development. The brochure also highlights strong results from a prototype of the program conducted in the Dagbani language.

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

English language teaching in Bangladesh today: Issues, outcomes and implications - Rahman, Mohammad Mosiur; Islam, Md Shaiful; Karim, Abdul; Chowdhury, Takad Ahmed; Rahman, Muhammad Mushfiqur; Seraj, Prodhan Mahbub Ibna; Singh, Manjet Kaur Mehar (Language Testing in Asia, 2019)
Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum, method, and materials in Bangladesh; validity of the current assessment and its washback effect on English language teaching in Bangladesh; and current situation of teachers’ professional development. The article concluded with language policy and planning implications for policymakers, curriculum and material developers, public exams’ test-setters, and future English teacher training programmes, keeping the overall development of ELT in Bangladesh in mind.

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Evaluations of situational judgement tests to assess non-academic attributes in selection - Patterson, Fiona; Ashworth, Victoria; Zibarras, Lara; Coan, Philippa; Kerrin, Maire; O’Neill, Paul (Medical Education, 2012)
Medical Education 2012: 46: 850–868 Objectives This paper presents a systematic review of the emerging international research evidence for the use of situational judgement tests (SJTs) for testing important non-academic attributes (such as empathy, integrity and resilience) in selection processes. Methods Several databases (e.g. MEDLINE, PsycINFO, Web of Science) were searched to retrieve empirical studies relating to SJTs published between 1990 and 2010. Personal contact with experts in the field was made to identify any unpublished research or work in progress to obtain the most current material. Finally, reference lists were checked to access other relevant journal articles and further research. All research studies were required to meet specific inclusion criteria selected by two independent reviewers. Results Over 1000 citations were identified during the initial literature search; following the review of abstracts, full-text copies of 76 articles were retrieved and evaluated. A total of 39 articles that adequately met the inclusion criteria were included in the final review. The research evidence shows that, compared with personality and IQ tests, SJTs have good levels of reliability, predictive validity and incremental validity for testing a range of professional attributes, such as empathy and integrity. Conclusions SJTs can be designed to test a broad range of non-academic constructs depending on the selection context. As a relatively low-fidelity assessment, SJTs are a cost-efficient methodology compared with high-fidelity assessments of non-academic attributes, such as those used in objective structured clinical examinations. In general, SJTs are found to demonstrate less adverse impact than IQ tests and are positively received by candidates. Further research is required to explore theoretical developments and the underlying construct validity of SJTs.

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Why the World Needs a Curriculum Alignment Hub - Chandra, Shivi (Learning Equality, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

What does the research suggest is best practice in pedagogy for remote teaching? - McAleavy, Tony; Gorgen, Kristine (2020)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

M-learn lessons learnt: Bangladesh perspective - Imam, Zaki (QScience Proceedings, 2013)
M-learning is a form of distance learning in that it provides a communication tool( the mobile phone) to bridge the distance between the providing institution and the learners and facilitates 2-way (synchronous and asynchronous) interactivity between teacher and the learner (McWilliams et al, 2007). M-learning allows the remote teachers to stay in frequent contact with teacher educators, to ask questions and discuss issues as they adapt new teaching practices. This programme has been initiated by Ministry of Education upon requested by ADB, Manila to implement technology based training programme for reaching remote and disadvantaged areas. M learning has been piloted by teacher educators of Government Teachers’ Training College in one district (Barisal, located in the southern part of Bangladesh) and later extended to four districts to train teachers of remote schools of Patuakhali, Sandwip, Hatya and Thakurgaon districts. Regular 14 day and 5 day follow-up face-to-face inservice Continuing Professional Development (CPD) training was adapted as a two day face-to-face orientation, followed by a 6 week programme with regular conference calls to support classroom practices. Findings of the programme are very promising for adapting new practices. The CPD training by using mobile phone became very successful for increasing teachers and student’s competence level. Government of Bangladesh and Development Partners are very keen to maximize the use of technology in CPD for teachers especially for addressing female teachers and reaching training facilities to remote areas.

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.

Evaluating the Implementation Fidelity of Technology Immersion and its Relationship with Student Achievement - Shapley, Kelly S.; Sheehan, Daniel; Maloney, Catherine; Caranikas-Walker, Fanny (The Journal of Technology, Learning and Assessment, 2010)
In a pilot study of the Technology Immersion model, high-need middle schools were “immersed” in technology by providing a laptop for each student and teacher, wireless Internet access, curricular and assessment resources, professional development, and technical and pedagogical support. This article examines the fidelity of model implementation and associations between implementation indicators and student achievement. Results across three years for 21 immersion schools show that the average levels of school support for Technology Immersion and teachers’ Classroom Immersion increased slightly, while the level of Student Access and Use declined. Implementation quality varied across schools and classrooms, with a quarter or less of schools and core-content classrooms reaching substantial implementation. Using hierarchical linear modeling, we found that teacher-level implementation components (Immersion Support, Classroom Immersion) were inconsistent and mostly not statistically significant predictors of student achievement, whereas students’ use of laptops outside of school for homework and learning games was the strongest implementation mediator of achievement.
Keywords: ⛔ No DOI found

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the COVID-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion, and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.

Interactive White Boards in Preschool and Primary Education - Drigas, Athanasios; Papanastasiou, George (International Journal of Online and Biomedical Engineering (iJOE), 2014)
Technologies within the domain of interactive, remote and on line science which are extensively adopted in education’s everyday life are interactive whiteboards and related applications. Interactive whiteboards indicate positive effects on students’ learning and instructors' teaching, promoting whole class teaching. In this review-paper we cope with the studies that explore the integration of IWBs in preschool and primary education in the last decade (2004-2013). Research has shown that interactive whiteboards are able to keep students involved and foster their attention in every aspect of the curriculum, much easier than without it. This technology has proven its value added to students and teachers in different facets of teaching and learning, in literacy, in mathematics, in science, in physics, its impact on English Language Learners, on relations and learning, on the use of IWBs by kindergartners, professional development of teachers, pedagogical orchestration, classroom dialogue and pedagogic practice.
Keywords: IWB; collaboration; e-learning; e-teaching; interactive; multimodal teaching

Factors determining digital divide in Ghana's basic schools - Quaicoe, James Sunney; Pata, Kai (2015 IST-Africa Conference, 2015)
This paper explores the concept of digital divide (DD) in Ghana’s basic schools in Sekondi-Takoradi Metropolis in Western Region. We tested the ICT culture variables as well as school location factor in respect to school’s digital divide. A survey sample contained 17 regional city schools from three different locations – central city in the region, towns away from the central city, and village schools. The survey instrument was developed with ten ICT culture variables. The variables in the instrument met the Cronbach’s Alpha threshold value of α = 0.70. Data was analysed with Descriptive statistics, Hierarchical Cluster analysis, Independent t-test, and Canonical discriminant analysis. We found that school location did not determine the schools DD, nonetheless the schools were digitally divided, – 2 clusters were found among schools. This DD was determined by certain ICT culture variables: Teacher’s ICT competences and the usage of ICT in Teacher’s professional practice were paramount.

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

What-are-countries-that-already-use-remote-learning-doing-and-what-can-we-learn-from-them-EdTechHub.pdf

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Analysis of emergency remote teaching in formal education: Crosschecking three contemporary techno-pedagogical frameworks - Kasperski, Ronen; Porat, Erez; Blau, Ina (Research in Learning Technology, 2023)
During the COVID-19 pandemic outbreak many countries around the world were forced to turn to Emergency Remote Teaching (ERT) and upscale the use of digital technologies for learning, teaching and assessment. The current study analysed field reports from 89 elementary and secondary Hebrew-speaking and Arabic-speaking information and communication technology schools in Israel, representing the cultural, ethnic, and religious diversity of the education system. The qualitative analysis of the collected data was based on three well established contemporary models of technology integration and Digital Competence of Educators (DigCompEdu): the International Society for Technology in Education, Technological Pedagogical Content Knowledge and DigCompEdu. The analysis (n = 872 statements) yielded aspects in the teachers’ reports that correspond with the theoretical models, alongside aspects that extend these models to ERT and aspects that were missing from the reports. Finally, based on our findings and previous work we suggested a comprehensive framework for ERT that can be used to design teachers’ professional development necessary for effective remote teaching in both emergency and routine times.
Keywords: COVID-19 pandemic; digital pedagogy; e-learning; emergency remote teaching; information and communication technology; online learning

Evaluating Pre-Service Teaching Practice for Online and Distance Education Students in Pakistan: Evaluation of Teaching Practice - Ahmed Abdullah, Nauman; Sultana Mirza, Munawar (International review of research in open and distance learning, 2020)
In addition to conventional modes, teacher education programs in Pakistan are also offered through online and distance education. Teaching practice is a significant component of pre-service teacher education programs. Assessing the quality of teaching practice for pre-service student teachers is important, as these modules train the prospective teachers for their professional teaching careers. Virtual University of Pakistan (VU), an online university, offers pre-service teacher education programs. This research is an investigation into the learning opportunities and practices of VU student teachers in their teaching practice modules. Students enrolled in different teacher education programs served as the population of this study. Those in the fall 2018 semester who were enrolled in teaching practice modules were selected as a sample. Data sources included lesson plans prepared, lessons delivered, administrative and co-curricular duties performed by the students, as well as evaluation reports by supervisors, cooperating teachers, and school principals. There were improvements in the student teachers’ lesson plan formation and their overall learning. Data obtained through personal visits by VU faculty was used to verify and assess actual classroom teaching. Lack of regular attendance and punctuality by student teachers was observed as a result. Internal review of the VU system as it relates to the teaching practice modules was conducted to address any shortcomings in the course(s), its procedures, and its controls. Recommendations for improving the system, such as grading the modules, peer-assessment, and orientation workshops for student teachers are provided, as well as suggestions for developments in the teaching practice modules themselves.

EdTech Horizon Scan: Blockchain technology in education - Beoku-Betts, Iman; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking on a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This EdTech Horizon Scan examines the use of blockchain technology in education. Beginning with an overview of blockchain technology, the scan explains what blockchain technology is and how it works. The next section focuses on how blockchain technology can be used in education. In particular, it looks at the benefits of using blockchain technology for micro-credentialing and ownership of learning credentials, the transfer of credits and smart contracts, storing student credentials, identity verification and intellectual property protection. Section 4 gives a summary of the use of blockchain technology, noting the different challenges that may be associated with adopting blockchain technology into education systems. Section 5, gives real examples of the use of blockchain technology in education and different education institutions. Key words: blockchain; cryptography; data; decentralised database; digitalisation; education; micro-credentialing; smart contracting; student credentials; verification An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.

“Being on the wrong side of the digital divide”: seeking technological interventions for education in Northeast Nigeria - Martens, Marianne; Hajibayova, Lala; Campana, Kathleen; Rinnert, Gretchen Caldwell; Caniglia, Joanne; Bakori, Isa Garba; Kamiyama, Tsukuru; Mohammed, Liman Audu; Mupinga, Davison M.; Oh, Olivia Jeonghwa (Aslib Journal of Information Management, 2020)
Purpose This paper aims to report the initial findings of a project aiming to re-establish basic education in conflict-ravaged states in Northeastern Nigeria and to improve education providers' ability to plan and deliver basic educational services. The authors present a preliminary analysis of Nigerian teachers' access to information communication technology (ICT), their technology skills, as well associated national ICT policies. Design/methodology/approach This case study uses results from two co-designed tools, administered using KoboToolbox to Education Managers in the first instance, and teachers in the second. The data from the tools form the basis for analysis. Findings In the first instance, educational managers reported a lack of access to technology, the internet and to training and professional development. In the second instance, teachers reported issues present in the classroom environment, including poor infrastructure, a lack of resources and over-crowded classrooms. Very few teachers had access to computers or to the internet. Research limitations/implications The 33 educational managers represent a small sample size and may not be fully representative of the region covered. The ICT Capacity Audit tool listed Excel in two different areas – basic Excel skills and using Excel for data analysis – which could have caused confusion for participants. The data collection should be repeated, expanded and compared for consistency. For the team, changes to the proposed (SENSE) box content meant that we were not able to deliver low-tech tools, such as Boogie Boards, or high-tech tools, such as tablets, to schools. Originality/value Despite seemingly insurmountable challenges, the research team identified low-tech tools as a feasible resource in the classroom. Existing tools, such as teachers' smartphones and use of the WhatsApp application, can be used for sharing educational resources and providing teacher training. This paper argues that Nigeria needs up-to-date national ICT policies to guide in-country efforts to develop implementation of information technology initiatives for education.

Flexible strategies for ensuring quality learning outcomes in education in emergencies (NEQMAP 2021 thematic review) - Tarricone, Pina; Teo, Ian; Mestan, Kemran; Sundarsagar, Kris; Killimangalam, Ashtamurthy; Abd Razak, Nordin (International Education Research, 2021)
The COVID-19 pandemic has interrupted schooling for students globally and challenged how policy-makers might respond and recover from this protracted emergency. In collaboration with NEQMAP, the GEM Centre has conducted a rapid review of policy and practice documents for 14 countries, and an online survey with policy-makers in 7 of them to identify the types of flexible learning strategies that were implemented over the course of this pandemic. An education in emergencies Policy Monitoring Framework was used both to guide the analysis of documents and survey data, and to provide the basis for reporting findings. The range of flexible learning strategies identified in this review focused on: enhancing system level processes to ensure quality learning outcomes; streamlining the curriculum; utilising a range of student assessment and monitoring approaches; improving inclusion and equity for vulnerable learner groups; and supporting school leaders and teachers using education tools and resources, professional development courses, and support networks.
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

DIKSHA - Platform for School Education – Apps on Google Play - DIKSHA (2020)
The DIKSHA platform offers teachers, students and parents engaging learning material relevant to the prescribed school curriculum. Teachers have access to aids like lesson plans, worksheets and activities, to create enjoyable classroom experiences. Students understand concepts, revise lessons and do practice exercises. Parents can follow classroom activities and clear doubts outside school hours. App highlights • Explore interactive material created by teachers and the best Indian content creators for teachers and students in India. By India, for India! • Scan QR codes from textbooks and find additional learning material associated with the topic • Store and share content offline, even without Internet connectivity • Find lessons and worksheets relevant to what is taught in the school classroom • Experience the app in English, Hindi, Tamil, Telugu, Marathi, Kannada, Assamese, Bengali, Gujarati, Urdu with additional Indian languages coming soon! • Supports multiple content formats like Video, PDF, HTML, ePub, H5P, Quizzes - and more formats coming soon! Advantages for teachers • Find interactive and engaging teaching material to make your class interesting • See and share best practices with other teachers to explain difficult concepts to students • Join courses to further your professional development and earn badges and certificates on completion • View your teaching history across your career as a school teacher • Receive official announcements from the state department • Conduct digital assessments to check your students’ understanding of a topic that you have taught Advantages for students and parents • Scan QR codes in your textbook for easy access to the associated lessons on the platform • Revise lessons that you learnt in class • Find additional material around topics that are difficult to understand • Practice solving problems and get immediate feedback on whether the answer is correct or not. Want to create content for DIKSHA? • Help teachers deliver concepts in an easy and engaging manner • Help students learn better in and outside class. • Get involved in providing students with high quality learning material, irrespective of where they study • If you wish to be a part of this movement, visit the VidyaDaan portal using vdn.diksha.gov.in This initiative is supported by the Ministry of Human Resources Development (MHRD) and led by the National Council Of Educational Research And Training (NCERT) in India.

Education in times of restriction: an examination of refugee girls’ and young women’s access to learning during COVID-19 school closures in Pakistan - Barnes, Katrina; Ashlee, Amy; Mukankusi, Aimee; Pacitto, Julia; Rabi, Asma; Thomas, Matt; Ullah, Noor; Zazai, Rozina; Zhao, Annette (Educational Research for Policy and Practice, 2023)
This paper examines the extent to which refugee girls and young women were able to access learning during COVID-19 education closures in Pakistan, and the role that EdTech played in their learning access. It is based on findings from a survey with 403 Afghan refugee students, along with in-depth interviews with six young female refugees. The research shows that, while the majority of female refugee students were able to continue accessing education in some form during school closures, learning access was nevertheless limited, and a sizable minority were not engaged in any learning during this time. Teacher and institutional support was either absent or inadequate for many students, and infrastructure and devices that serve to support remote learning were not always reliable or accessible. Although male respondents were less likely than females to engage in independent study during the closures, refugee girls and young women were significantly less likely than their male counterparts to own the devices they needed for learning. The findings demonstrate how targeted investment in specific types of EdTech and teacher professional development, as well as supporting educational institutions in the establishment of remote learning opportunities, could help sustain learning during future periods of educational restriction.
Keywords: COVID-19; Distance education; Educational technology; Gender; Pakistan; Refugee education

Education in times of restriction: An examination of refugee girls’ and young women’s access to learning during COVID-19 school closures in Pakistan - Barnes, Katrina; Ashlee, Amy; Mukankusi, Aimee; Pacitto, Julia; Rabi, Asma; Thomas, Matt; Ullah, Noor; Zazai, Rozina; Zhao, Annette (Educational Research for Policy and Practice, 2024)
Abstract This paper examines the extent to which refugee girls and young women were able to access learning during COVID-19 education closures in Pakistan, and the role that EdTech played in their learning access. It is based on findings from a survey with 403 Afghan refugee students, along with in-depth interviews with six young female refugees. The research shows that, while the majority of female refugee students were able to continue accessing education in some form during school closures, learning access was nevertheless limited, and a sizable minority were not engaged in any learning during this time. Teacher and institutional support was either absent or inadequate for many students, and infrastructure and devices that serve to support remote learning were not always reliable or accessible. Although male respondents were less likely than females to engage in independent study during the closures, refugee girls and young women were significantly less likely than their male counterparts to own the devices they needed for learning. The findings demonstrate how targeted investment in specific types of EdTech and teacher professional development, as well as supporting educational institutions in the establishment of remote learning opportunities, could help sustain learning during future periods of educational restriction.

The potential and prerequisites of effective tablet integration in rural Kenya - Heinrich, Carolyn J.; Darling-Aduana, Jennifer; Martin, Caroline (British Journal of Educational Technology, 2020)
This study investigates how pedagogical, cultural and institutional factors interact with technical knowledge in educational technology integration and how they relate to equitable and effective technology use in low-resource settings. In the context of a one-to-one tablet initiative in rural Kenya, we explore how these factors constrain or support access to technology, instructor capacity, student engagement and student learning, as well as their implications for reducing educational and digital divides. We employ a mixed methods, such as a quasi-experimental (prepost, nonequivalent control group) research design that draws on data from classroom observations, teacher interviews, student surveys and focus groups, and assessments of student academic performance to generate evidence on classroom practices and student learning in schools with access to tablets, while also highlighting core challenges to successful technology integration. Our findings contribute to the identification of prerequisites and supporting factors for successful educational technology integration, as well as policy levers and school-based strategies that are likely to increase equitable access to quality learning experiences in schools in low-resource contexts. Practitioner Notes What is already known about this topic A lack of funding, planning and infrastructure hinder information and communication technology (ICT) integration. Procurement of educational technology and infrastructure improvement efforts has reduced digital divides, but learning divides persist in implementation. Insufficient teacher technology expertise and professional development constrain teacher's effective use of educational technology in classrooms. What this paper adds We employ mixed methods—triangulating the student assessment data with data from student surveys and focus groups, teacher interviews and classroom observations—to identify how pedagogical, cultural and institutional factors interact with technical knowledge in ICT integration in ways that support or constrain student learning in low-resource contexts. We find that more attention is needed for cultural factors that interact with pedagogical and technical skills to ensure that the classroom instructors' attention is equitability distributed in ways that discourage in-class “tracking” and differential access to quality learning experiences, such as some teachers' disregard of “slow learners” in the classroom. In low-resource contexts, providing even basic levels of infrastructure (eg, a consistent power source) and access to general technical knowledge requires more creative and concerted efforts from school leadership and instructors, such as the offer of tutorials and reading clubs outside of the class to expand access and improve the use of devices. Implications for practice and/or policy We find that device sharing can have positive effects on peer-to-peer learning, which suggests that policymakers in Kenya should weigh the benefits of achieving one-to-one device access against the potential advantages of alternative investments, such as expanding professional development on the integration and use of currently available devices. Increasing opportunities for peer-to-peer learning and exchange (among teachers and students) and building shared capacities for ICT integration can help reduce technical issues and lost instructional time.

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
Keywords: ___working_potential_duplicate

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

Universal Design for Learning: Is It for Everyone? - Rose, D; Meyer, A (2006)
Universal Design for Learning (UDL) stands at the forefront of contemporary efforts to create universal access to educational curricula for all students, including those with disabilities. The "universal" in UDL does not mean there is a single optimal solution for everyone. Instead, it underscores the need for flexible approaches to teaching and learning that meet the needs of different kinds of learners. In this first UDL Reader, Anne Meyer and David H. Rose, cofounders of CAST, the educational nonprofit that developed the UDL framework, bring together a collection of articles on the practical, classroom dimensions of the UDL revolution in education. The authors offer insights on learner differences, the capacities of new media in the classroom, and effective teaching and assessment practices. The volume also includes lessons from teacher professional development workshops, classroom-based research, and UDL practitioners themselves. A highly readable volume aimed particularly at school teachers and administrators, this book is also an uncommonly accessible introduction to UDL for all readers committed to creating improved and universal access to educational materials for all students. Following a preface (Anne Meyer and David H. Rose), this book contains the following chapters: (1) Applying Universal Design for Learning in the Classroom (Peggy Coyne, Patricia Ganley, Tracey Hall, Grace Meo, Elizabeth Murray, and David Gordon); (2) A UDL Case Story and Model Lesson: Reading Challenges in Geography and Social Studies (The Staff at CAST); (3) Frequent Questions about Universal Design for Learning (Grace Meo); (4) A Level Playing Field: UDL in the Classroom (Lani Harac); (5) Teacher Perspectives: UDL in the Elementary Classroom (Kirsten Lee Howard); (6) Teacher Perspectives: Strategy Instruction Goes Digital (Nicole Strangman); (7) Implications of Universal Design for Learning for Classroom Assessment (David H. Rose and Robert P. Dolan); (8) The Promise of New Learning Environments for Students with Disabilities (Bart Pisha and Skip Stahl); (9) Transforming the Textbook to Improve Learning (Skip Stahl); (10) Engaging the Text: Brain Research and the Universal Design of Reading Strategy Supports (David H. Rose and Bridget Dalton); and (11) Teaching Internet Literacy Strategies: The Hero Inquiry Project (Maya B. Eagleton, Kathleen Guinee, and Karen Langlais). An index is also included.

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...

The current level of competence of schoolteachers on how to use cloud technologies in the educational process during COVID-19 and the Russian-Ukrainian war - Vakaliuk, Tetiana; Spirin, Oleg; Antoniuk, Dmytro; Medvedieva, Mariia; Osova, Olha; Novitska, Inesa (Myroslav I. Zhaldak Symposium on Advances in Educational Technology, 2021)
During the period of total lockdown, teachers had to move to distance learning to organize a continuous educational process, which is not possible without the active use of modern information and communication technologies, including cloud services. Because of this, at the beginning of the pandemic, Zhytomyr Polytechnic State University conducted several free distance online courses for teachers, which included studying the possibilities of using cloud technologies in teaching in a pandemic. Somewhat later, some secondary schools in Zhytomyr expressed a desire to take the same courses, but in person. 98 teachers of schools of the city of Zhytomyr were covered by training on courses “Cloud technologies in the educational process in the conditions of quarantine”. After face-to-face courses, teachers in Zhytomyr schools have significantly increased their competence in the use of cloud technologies in the educational process in the context of the COVID-19 pandemic. Not only has their level increased in general, but the horizons regarding the variety of cloud services that should be used in distance learning have expanded. Course training, organized according to scientifically sound methods, helps to increase the motivation of students (teachers) to self-study, as well as to the future use of cloud technologies in the educational process. The two-year pandemic and the start of a full-scale war between Russia and Ukraine contributed to the fact that teachers of secondary schools began to actively engage in self-education and self-development. If earlier (at the beginning of the pandemic) it was difficult for teachers to switch to online learning, then with the outbreak of war, teachers were already ready to use various online tools in their practice. As the study showed, all the interviewed teachers continued their self-education in different ways, studied a large number of services that can be used in the educational process, and provided the authors with ideas for further expanding the courses according to their desires, which should be used in the educational process. It should be noted that it is important that all the respondents unanimously approved that they use the acquired competencies in their professional activities during the period of Russian aggression. In addition, in additional comments, teachers noted that among their acquaintances there are many teachers who want to take such courses since at one time they had no desire or motivation.

A Study on Using Serious Games in Teaching German as a Foreign Language - Alyaz, Yunus; Spaniel-Weise, Dorothea; Gürsoy, Esim (Journal of Education and Learning, 2017)
The interest in Digital Game-Based Language Learning (DGBLL) has increased considerably in recent years although being a relatively new approach. Despite the interest that DGBLL took, the studies in the context of German as a Foreign Language (FL) are quite limited. Moreover, DGBLL in the Turkish context is not prevalent. Due to this gap in the literature, a research project was launched at a big state university in Turkey in 2014 to explore the potentials and limitations of DGBLL. The study focuses specifically on serious games for FL teaching and learning. The aim of the project, in addition to the promotion of linguistic skills of the learners, is to contribute to the development of professional qualifications of the future FL teachers. The present research aims to report on the pilot study of the project. A one group pre-test post-test research design was used in the study. Quantitative data was collected via two opinion questionnaires implemented at the beginning and at the end of the process as well as a receptive vocabulary test. Qualitative data was collected via semi-structuted interviews and game diaries that participants kept. Two serious games for German was selected and used with traditional dictation, transcription and reading comprehension activities. The results of an 11-week gaming activity indicated significant differences between pre- and post-tests in vocabulary. Additionaly, age was found to be an important factor that affects participants’ attitudes towards serious games. The results indicate that the participants found game activities useful for the development of other language skills.

Primary school learning in sub-Saharan Africa during COVID-19: A scoping review of responses and recovery initiatives induced during school closures - Wawire, Brenda; Barnes-Story, Adrienne; Kiru, Elisheba; Kim, Sungkyum (Current Issues in Comparative Education, 2023)
Globally, the COVID-19 pandemic caused unprecedented disruptions in education. School closures quickly followed the onset of the pandemic to contain the spread of the virus, forcing millions of students out of their regular academic calendars. Countries put in place interventions aimed to reduce the deleterious effects of school closures and disruptions in learning. For instance, many countries used various mediums to provide students with distance learning. This scoping review examines the interventions that education systems in low- and middle-income Sub-Saharan African (SSA) countries (LMIC) implemented to mitigate learning loss in reading and writing skills among early grade learners (i.e., children attending primary schools) and discusses the reach of those programs. This review highlights the proportion of students reached by the targeted mitigation measures, revealing that LMIC countries in SSA provided students with remote learning opportunities through radio and television programming, provided teachers with professional development on the use of novel tools, and provided parents and families with support to help learners at home. However, these disruptions affected the traditional assessment methods. Various assessment methods were implemented to measure student progress, but there is a need for appropriate progress monitoring tools and accurate data to measure the effectiveness of the interventions. Many LMIC implemented Return-to-School policy frameworks, processes, and principles that ensured safe learning continuity.
Keywords: COVID-19; early grades; interventions; learning loss; literacy; responses

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)

Learning ecologies through a lens: Ontological, methodological and applicative issues. A systematic review of the literature - Sangrá, Albert; Raffaghelli, Juliana Elisa; Guitert‐Catasús, Montse (British Journal of Educational Technology, 2019)
The concept of learning ecologies emerged in a context of educational change. While the “learning ecologies” construct has offered a broad semantic space for characterizing innovative ways of learning, it is also true that its potential to promote innovative educational interventions may have been hindered by this same broadness. Based on this assumption, in this paper the authors carried out a systematic review of the literature on learning ecologies with the aim of analysing: (1) the varying definitions given to the concept, including the ontological perspective underlying the phenomena studied; (2) the methodological approaches adopted in studying the phenomenon; and (3) the applications of the research on this topic. Throughout this analysis, the authors attempt to describe the criticalities of the existing research, as well as the potential areas of development that align well with the theoretical/ontological issues, methodological approaches and educational applications. The authors selected and analysed 85 articles, which they then classified in a set of 20 categories defined by them on a theoretical basis. Moreover, in order to triangulate the manual coding, a bibliometric map was created showing the co-citation activity of the 85 papers. The emerging picture showed significant variability in the ontological definitions and methodological approaches. In spite of this richness, few educational applications currently exist, particularly with regard to technology-enhanced learning developments. Most research is observational, devoted to describing hybrid (digital and on-site) learning activities that bridge the gap between the school and social spaces. Furthermore, many of the studies relate to the field of secondary education, with fewer studies exploring adult learning and higher education. The studies dealing with professional development relate mostly to teachers’ continuing education. The authors conclude that the concept of learning ecologies could be used to address further experimental and design-based research leading to research applications if there is proper alignment between the ontological, methodological and applicative dimensions. The main potential of this strategy lies in the possibility of supporting learners by raising their awareness of their own learning ecologies, thereby empowering them and encouraging them to engage in agentic practices. This empowerment could help maintain and build new and better learning opportunities, which every learning ecology can incorporate, amidst the chaotic abundance that characterizes the digital society.
Keywords: Reviewed

STEM: breaking gender stereotypes - UNGEI (UNGEI, 2021)
In some Western cultures, pink is for girls, blue is for boys. Why? It just is. You might hear mothers remark with wonder that their little girls just love the pink dress (that was given to them). You may have heard fathers insist that their sons not wear pink clothing. It’s interesting to think that at the end of the nineteenth century in the USA, pink was actually the colour preferred for boys, it being a softer version of military red. Things change. The accepted wisdom that stereotypes originally come from a place of truth is erroneous. No credible research has indicated that girls gravitate to pink things without any cultural prompting. Our gendered behaviour is primarily socially conditioned. Research suggests that the idea of a female brain and a male brain is false [1]. Rather, the plasticity of the brain means that it can be moulded – from birth onwards – through learning, engaging in the world and being socially conditioned. This includes learning and absorbing gender stereotyping. Gendered colours are harmless though, right? No, not really. Any gender stereotype will reinforce a gender bias. In 2019, a Fawcett Society study found that 45 per cent of people said that when they were children, they experienced gender stereotyping as they were expected to behave in a certain way [2]. Seven in 10 younger women (18-34s) affected by stereotypes say their career choices were restricted [3].  Around 70 per cent of individuals in 34 countries associated science with males more than with females [4]. © UNICEF/UN0364176/XimendazCaregivers and teachers often reproduce the stereotype that boys are better in science and mathematics than girls, encouraging girls to aspire to ‘female-oriented’ careers instead of ‘male’ STEM related ones [5,6]. To compound this negative reinforcement, curriculum and learning materials reinforce gender stereotypes and unequal gender norms in STEM. In India, illustrations in math and science textbooks in primary school show 6 per cent girls, but more than 50 per cent boys [7]. The stereotyping sanctioned by parents, teachers and the curriculum itself negatively impacts a girl’s self-belief – and her future aspirations [8]. When three women won the Nobel Prize for science in 2020, it was newsworthy partly because not many women have won the prize over the years. But is it also newsworthy because, even today, many would not expect women to be such high achievers in science, technology, engineering and mathematics. Engineering is for boys. Mechanical toys are for boys. Science experiments are for boys. These are the stereotypes we learn. Where does this thinking come from? There’s obviously a lot to unpack here: traditional roles in society born out of a female’s capability to bear children, or stronger upper body strength, on average, amongst males, for example. But they don’t speak to our cognitive and intellectual potential. And I’m sure there would be many who would dispute every particular of the above. Questioning norms that are the foundation of our interaction with the world is difficult for all of us to do. © UNICEF/UN0145559/SchermbruckerAcknowledging that stereotypes exist is straightforward. Deciding that they shouldn’t constrain our behaviour and life path is a little harder. But confronting and actively challenging these stereotypes – indeed, breaking them! – is an altogether more difficult process. How do we do it? How do we take organic and grassroots solutions toward a tipping point of change? This International Girls in ICT Day (22nd April), UNGEI hosted an Instagram Live event to explore these important questions. Transform Education members Maryam and Nivaal and NASA engineer Farah Alibay talked about working with NASA on the Mars 2020 mission, how to drive progress for gender equality in STEM and why representation matters.  Shifting power in STEM starts with listening to the experts and girls themselves, such as the inspiring changemakers on UNICEF’s Teen. Girl. Activist site. Debunking stereotypes is in their very capable hands… The first thing we need to do is recognize that there is a societal bias... let’s recognize that we are treating girls differently and that they are not being given the same opportunities. Now that we’ve started to recognize that problem, I think...normalizing STEM for girls, providing resources, and providing a safe space for girls is really important. Farah Alibay, Systems Engineer, NASA (UNGEI International Girls in ICT IG Live Event) Some choose to tackle stereotypes head-on, like the ‘Talent Viewer’ in the Netherlands, to break the stereotype that girls can’t successfully engage in STEM. Girls and boys in primary school (aged 9 to 12) assign talents to each other, discuss them, then investigate what STEM professions used these talents. This looks at certain talents being appropriate for STEM, not gender. A woman working in a STEM field talks to the classes about her job, effectively role modelling for girls. Critically, parents are encouraged to discuss the talents with their child and teachers participate in professional development on gender awareness, STEM education and talent development. The evaluation of the programme has indicated a positive change in attitude in both girls and boys towards girls’ participation in STEM. Around 46,000 children have engaged in this exciting work to date. © UNICEF/UNI363793/AryanAnother approach is simply to place girls in STEM-related industries, to show that it’s a natural place for both men and women, like the ‘Technogirls’ programme. This is a public-private partnership in South Africa that seeks to enhance the career uptake by disadvantaged girls in STEM fields (which is critical to the country’s economic growth). It identifies school-going young women from disadvantaged communities and places them in corporate mentorship and job-shadowing programmes. So far, 11,241 girls have engaged in structured job-shadowing programmes – and 78 per cent of them who have gone on to study in one of three scarce skills STEM fields in the country. These women become role models for the next generation and many of them are now mentors to new intakes of girls. The best investment is...girls' quality STEM education. And if we can give support to girls for quality STEM education, they will pay back successfully in the future to make a better world. Nasrin Siddiqa, Brookings Echidna Global Scholar (UNGEI@20 Forum) Other education systems have worked on how they teach STEM to ensure that girls aren’t overlooked or left behind. UNICEF in Ghana has worked with the Korea International Cooperation Agency and the Ghana Education Service on the ‘Better Life for Girls’ project. Focused on dismantling gender norms, the project included gender-responsive pedagogy (teaching and learning processes that pay attention to the specific learning needs of girls and boys) in mathematics and science, and providing life skills and leadership training for adolescent girls – helping more than 4,000 girls to stay in school and explore their potential. Training teachers on gender-responsive pedagogy helped to change girls’ perceptions of their own abilities – and this has a knock-on effect in the learning they pursue. If girls had believed the stereotype about not being good at mathematics, what other stereotypes can they challenge? And that is surely a question for all of us. During UNGEI’s 20th Anniversary Forum (UNGEI@20), activists, experts and leaders came together to explore what it will take to close the STEM gender gap in education and thus help girls fulfil their leadership potential. The event concluded that we need a gender-transformative approach to education, increasing opportunities for girls to develop digital skills and building their confidence and aspirations to pursue careers as STEM professionals. Technology is such a useful tool because it doesn't just provide mentors. It provides resources. It provides community. When you take away that access to tech, you take away that access to education as well, that basic human right. Audrey Pe, WiTech Founder (UNGEI@20 Forum) In the pursuit of equity in digital literacy and STEM skills, especially as we look toward a world of work where 9 in 10 jobs will require digital skills, UNICEF is proud to mobilize commitments alongside other public and private partners as an Action Coalition for Technology and Innovation as part of the Generation Equality Forum. These commitments include advancing girl-designed solutions to learning fit for a digital world, and advancing an outcome fund for digital literacy equity that brings together the best of public and private human and financial resources. © UNICEF/UNI363793/AryanIn the context of the Covid-19 crisis, which exposed structural inequalities in education and access to technology, these types of interventions are more important than ever. If we are to deliver on our global commitments to Sustainable Development Goals (SDGs) 4 and 5, we need to understand just how much harm stereotypes of any kind can be, particularly to young, vulnerable, curious children. If we are serious about helping children to achieve their potential – for their own development and so they can contribute to their communities and the world – then we need to minimize the forces that limit that potential. This includes gender stereotyping. We need to start celebrating children for who they are, not who we think they should be, based on a pointless stereotype. Let’s help them to access their rights to be themselves. Let’s help them to wear whatever colour they like.

What Matters Most for Education Management Information Systems: A Framework Paper - Abdul-Hamid, Husein (SABER Working Paper Series, 2014)
Keywords: Academic Assessments; Access to Data; Access to Education; Access to Information; Adult Education; Annual School Census; Application Programming; Assessment Framework; Average Teacher Salaries; Basic Education; Basic Education Statistics; Best Practice; Business Intelligence; Care Providers; Class Sizes; Classroom; Classroom Learning; Classrooms; Client Countries; Communication Technology; Communications Technologies; Communications Technology; Completion Rates; Continuing Education; Curriculum; Data Analysis; Data Collection; Data Coverage; Data Gathering; Data Providers; Data Sharing; Data Sources; Data Systems; Data Warehouse; Decision Makers; Decision Making; Decision-Making; Demand for Education; Domain; Domains; Early Childhood; Early Childhood Development; Early Childhood Education; Educated Population; Education Budget; Education Data; Education Development; Education Institutions; Education Management; Education Management Systems; Education Outcomes; Education Planning; Education Policies; Education Policy; Education Providers; Education Services; Education Statistics; Education Strategy; Education System; Education Systems; Education Targets; Education Teachers; Education for All; Educational Development; Educational Expenditures; Educational Inputs; Educational Outcomes; Educational Planning; Educational Processes; Educational Quality; Educational Sciences; Educators; Enabling Environment; Enrollment Data; Enrollment Levels; Enrollment Rates; Enrollment Statistics; Equitable Education; Expert Opinion; Female Teachers; Financial Performance; Formal Education; Functionalities; Functionality; Gender Equality; Gender Equity; Gender Parity; Gender Parity Index; Girls; Global Education; Gross Enrollment; Gross Enrollment Ratio; High Quality Education; Human Resources; Improvement of Education; Information Gaps; Information System; Information Systems; Information Technology; Innovation